Intersex Brain Transcriptome in Female-Mimicking Males of a Fish with Sequential Alternative Reproductive Tactics. - CARDOSO S.D., GONÇALVES D., GOESSMAN A., CANÁRIO A.V.M., OLIVEIRA R.F. (Molecular Ecology)

Neurogenomic plasticity underlying alternative reproductive tactics in the peacock blenny (Salaria pavo) males - Cardoso, S.D.; Gonçalves, David Manuel Flores; Goessman, A.; Canário, Adelino Vicente Mendonça; Oliveira, R.F. (Molecular Ecology)

Cross-cultural adaptation and validation of the Chinese version of Skills and Needs Inventories in Functional Behavior Assessments and Interventions (SNI-FBAI-CN) - Chen, Mo; Dutt, Anuradha S.; Nair, Rahul (Behavioral Interventions)
Cross-cultural adaptation and validation of measures are necessary to provide evidence-based educational intervention services among children with autism spectrum disorder (ASD) across countries. Language plays an integral role in the cross-cultural adaptation and validation process of measures. Currently, there are limited validated tools in Chinese available to assess special education teachers' skills in functional behavior assessments and interventions in Mainland China to effectively support students with ASD. This study aimed to validate a Chinese version of the Skills and Needs Inventories in Functional Behavior Assessments and Interventions (SNI-FBAI-CN) in mainland China. The SNI-FBAI, originally developed and validated in Singapore, in the English language, was translated, culturally adapted, and then administered to 239 special education teachers in two schools for children with ASD in China. Results show that the SNI-FBAI-CN has a three-factor structure (i.e., skills in behavioral assessment, skills in behavioral interventions, and needs for training) that fits the data well, with good reliability for the overall scale, as well as the three subscales. Partial measurement invariance was established between the Chinese and the original Singapore samples, providing additional construct validity evidence for this tool. Limitations of this study and directions for future research are discussed.
Keywords: Chinese; SNI-FBAI; autism spectrum disorders; cross-cultural validation; mainland China; special education teachers

The Teaching of Computer Competences with Cooperative Learning in Macao: Working in Progress - WONG, K., NEGREIROS, J., NEVES, A. (International Journal for Digital Society)

聖多瑪斯思想權威之演變，從1274年至1323年 - 蔡翼倫 (《神學論集》)
本文梳理聖多瑪斯去世至1323年列聖品之間，發生的圍繞其思想權威性的爭議與演變。在這近五十年中，多瑪斯思想的權威性在不斷的爭議與回應中逐漸形成，其中尤其針對他運用亞里士多德的哲學來闡釋天主啟示，及對貧窮勸諭的理解所衍生的論辯。作者指出，以道明會會士為 主的神學家致力於以多瑪斯思想為基點，回應各種反對多瑪斯思想的挑戰，過程中逐漸形成了具有統一性的多瑪斯學派，加以教會內各種歷史性因素，都促成了多瑪斯在1323年7月的亞維農被列入聖品。

Application of D-optimal design for determination of the influence of water content on the thermal degradation kinetics of ascorbic acid at low water contents - Frías, Jesús M.; Oliveira, Jorge C.; Cunha, Luís M.; Oliveira, Fernanda A. (Journal of Food Engineering, 1998)
The kinetics of thermal degradation of ascorbic acid was studied in a Maltodextrin matrix at different temperatures between 75 and 140 °C. Isothermal experiments were performed with samples earlier equilibrated in environments of known aw at 4 °C, enclosed in hermetically sealed vials, with water contents (w) between 0.17 and 1.68 g water/g solids. Sampling times were selected according to an optimal experimental design in terms of minimum confidence regions of the parameters estimated, using the Bigelow model and estimates from preliminary experiments. The results showed a quadratic dependence of the reference D-value and linear dependence of the z-value with moisture content: Dr(140 °C) = 150.07 − 290.73w + 269w2 (min); z = 12.14 + 22.99w (°C) and showed the applicability of D-optimal designs for determining kinetic parameters in complex situations, with limited experimental requirements. The dependence of the rate constants with water content could not be described by the WLF model in qualitative terms, although in absolute values this model could be used with constants similar to those expected from glass transition theory. The thermodynamic analysis of the results showed a good application of the compensation theory in the whole range of water contents.

Publishing mathematics on the World Wide Web - Majewski, M. (Journal of Computer Assisted Learning, 1999)
This paper shows how mathematical concepts can be displayed on World Wide Web pages. A few of the most interesting solutions are outlined although a few others are missing and a few more will be invented very soon. It is for authors to decide which system is the most suitable for their purposes.

Influence of pH and high pressure on the thermal inactivation kinetics of horseradish peroxidase - Lemos, Maria Adília; Oliveira, Jorge C.; Hendrickx, Marc E: (Food Biotechnology, 1999)
The inactivation kinetics of horseradish peroxidase were determined at several values of pH (3, 4, 7, 9 and 10), temperature (40 to 70 °C) and pressure (7, 8 and 9 kbar). The data were obtained by taking samples from the moment that pressure inside the hydrostatic high pressure vessels reached the value specified, and therefore relate to isothermal and isobaric conditions. The inactivation kinetics were non‐log linear and could be individually well described by the conventional two‐fraction model, but the overall consistency of the kinetic parameters of this model was poor and the model was clearly not robust. Inversely, the kinetic model based on the Weibull probability distribution function yielded good individual fits and also a good overall consistency of the kinetic parameters. The whole set of 327 data points could be well described by an overall model considering that the shape parameter (ß) varied with pressure but not with temperature and that the rate parameter (1/α) varied with temperature according to an Arrhenius law, with a pressure‐independent activation energy, and varied exponentially with pressure. The activation energy and the pressure‐sensitivity parameter did not vary with pH up to pH 9. The results suggested a discontinuity of the kinetic behaviour at pH 10, with a different inactivation mechanism prevailing.
Keywords: enzyme barostability; enzyme inactivation; kinetic modeling; protein denaturation

Kinetics of the adsorption of bovine serum albumin contained in a model wine solution by non-swelling ion-exchange resins - Sarmento, M. R.; Oliveira, J. C.; Slatner, M.; Boulton, R. B. (Journal of Food Engineering, 1999)
Adsorption of wine proteins is an essential step in the production of white and rosé wines. In order to develop environmentally friendly adsorption processes, non-swelling adsorbents are required. The performance of selected non-swelling ion-exchange resins (Macro-Prep™ 50S and Streamline® SP) was studied by describing the process kinetics of the adsorption of BSA in a model wine solution. The process was assumed to be diffusion controlled and a shrinking core model was applied. Experiments were performed in the 5–35°C temperature range and with different equilibrium partition coefficients. The results obtained with the shrinking core model were theoretically consistent and the apparent diffusivity values correlated very well with theoretically estimated effective diffusivities combined with a linear dependence of porosity with temperature. Separating the temperature effect on porosity, the apparent diffusivity followed an Arrhenius type dependency with temperature with 16.9 kJ/mole activation energy.
Keywords: Diffusion; Mass transfer; Protein adsorption; Wine stability

Ideology, Linguistic Capital and the Medium of Instruction in Hong Kong - Morrison, Keith; Lui, Icy (Journal of Multilingual and Multicultural Development, 2000)

Measurement of glass transition in native wheat flour by dynamic mechanical thermal analysis (DMTA) - Pereira, Pedro M.; Oliveira, Jorge C. (International Journal of Food Science & Technology, 2000)
This work describes a method to study glass transition on native starch powders, based on dynamical mechanical thermal analysis using compression tests, and was applied to wheat flour (13.5% water content). This method will allow the determination of Tg in native (unprocessed) starchy materials, with minimal disturbance of the natural structures. The influence of the test conditions (heating rate, frequency and strain) on the glass transition measurements was determined using factorial designs. The values of Tg determined as the maxima of the energy dissipation (peaks in E″) of native flour and of freeze-dried pre-gelatinized flour were not statistically different (around 64 °C). The heating rate did not affect the measurements in the range tested (0.25 to 1 °C min−1). An interactive effect of the strain amplitude and the frequency was detected. The significance of this interaction can be caused by differences in mechanical energy dissipation, which would indicate that not only temperature but also the total energy input may affect this transition. Slight effects of phase separation between gluten and starch were found on native flour.
Keywords: Phase transitions; starch; viscoelastic properties

Selection of low swelling materials for protein adsorption from white wines - Sarmento, Miguel R.; Oliveira, Jorge C.; Boulton, Roger B. (International Journal of Food Science & Technology, 2000)
The protein adsorption capacity of different materials was evaluated to assess their potential efficacy as alternative adsorbents for the removal of proteins from wines, with the purpose of finding suitable low-swelling materials that could be used in a percolated bed. The adsorbents tested were thermally treated sodium bentonite, low-swelling adsorbing clays, ion exchange resins and other protein adsorbents (silica gel, hydroxyapatite and alumina). The materials were evaluated by analysing both the capacity to stabilize untreated white wines, according to a heat test, and by characterizing the adsorption isotherms of bovine serum albumin (BSA) in a model wine (water, ethanol and K-bitartrate). Breakthrough curves in a packed bed were determined experimentally for some materials, showing the influence of the adsorption isotherm shape. Some ion-exchange resins showed a favourable behaviour and have good potential as alternative adsorbents.
Keywords: Bentonite; percolated beds; sorption isotherms; wine stability

Randomised Controlled Trials for Evidence-based Education: Some Problems in Judging 'What Works' - Morrison, Keith (Evaluation & Research in Education, 2001)

Simplicity and Complexity in Contemporary School Leadership: A Response to Grace - Morrison, Keith (British Journal of Educational Studies, 2001)

Testing to Destruction: A problem in a small state - Morrison, Keith; Joan, Tang Fun Hei (Assessment in Education: Principles, Policy & Practice, 2002)

A análise da cultura organizacional escolar através dos seus artefactos - Correia, Ana; Costa, Adelino (Revista do Fórum Português de Administração Educacional, 2003)

Complexity theory and curriculum reforms in Hong Kong - Morrison, Keith (Pedagogy, Culture & Society, 2003)

Toward an educational agenda for Macau at the start of the new millennium - Morrison, Keith (China Perspectives, 2003)

Improving Teaching and Learning in Higher Education: Metaphors and Models for Partnership Consultancy - Morrison, Keith (Evaluation & Research in Education, 2003)

The poverty of curriculum theory: a critique of Wraga and Hlebowitsh - Morrison, Keith R. B. (Journal of Curriculum Studies, 2004)

Liderança feminina nas escolas de Macau: uma abordagem exploratória - Correia, Ana; Costa, Jorge (Revista Portuguesa de Investigação Educacional, 2004)

The Chinese Diaspora in Mozambique - Morais, Isabel (Singapore: The Chinese Heritage Centre Bulletin, 2005)

Pedagogy in higher education - Morrison, Keith (Chinese Cross Currents, 2005)

Structuration theory, habitus and complexity theory: elective affinities or old wine in new bottles? - Morrison, Keith (British Journal of Sociology of Education, 2005)

Undergraduate students in part‐time employment in China - Tam Oi I, Betty; Morrison, Keith (Educational Studies, 2005)

Measuring and Targeting Internal Conditions for School Effectiveness in the Free State of South Africa - Kgaile, Abraham; Morrison, Keith (Educational Management Administration & Leadership, 2006)
A questionnaire-based methodology for constructing an overall index of school effectiveness is reported, focusing on within-school conditions of schools, which is currently being used in the Free State of South Africa. The article reports the construction and use of a straightforward instrument for measuring the effectiveness of key aspects of the conditions for school effectiveness in the Free State, using a variety of dimensions. It indicates how this instrument can identify where to intervene in improving schools in order to gain the maximum return on investment of time, effort, development activity and support. The instrument provides aggregated and disaggregated data for individual schools, groups of schools and whole districts, both at a single point in time and over time, thereby enabling the most economical and beneficial development to be planned for targeted individual schools and groups of schools. It enables users to identify the key drivers of the internal school conditions for effectiveness, development and change in schools.

Smallpox Vaccinations and the Portuguese in Macao - Morais, Isabel (Review of Culture, 2006)

Paradox Lost: Toward a Robust Test of the Chinese Learner - Morrison, Keith (Education Journal, 2006)
This article suggests that attempts to date to unravel the paradox of the Chinese learner are incomplete and inadequately modeled, and that the complexities of the paradox have not yet been fittingly operationalized or alternative explanations of research data investigated. It contends that attempts either to state or to unravel the paradox are chimerical, as they risk oversimplifying a complex phenomenon, the extent and nature of which are insufficiently understood to date. The article argues that investigating the phenomenon of Chinese learners' strong performance in international measures of achievement requires researchers to operate more rigorously in their search for alternative and multiple explanations of results in terms of causality, sampling, and representing heterogeneity. Several explanations of data on the paradox are presented, and alternative explanations which might be more usefully explored are provided. The article also questions the extent to which research on the Chinese learner, with a search for a unitary set of characteristics, is not, itself, prey to totalizing, collectivist ideologies cast in unrealistic meta-narratives. Recommendations are made for further research.

Sensitive educational research in small states and territories: the case of Macau - Morrison, Keith (Compare: A Journal of Comparative and International Education, 2006)

Does repeating a year improve performance? The case of teaching English - Morrison, Keith; Ieong On No, Anna (Educational Studies, 2007)

Burnout and Service Employees' Willingness to Deliver Quality Service - Humborstad, Sut I W; Humborstad, Bjarte; Whitfield, Richard (Journal of Human Resources in Hospitality & Tourism, 2007)
Employees are vital for enhancing customer satisfaction and loyalty in service organizations because their proactive involvement is an essential part of delivering the services offered. With the recent rapid growth of tourism in the Macau SAR, service employee workloads are clearly increasing, and consequently one would expect that the incidence of job burnout is rising. This study uses the well-known Maslach Burnout Inventory (MBI) to investigate the relationship between service employees' burnout and their willingness to deliver quality services. Self-administered questionnaires from 110 operational staff in three hotels in Macau have been analyzed. The results indicate that job burnout reduces staff's willingness to deliver quality services and that this effect is moderated by individual staff's level of affective organizational commitment, and their perceptions of the extent of organizational and supervisor support provided by the organization. Based on these results, practical managerial strategies to improve service performance are identified.
Keywords: Job burnout; affective organizational commitment; perceived organizational support; perceived supervisor support; quality service delivery willingness

Educational Philosophy and the Challenge of Complexity Theory - Morrison, Keith (Educational Philosophy and Theory, 2008)

Implementation of empowerment in Chinese high power-distance organizations - Humborstad, Sut I W.; Humborstad, Bjarte; Whitfield, Richard; Perry, Chad (The International Journal of Human Resource Management, 2008)
The importance of empowerment in service industries is recognized by practitioners and scholars in the West but there has been limited investigation of its impact on the willingness of service personnel in a high power-distance culture. This study examines how empowerment can be facilitated in the high power-distance context of China. Regression and path model analysis using a sample of 290 service employees from six 4-star to 5-star hotels in the Macau SAR China indicate that empowerment positively leads to higher service willingness and this relationship is mediated by performance-based rewards, and organizational and supervisor support. These findings have implications for HR managers considering or using empowerment.
Keywords: empowerment; high power-distance culture; organizational support; performance-based rewards; supervisor support; training

Men and women in employment in Macau: A longitudinal survey of inequality. - Morrison, Keith (Journal of Macau University of Science and Technology, 2009)

School inspection in small states and territories: an overview and case study of Macau - Morrison, Keith (Compare: A Journal of Comparative and International Education, 2009)

An exploratory study of students' consumption of non‐alcoholic beverages in Nigeria: A qualitative perspective - Gbadamosi, Ayantunji; Olukayode Iwaloye, Ojo; Bamber, David (Nutrition & Food Science, 2009)
Purpose – Given the diversity which exists among various groups of consumers, the purpose of this paper is to explore students' consumption of non‐alcoholic beverages in Nigeria. Design/methodology/approach – Three focus groups and 20 in‐depth interviews were conducted with students in three universities located in Lagos, Nigeria. Findings – Initial findings indicate that these students' consumption of non‐alcoholic beverages is influenced in many ways. Nevertheless, the most striking of these influences are found to be convenience of purchase, along with availability, price, health concerns, and culture/social reasons. Originality/value – The main contribution of the study lies in the relevance of segmentation, targeting, and positioning activities of business organisations in respect of marketing of non‐alcoholic beverages. Based on the findings, the empirical study will serve as a valuable input to marketers in their planning, analysis, and implementation of appropriate marketing strategies to students vis‐à‐vis the highlighted influences on their consumption of this category of food. It will thus serve as a tool for creating competitive advantage in this prevailing volatile business environment.
Keywords: Consumer behaviour; Nigeria; Non‐alcoholic drinks; Students

Use of CALMS to enrich learning in introductory programming courses - Thota, Neena (Proceedings of the 17th International Conference …, 2009)
Use of CALMS to enrich learning in introductory programming courses

“China Wahala”: the Tribulations of Nigerian “Bushfallers” in a Chinese Territory” - Morais, Isabel (Transtext(e)s Transcultures 跨文本跨文化. Journal of Global Cultural Studies, 2009)
Recent scholarly studies and media coverage have primarily focused on China’s increasing presence and sometimes asymmetrical engagement with Africa in tandem with the new trend of Chinese migration to that continent. Yet, the inverse flux of Africans to China and the emergence of African communities in Southern China over the last decades is influencing some areas of the Pearl River Delta Region, and changing the fabric of cities like Guangzhou, Macau and Hong Kong, in a way without precedent. There are representations or exotic descriptions from some mass circulation magazines and newspapers on the infamous Chungking Mansions in Hong Kong or the so-called “Chocolate-city,”an area centered aroundHongqiao, the village-district and Canaan market in the city of Guangzhou, with its arcades and strip malls filled with ethnic businesses and transnational migrants. In Macau, significant concentrations of African population of different origins are also seen in the “Papa pun” commercial center or in downtown areas. Despite many studies devoted to the “ethnoburbs” in other latitudes, only very recently, these entrepreneurial African communities in Mainland China are starting to become worthy of serious scholarly attention. Yet,there is total absence of studies dealing with the presence of more and more African students and the cultural manifestations of African communities well portrayed in the new African cinema, in music produced by Afro-Chinese bands or even singers.Besides a continuing inward flow of transient Africans who come to China for business on a regular basis, a significant number of settler African traders, particularly Nigerians, have already married local Chinese women, set up families, autonomously run their businesses without recourse to Chinese intermediaries, and established a web of informal and formal committees representing their home nations and states, to solve disputes while maintaining personal and business links with Africa. Besides, those emigrant ‘bushfallers’ who are coming to China solely for business purposes, a new form of “silent” migration of Nigerians comprising students from different backgrounds is enrolling in higher education institutions in the Macau Special Administrative Region of China. These students are coming to pursue their studies or to seek a job to pay their student fees at the margin of the PRC scholarship and stipendprograms for visiting African students that were popular in China in the 1960s and mid-1970s as part of CCP’s foreign policy for Third World aiming friendly relations with Africa. Today, these “transnational” Nigerian students are in their own way affirming their identity and difference, in southern China, in particularly in Macau SAR, thanks to their network of multiple interrelations across nation-states from Africa to Asia and to a combination of perseverance, zeal, and gentleness without subservience. Although they have not been targets for the hostility and even violence like the Shanghai incident of July 1979 or the Nanjing protests in December 1988 at Hehai University targeting African students, today these Nigerian students are facing more subtle forms of ethnocentrism and legal discrimination from immigration laws to daily practices, which always try to associate their citizenship to problematic or easy stereotypes of scam or colour. Yet, at the same time, everything seems to indicate that these newcomers are quick adapting and finding new forms of negotiating their social integration in the Chinese local society which in turn is offering more opportunities.This paper is part of a more ambitious project which aims to assess the new forms of migration from Africa to China and from China to Africa as well as their impact and contribution of globalization. First, this paper considers why and how Macau has evolved from a Portuguese outpost where slavery was a an institutionalized commodity to special administrative region of China where a new urban African community, mostly composed by Nigerian students, is in formation due to opportunities and rapid changes occurring in the region in the first years of the twenty-first century, by comparing the new to old African communities of students and business people/migrant workers from former Portuguese colonies (Angola, Cape Verde, São Tomé and Príncipe, Guinea-Bissau, and Mozambique).Finally, borrowing the title from a sequel movie with the same title of the promising New African cinema, the paper focus on the “China Wahala”or the troubles of these Nigerian students through their tales of their experiences of racism(s) and their negotiations and responses which radically contradicts not only the slogans of cultural diversity propagated by the official discourse and tourist channels as these Nigerians are confronted daily with often dramatic situations ranging from indifference and ostracism to exclusion.

Complexity Theory, School Leadership and Management: Questions for Theory and Practice - Morrison, Keith (Educational Management Administration & Leadership, 2010)
Complexity theory (CT) has had a meteoric rise in management literature and the social sciences. Its fledgling importation into school leadership and management raises several questions and concerns. This article takes one view of CT and argues that, though its key elements have much to offer school leadership and management, caution has to be exercised in accepting CT too readily, as it: (1) is unclear on its own novelty, nature and status; (2) can be regarded as disguised ideology in conflating description and prescription; (3) confuses explanation with prediction; (4) is relativist, undermining its own status; (5) contains problems in its advocacy of self-organization; (6) neglects the ethical and emotional dimensions of leadership and management; and (7) risks exonerating school leaders and managers from reasonable expectations of accountability and responsibility. The article concludes that there are questions to CT at the levels of theory, ontology, deontology and ethics, but that it offers useful challenges for school leadership and management.

Complexities of Languages and Multilingualism - Baragül, Fernando (Educational Challenges in Multilingual Societies, ed. Zubeida Desai et al., 2010)
Complexities of Languages and Multilingualism

Geochemistry and stable isotope constraints on high-temperature activity from sediment cores of the Saldanha hydrothermal field - Dias, Ágata; Früh-Green, G.L.; Bernasconi, S.M.; Barriga, F.J.A.S. (Marine Geology, 2011)

Leadership for self-organisation: complexity theory and communicative action - Morrison, Keith (International Journal of Complexity in Leadership and Management, 2011)

Plasticity in reproductive behaviour in two populations of the peacock blenny - Oliveira, Rui F.; Simões, Mariana G.; Gonçalves, David; Saraiva, João L. (Behaviour, 2011)

Attitudes to mental illness: the effects of labels and symptoms - Found, Andrew; Duarte, Carlos (East Asian Archives of Psychiatry: Official Journal of the Hong Kong College of Psychiatrists = Dong Ya Jing Shen Ke Xue Zhi: Xianggang Jing Shen Ke Yi Xue Yuan Qi Kan, 2011)
OBJECTIVES: To investigate the effects of different Chinese terms for mental illness and related symptoms on the attitudes of adolescents towards sufferers of a mental illness. METHODS: A survey of 578 secondary school students attending 4 schools in Macao was conducted. Each student read a short passage about a new student with a mental illness joining their class. Different versions used different labels to refer to the illness of the new student. The symptoms describing the new student also varied: either describing positive symptoms of schizophrenia or mild negative symptoms only. The attitudes of participants to the new student described were measured. RESULTS: There were significantly more negative attitudes towards the sufferer of a mental illness referred to with a psychiatric label, compared with a general label 'illness'. Participants also expressed significantly more negative attitudes when positive symptoms of schizophrenia were used to describe the new student. The results are discussed in terms of the influence of labels and symptoms on attitudes towards mental illness. CONCLUSIONS: These results supported the existence of 2 additive costs in terms of negative attitudes towards sufferers of mental illness, one associated with the label and the other associated with the symptoms.
Keywords: Adolescent; Adolescent Behavior; Asian People; Attitude to Health; Female; Humans; Male; Mental Disorders; Stereotyping; Students; Surveys and Questionnaires; Young Adult

Education and human capital management in a world city: the case of Singapore - Ho, K. C.; Ge, Yun (Asia Pacific Journal of Education, 2011)
There is considerable evidence to suggest that the human capital needs of the world city differ from what Robinson calls “ordinary cities” or what Markusen and associates term as “second tier cities”. This path is blazed most notably in the field of world cities and the flow of skilled labour, in the work by Sassen and with case examples (finance, law, accountancy) provided in the work by Beaverstock and his associates. This focuses on producer services and migration flows needs to be matched by an accompanying look at city-based strategies. This paper represents an attempt to provide this by providing a case history analysis of Singapore in three stages of growth – as port city, industrial city and as world city – in order to show how the evolving infrastructure associated with human capital (education, immigration and labour policies) allows human capital to be developed, attracted, harnessed, deployed, released and retained.
Keywords: Singapore; human capital; migration

The Development of the Gaming Industry and Its Impact on Land Use - Wan, Yim King Penny; Pinheiro, Francisco (Gaming, Governance and Public Policy in Macao, 2011)
Over the past few years, the gaming industry has changed the face of Macao and the lives of its citizens. The liberalisation of casino licensing in 2002 and the implementation of the Chinese government's new visa regulations in 2003, which permitted many mainland Chinese to travel to Hong Kong and Macao on an individual basis, triggered an economic boom. Foreign investment increased dramatically as international companies began to build casinos and hotels. By 2006, gaming revenues had reached a record annual high of US$10.33 billion, far exceeding the US$6.6 billion made on the Las Vegas strip (Gaming Inspection and Coordination Bureau, 2008). Tourist numbers more than doubled from 11 million in 2002 to 21.7 million in 2009 (Statistics and Census Service, 2009a). Rapid economic growth has come at a price, however. There have been many social dislocations and challenges for public policy that can be attributed to the expansion of the gaming industry. A particular issue is land, a fundamental factor of production and an essential component of the gaming industry's success but in short supply in Macao. The tension between casino requirements for land and public needs spills over into debates on matters as diverse as building height restrictions, heritage protection, green space, the opaqueness of government decisions and its lack of consultative mechanisms. © 2011 by The Hong Kong University Press, HKU. All rights reserved.

Management Transition in South Korea: A Case Study - Chan, Wai Ip; Trimarchi, Michael; Negreiros, Joao (Asian Journal of Business and Management Sciences, 2012)
South Korea management system has been influenced significantly by their traditional social and religious beliefs for hundreds of years. Yet, the 1997 Asian financial crisis has gradually confirmed this shifted, from the Confucius mentality to a close Westernized system. This paper aims to evaluate this management transition in South Korea. The theoretical model of the convergent-divergent, as proposed by Chatterjee and Nankervis [2006], is applied to identify a number of critical factors. The aforementioned factors altogether have influenced the management system in four main vectors: (A) From seniority to meritocracy performance management; (B) From consultative to individualistic decision-making style; (C) From ignoring to embracing corporate governance; (D) From avoiding to improving environmental sustainability.

Murky shooting: The use of auditory (non-speech) feedback on mobile audiogames - Cordeiro, J.; Baltazar, A.; Barbosa, A. (ACM International Conference Proceeding Series, 2012)

Social cues in the expression of sequential alternative reproductive tactics in young males of the peacock blenny, Salaria pavo - Fagundes, Teresa; Simões, Mariana G.; Gonçalves, David; Oliveira, Rui F. (Physiology & Behavior, 2012)

Negative affect among undergraduates: Why are higher levels reported by Asian students?: Negative affect in Asian undergraduates - Found, Andrew; Cheong, Hoi Ieng; Duarte, Carlos (Asia-Pacific Psychiatry, 2012)

Searching for causality in the wrong places - Morrison, Keith (International Journal of Social Research Methodology, 2012)

Interpopulational variation of the mating system in the peacock blenny Salaria pavo - Saraiva, João L.; Pignolo, Giulia; Gonçalves, David; Oliveira, Rui F. (acta ethologica, 2012)

Quality of Life in Macau, China - Rato, Ricardo; Davey, Gareth (Social Indicators Research, 2012)
We report the initial findings of an ongoing, long-term investigation into subjective quality of life in Macau, a Special Administrative Region of China. Data were collected via quarterly public surveys (2007 to 2009; n = 8,230), as part of the Macau Quality of Life Report. The main aims of the study were to: (a) ascertain the public’s satisfaction with life and with the regional situation in Macau; (b) confirm the utility of the International Wellbeing Index (IWI) as a measure of subjective life quality; and (c) contribute to ongoing discussion in the literature on quality of life in China. The data indicated moderate levels of personal (PWI = 64.4; range 63–66.7) and national (NWI = 59.7; 57.4–63.7) wellbeing across the study period, which implies that residents in Macau are generally satisfied with life. The lowest scores were reported in the first quarter of 2009, a period of great economic uncertainty in Macau and the world, but were positioned within the normative range. The IWI demonstrated good psychometric performance, consistent with previous studies in China and the West, which confirmed its utility. These findings are discussed in relation to the IWI’s theoretical underpinnings and the literature.
Keywords: China; International Wellbeing index; Macau; Quality of life

Subjective Wellbeing in China: A Review - Davey, Gareth; Rato, Ricardo (Journal of Happiness Studies, 2012)
We critically review studies of subjective wellbeing conducted in China by the International Wellbeing Group, and we evaluate the International Wellbeing Index (IWI), a new instrument they developed. Subjective wellbeing was positive and similar in studies across China, and conformed to the normative range. Its resilience (PWI = 61.2–67.1) mirrors survey findings conducted in Western countries, in agreement with Subjective Wellbeing Homeostasis. Reliability, validity and psychometric analyses support the utility of the IWI as a measure of subjective wellbeing. Our conclusions have implications for research and social development in China, discussed further in this review.
Keywords: China; Happiness; International wellbeing index; Quality of life; Subjective wellbeing

廣州會議（1667-1668）四十二條條文的意義 - Ip, Ka Kei (道風：基督教文化評論, 2012)
Canton Conference (1667-1668) is regarded as an important event in the history of Christianity in China. The Conference was held by missionaries from three religious orders, namely, the Jesuits, Dominicans and Franciscans. Together they tried to achieve something common to strive for the prosperity of the China mission. It is true that the background and atmosphere of the Conference was influenced and overwhelmed by the Rites controversy. However, another significant part that the conference covered, in a large portion, dealt with wide pastoral issues in the context of Chinese society. The forty two articles in this Conference demonstrate the open-mindedness and a fairly positive knowledge of an approach to Chinese custom. In addition, some recommendations remain open to further inquires, in the sense that they were still finding a better way to cope with the indigenous affairs. Analysis of the articles as a whole gives light to various aspects of missionary work at that time beyond the controversial article forty-first.
Keywords: Canton Conference; Christianity in China; Missionary Activity; 中國基督宗教史; 傳教士活動; 廣州會議

Message from general chairs - Berglund, A. (Proceedings - 2013 Learning and Teaching in Computing and Engineering, LaTiCE 2013, 2013)

Efficient isolation of polymorphic microsatellites from high-throughput sequence data based on number of repeats - Cardoso, Sara D.; Gonçalves, David; Robalo, Joana I.; Almada, Vitor C.; Canário, Adelino V.M.; Oliveira, Rui F. (Marine Genomics, 2013)

NIME education at the school of arts of the portuguese catholic university/CITAR - Martins, L.G.; Barbosa, A. (Proceedings - 2013 Learning and Teaching in Computing and Engineering, LaTiCE 2013, 2013)

Interviewing children in uncomfortable settings: 10 lessons for effective practice - Morrison, Keith (Educational Studies, 2013)

Lone parents' experiences as higher education students: learning to juggle - Morrison, Keith (Educational Research and Evaluation, 2013)

Online and paper evaluations of courses: a literature review and case study - Morrison, Keith (Educational Research and Evaluation, 2013)

Ecological modulation of reproductive behaviour in the peacock blenny: a mini-review - Saraiva, J. L.; Gonçalves, David; Oliveira, R. F. (Fish Physiology and Biochemistry, 2013)

Signos de los tiempos: desafío a la Nueva Evangelización. El Concilo Vaticano II. Uma Perspectiva teológia. Vicente Vide - José R. Villar (Eds.) San Pablo: Madrid, 2013: - Stilwell, Peter (2013)

加拿大網絡安全戰略及法律問題 - , - Yang, Vincent (中國法學- 2013年網絡資訊安全法特刊, 2013)

Potential Ecological Risk of Heavy Metal Distribution in Cemetery Soils - Amuno, S. A. (Water, Air, & Soil Pollution, 2013)
In this paper, preliminary investigation was conducted to evaluate the potential ecological risk of heavy metals contamination in cemetery soils. Necrosol samples were collected from within and around the vicinity of the largest mass grave in Rwanda and analyzed for heavy metal concentrations using total digestion–inductively coupled plasma mass spectrometry and instrumental neutron activation analysis. Based on the concentrations of As, Cu, Cr, Pb, and Zn, the overall contamination degree (Cdeg) and potential ecological risks status (RI) of the necrosols were determined. The preliminary results revealed that the associated cemetery soils are only contaminated to a low degree. On the other hand, assessment of the potential ecological risk index (RI) revealed that cumulative heavy metal content of the soil do not pose any significant ecological risks. These findings, therefore, suggest that, while cemetery soils may be toxic due to the accumulation of certain heavy metals, their overall ecological risks may be minimal and insignificant.
Keywords: Cemetery soils; Environmental management; Heavy metals; Mass graves

Financial Worldwide Crisis: The Anti-Counter Cycle of Australia - Pou, Boey Tang; Trimarchi, Michael; Negreiros, Joao (Journal of the Faculty of Economics and Administrative Sciences, Çankırı Karatekin University, 2013)
If Australia has been subject to major influences by the United States and European countries, why is its economy healthier than their counter partners? What are the economic foundations that underline this anti-counter cycle of financial worldwide crisis from Australia? What are some of the lessons that countries from Europe that have not fared during the current financial worldwide crisis should learn from Australia? The purpose of this paper is to review the present Australian management system. Four changes are identified including embracement of corporate governance, a shift to adopt more R&D activities, a shift to adopt environmental sustainability practices and emerging corporate social responsibility. On the conclusions settings, a recap and recommendation on how Portugal, a member of the PIGS (Portugal, Italy, Greece and Spain) Southern European Countries club forgot to embrace directives that have been applied in Australia, to avoid the actual financial and identity crisis.

The Internet in China’s state–society relations: Will Goliath prevail in the chiaroscuro? - Sautedé, Eric (China Information, 2013)
This article explores how state and society relations have been affected by the development of information technology in China over the past 20 years. It argues that despite all the transformative changes that such technology has helped bring about, ?benefits? have to be weighed in terms of both empowerment of society and strengthening of state capacity. Ultimately, the digital challenge has not translated into a weakening of the authoritarian state, and this can be explained by the very nature of the party-state in China and how it has managed to make use of communication tools that prove to be both constructive and divisive.

The etiology of mental disorders: public endorsement of traditional Chinese beliefs in Macau - Found, Andrew; Duarte, Carlos (The International Journal of Social Psychiatry, 2013)
BACKGROUND: Public beliefs concerning the causes of mental disorders are important in their effective treatment. The relative importance of public beliefs related to the etiology of mental disorders among Chinese populations and their relationship to other attitudes to mental disorders are poorly understood. AIMS: To investigate the endorsement of beliefs related to the etiology of mental disorders in Macau, in particular, traditional Chinese beliefs, and to explore their relationship to general attitudes towards mental disorders. METHODS: A survey of 361 members of the public measured attitudes towards 32 possible causes of mental disorders as well as contact with and social distance from individuals with a mental disorder. RESULTS: The results indicated that traditional Chinese beliefs were ranked with relatively low importance compared with psychosocial causes. Traditional beliefs related to two underlying factors and were significantly higher in participants with lower education levels. There was a significant negative correlation between endorsement of traditional beliefs and contact with individuals with a mental disorder and a significant positive correlation between endorsement of traditional beliefs and desired social distance from individuals with a mental disorder. CONCLUSION: Factors underlying traditional Chinese beliefs concerning the causes of mental disorders are associated with more negative attitudes towards individuals with a mental disorder, with such beliefs more strongly endorsed by those with relatively lower education levels.
Keywords: Adolescent; Adult; Aged; Attitude to Health; Chinese; Female; Health Knowledge, Attitudes, Practice; Humans; Macau; Male; Medicine, Chinese Traditional; Mental Disorders; Mental disorder; Middle Aged; Surveys and Questionnaires; Young Adult; etiology; lay theories

Gender, sibling position and parental expectations: A study of Chinese college students - Found, Andrew; Sam, David (Journal of Family Studies, 2013)
Differences in parental expectations related to cultural background, gender and sibling position were investigated among Chinese college students in Macau. Three-hundred and forty-four Chinese college students completed a questionnaire which included measures of parental expectations and psychological distress, as well as information about their gender, cultural background (Mainland China or Macau) and sibling position. Participants born in mainland China reported significantly higher perceived parental expectations (PPE) compared with students from Macau. Contrary to predictions, there was no evidence of a difference in PPE in relation to gender or being the first-born sibling. These findings are discussed in terms of changes in family values and parental attitudes within Chinese society over the past few decades.
Keywords: Chinese; gender; parenting; siblings; students

Etnografia, lugares da memória e o discurso dos poderes na aldeia dos índios potiguara - Simões, José Manuel (e-hum, 2013)
eoi/doi Deposit-Electronic Object Identifierhttp://eoi.citefactor.org/10.11248/ehum.v6i2.1385RESUMO: A aldeia dos índios Potiguara não é somente um aglomerado de casas e pessoas. Trata-se de um espaço social muito mais complexo, somando ao habitat modelos de parentesco, cruzando práticas culturais e economicas, juntando aos humanos bichos e plantas, rotinas de trabalhos e “libertações” de lazeres. A aldeia Potiguara embora se apresente como singular, ela comunicava e continua a comunicar hoje com redes mais amplas de aldeias rurais e indígenas, gerando transformações culturais e sociais profundas. Embora as alterações marquem as mudanças nos habitos da aldeia Potiguara acredita-se que as práticas culturais que se estendem das festas ao turismo das suas aldeias são tão tradicionais como singulares.PALAVRAS-CHAVES: Aldeia indígena – Espaço social – Práticas culturais – TransformaçõesABSTRACT:The village of Potiguara Indians is not only a cluster of houses and people. This is a social space much more complex, adding to habitat kinship models, crossing cultural and economic practices, joining human animals and plants, work routines and "releases" of leisure.The Potiguara village despite presenting as singular, she communicated and continues to communicate today with wider networks of rural and indigenous villages, generating deep cultural and social transformations. Although the changes mark the changes in the habits of the village Potiguara is believed that cultural practices that extend parties to tourism from their villages are so traditional and unique.KEYWORDS: Indian Village - social area - Cultural practices - TransformationsRecebido: 31/08/2014    Aceito: 01/10/2014
Keywords: Aldeia indígena; Espaço social; Práticas culturais; Transformações

The creative industries as an integrated factor in a sustainable model for Macao's economic development - Azevedo, Margarida; Barbosa, Álvaro (Creative Industries Journal, 2014)
This article presents an insight into one of the regions with the fastest-growing economy, heavily based on an entertainment, gaming and tourism industry, and that is urgently looking for a sustainable model that articulates with complementary sectors within the cultural and creative industries – Macao. Macao is facing a major economic and social challenge; it has grown as a vulnerable economy relying almost exclusively on gaming revenues. Alternative activities to diversify the economy are urgently required to answer the competition risks haunting this industry. The cultural and creative industries could be a complementary activity – a vehicle for economic diversification. However, current public and private stakeholders for the cultural and creative sector might have been neglecting the unique cultural and heritage ecosystem of the territory, focusing on isolate opportunities and overlooking an inclusive and robust strategy. A sustainable model that attends to the local conditions and its people is required for alternative activities to become a meaningful sector for the social and economic development of Macao.

Privacy in sound-based social networks - Cordeiro, J.; Barbosa, A. (Communications in Computer and Information Science, 2014)

An eco-structuralism approach in soundscape (data) composition - Gomes, J.A.; Barbosa, A.; Penha, R. (ACM International Conference Proceeding Series, 2014)

Alternative pathway history in a fish with plastic reproductive tactic - Gonçalves, David (Functional Ecology, 2014)

Oestradiol and prostaglandin F2α regulate sexual display in female of a sex-role reversed fish - Gonçalves, David (2014)

Challenges of collborataive blend learning in undergraduate students - Monteiro, Elisa; Morrison, Keith (Education Research and Evaluation, 2014)

African Female Nascent Entrepreneurship In The Macao S.A.R. - Morais, Isabel (Urban Anthropology and Studies of Cultural Systems and World Economic Development, 2014)
African women from different countries and social classes, from those seeking refugee status to diplomats and peasants' daughters, have been arriving in increasing numbers on Chinese shores since the 1980s. The amazing stories of some of these "invisible" but dynamic women have been ignored, yet they reveal great diversity and deserve scholarly attention, as they provide rich material for studies on the African diaspora in China. This article focuses on African migration to Macao, a former Portuguese colony and primary migration destination in the Pearl Delta River Region, which currently hosts the densest African population in China. It explores both the more recent and the relatively longer-term migration of African women and university students to Macao, and examines the intersection of these communities resulting from the overlap between the ongoing global movements of African diasporas and new African migratory trends to China. The article draws on the life stories as well as the educational and entrepreneurial experiences of African women in Macao, and investigates the relevance of ethnic networks of trust and reciprocity for their communities' survival. This article places specific emphais on the experiences of African women, recognizing their achievements in the face of multiple intersections of racism and sexism on the part of both state and society, and reveals how the women employ a resistance strategy by reinforcing ethnic migrant networks.

The academic and intellectual life of Macau - Morrison, Keith (Review of Culture (Revista de Cultura), 2014)

Implementation of Enterprise Resource Planning for the Supply Chain Management of the Food and Beverage Department at Macao Entertainment Corp - Vai, Fong Tou; Lee, Leanda; Negreiros, Joao (Information Resources Management Journal (IRMJ), 2014)
One of the six gaming concession holders in Macao, Macao Entertainment Corp (MEC)1, undertook to centralize three casino/entertainment properties through utilization of a centralized Enterprise Resource Planning (ERP) in April 2010. The Supply Chain (SC) department was the first to apply the ERP in...

教育輿情中的教育政策目標, 議題關注與價值表達: 以兩份十大教育新聞榜單的話語分析為例 - 陳霜葉; 孟瀏今 (北京大學教育評論, 2014)

O Sonho e o Desejo Libertários da "Lusa Macaense" Lee Li-Lyang: O Heterónimo Feminino na poética de Virgílio De Lemos", - Morais, Isabel Maria da Costa (Entre a Desmistificação e a utopia: Indagação sobre as Lusofonias , Macau: University of Saint Joseph.69-95, 2014)
Virgílio de Lemos (1929-2013), poeta de vanguarda, é um dos precursores da modernidade e experimentalismo como criador do “barroco estético” que ele próprio designou como a linguagem poética marcante nas letras moçambicanas no das décadas de 50 e 60

Personality and learning styles surrounded by W3 software: The Macao Portuguese school case - Negreiros, João; Baptista, Zelia; Lee, Leanda (Education and Information Technologies, 2014)
One of the purposes of this study is to evaluate how the choice of teaching method can be assisted by knowledge of a student’s personality type and learning style. The present research is undertaken in the context of Web 2.0 tools use within the Portuguese literature subject at Escola Portuguesa de Macao (EPM). The Felder-Soloman index of learning style (ILS) and the Myers-Briggs Type Indicator (MBTI) based upon Jung’s theory of psychological nature were used as measures of learning style and personality type with 8th grade EPM students. Descriptive and chi-squared correlation statistical results of the associations between personality and learners types are presented. These results are discussed positing that the knowledge of student’s personality traits and learning styles together may have a notable implication for teaching methods.
Keywords: Escola Portuguesa de Macao (EPM); Felder and Soloman; ILS; MBTI; Myers and Briggs; Web 2.0

Researching international student migration in Asia: research design and project management issues - Ge, Yun; Ho, Kong Chong (Journal of Population Research, 2014)
In the context of Asia, the changing dynamics of higher education has increased the visibility and significance of the group of intraregional education migrants. There are several methodological issues which need to be addressed in conducting research for this group of migrants. First, how does the particular type of migrant group and Asian context influence the research design? Second, in order to capture the scale and diversity of this migrant group, how should research be conducted across multiple sites? Third, how does a mixed method design allow researchers to learn more about the behaviour, practice and orientations of education migrants? Our paper aims to make contributions to the discussions on the methods of education migration research in Asia through answering these questions. We use research experiences and preliminary data from a multinational project to illustrate the issues involved in the selection of methods, research design and project management.
Keywords: Asia; Higher education; International student migrants; Mixed methods; Multi-site design; Multicultural research

The other side of creative industries in Hong Kong and Macau - Mendes, Carla de Utra; Simoes, José Manuel (International Journal of Cultural and Creative Industries, 2014)

Capture and transformation of urban soundscape data for artistic creation - Gomes, Jose Alberto; Pinho, Nuno Peixoto De; Lopes, Filipe; Costa, Gustavo; Dias, Rui; Tudela, Diogo; Barbosa, Álvaro (Journal of Science and Technology of the Arts, 2014)

Lugares da Memória, Representações e Poderes - Simões, José Manuel da Silva (Rizoma, 2014)
No seguimento de uma série de contactos estreitos com uma comunidade social situada nos municípios de Baía da Traição, Rio Tinto, Marcação e Mataraca, a 85 quilómetros de distância de João Pessoa, capital do Estado da Paraíba, decidi, desde 2006, levar a efeito um intenso trabalho de campo nestas aldeias indígenas com o objectivo de concretizar um projeto de investigação que englobasse em obrigatória interdisciplinaridade os campos tantas vezes excessivamente singulares da História, da Sociologia, da Política, da Antropologia Cultural e das Teorias da Comunicação, acompanhando e refletindo sobre características e organização social, rituais, manifestações de carácter religioso, evolução histórica, usos e costumes de uma tribo que se abriu quase rendida ao exterior, mas porfiando em manter, todavia, traços e, sobretudo, um discurso narrativo de representações culturais ancestrais. Esta propositada interdisciplinaridade persegue um objectivo epistemológico bem preciso: transformar a investigação empírica em contribuição para uma nova teoria da história da comunicação – a comunicação antropo-histórica entre comunidades ditas tradicionais e o “outro” – a área por mim privilegiada em investigações anteriores, nomeadamente ao nível da licenciatura e do mestrado. Os Potiguara, cuja sociedade ainda não é alfabetizada e, na sua maioria, baseiam a sua cultura na tradição oral, transmitindo os seus lugares da memória sobretudo através do poder do português do Brasil, mesmo quando adornado por escassas palavras tupi, é graças à mensagem e à representação que algumas das suas manifestações culturais reinventam continuadamente a sua identidade Potiguara. É, assim, a mensagem e a representação que inventam o real social e reinventam dinamicamente a sua identidade cultural.
Keywords: Lugares de Memória

Visions for Education among Chinese and Non-Chinese Student Teachers: Exploring Cultural Differences - Correia, Ana (The International Journal of Diversity in Education, 2015)
Using Habermas’s theory of communicative action, this study explores the educational visions held by a multi-cultural class of students enrolled in a teacher preparation programme set in a culturally and linguistic diverse urban environment with a recent history of colonialism. The purpose of the study was to analyse the educational and teaching visions put forward by student teachers in an essay during the course “Principles of Education,” which took place in the 2013–2014 academic year and to determine whether the variation in respondents’ vision statements was related to the students’ cultural backgrounds. The students’ awareness of the instructor’s grading role may have influenced the content of their vision statements, and thus Habermas’s theory of communicative action was selected as it allows one to focus on both the content and the process of communicative interaction. The current qualitative research presents data from twenty Macau-Chinese and twenty non-Chinese overseas students. Their visions for education and teaching were examined along the lines of culture. The findings revealed that the idealised representations of what education and teaching is, does and symbolise, varies along culture lines. Since urban educational environments are growing culturally diverse, it is recommended that additional attention be given to cultural awareness in teacher education programmes.

A receção da figura de Melquisedeque na literatura cristã latina - Eleutério, JM (Didaskalia, 2015)
A interpretação da Escritura e das suas diferentes personagens enriquece a Tradição cristã, mas este processo de receção é muitas vezes marcado por debates e polémica …

Birth date predicts alternative life‐history pathways in a fish with sequential reproductive tactics - Fagundes, Teresa; Simões, Mariana G.; Saraiva, João L.; Ros, Albert F. H.; Gonçalves, David; Oliveira, Rui F. (Functional Ecology, 2015)

What students are saying on Facebook about their schools? - Kio, Su Iong (Webology, 2015)

The Colonization of Lifeworlds of Education by Work: Restoration and Recoupling of Lifeworld and System in the Inner Self - Morrison, Keith (Horizons of Education, 2015)
The argument is raised that, in an age of the networked, connected society in an information-rich environment with communication possibilities as never before experienced or made possible, the displacement of educational virtues of morality, ethics and the development of all-round human beings, by those of money, labour, power and work are speeding apace, and the disconnect between system and lifeworld is increasing. Drawing initially on the work of Habermas, in which the colonization of the lifeworld occurs by system imperatives of rationalization, labour, money and power, the paper argues that such moves are manifested starkly in discourses of the relation between education and work, and five areas are introduced in which the links operate. The marketization and commodification of education, together with its incorporation into the service of capital and labour, are attested through a short worked example of one small territory within the larger context of China. Then, taking a lead from Sertillanges and Habermas’s later work, the paper argues for: (a) a reaffirmation of the importance of moral, ethical and spiritual dimensions of education; (b) the breaking of a narrowly instrumental, capital-acquisitive view of education as serving the jobs market and social control and towards a liberating view of education as communicative action and the development of being rather than simply behaving; (c) the importance of transcendence and immanence; and, thereby, (d) moves towards the re-integration of system and lifeworld in participating subjects.

提升澳門文化遺產保護與管理的水平 - Pinheiro, Francisco Vizeu (澳門研究, 2015)

Catholic Orders as Efficient Institutions - Rothlin, Stephan; Frey, B. S (Lumen: A Journal of Catholic Studies, 2015)

Festas e lugares da memória dos índios Potiguara – a invenção das tradições locais - Simoes, José Manuel (Tokyo University of Foreign Studies, 2015)

Connectivism and the Use of Technology/Media in Collaborative Teaching and Learning - Thota, Neena (New Directions for Teaching and Learning, 2015)
This chapter explores the ways in which a relational understanding of the education process and the use of collaborative technologies in the connectivist tradition might inform and transform university teaching.

The Macau Forum and China's Soft Power in the Making: Training the Elite of the Development Portuguese Speaking Countries" - Tran, Émilie; Matias, José Carlos (China - An International Journal, 2015)

Coping with Merging and Advanced Market Risks - Xia, Harry (International Journal of Economics and Social Science, 2015)

教育治理背景下的本科訊息公開:基於政策証據視覺的分析教育發展研究 (CSSCI) - 孟瀏今 (2015)

Neurogenomic mechanisms of social plasticity - Cardoso, Sara D.; Teles, Magda C.; Oliveira, Rui F. (Journal of Experimental Biology, 2015)
Skip to Next Section Group-living animals must adjust the expression of their social behaviour to changes in their social environment and to transitions between life-history stages, and this social plasticity can be seen as an adaptive trait that can be under positive selection when changes in the environment outpace the rate of genetic evolutionary change. Here, we propose a conceptual framework for understanding the neuromolecular mechanisms of social plasticity. According to this framework, social plasticity is achieved by rewiring or by biochemically switching nodes of a neural network underlying social behaviour in response to perceived social information. Therefore, at the molecular level, it depends on the social regulation of gene expression, so that different genomic and epigenetic states of this brain network correspond to different behavioural states, and the switches between states are orchestrated by signalling pathways that interface the social environment and the genotype. Different types of social plasticity can be recognized based on the observed patterns of inter- versus intra-individual occurrence, time scale and reversibility. It is proposed that these different types of social plasticity rely on different proximate mechanisms at the physiological, neural and genomic level.

The seminars of the Macao forum: An illustration of China’s soft-power diplomacy towards the Portuguese-speaking countries - Tran, Emilie; Dos Santos, Jose Carlos Matias (China: An International Journal, 2015)
This article reviews the role that the Macao Special Administrative Region (SAR) plays in China’s cultural and public diplomacy through training programmes organised by the Macao Forum and tailored for the elite of the world’s Portuguese-speaking countries (PSCs). It begins with a review of China’s approach to key instruments of its soft-power offensive and strategy towards the developing world, followed by an overview of Beijing’s linkages with each PSC. Formulated as an expression of China’s cultural diplomacy towards the PSCs, the seminars of the Macao Forum serve as a kind of cooperation in which the provider party—rather than delivering tangible goods and services such as food, money, loans or infrastructure—actually offers grey matter in the form of ideas for initiatives in public policies and reforms, in order to foster further economic development and administrative rationalisation. Adding to an intense debate and substantial literature that discuss quantitatively and qualitatively China’s role in and aid provision to Africa, the authors argue that China, through the Macao Forum’s training programmes, courts the developing PSCs by building the capacity of their human capital, targeting in particular those in the public and private sectors who are in a position to implement their ideas.

Conflict between affective versus continuance commitment among casino dealers - Kuok, A. C. H; Taormina, Robert J. (Evidence-based HRM: a Global Forum for Empirical Scholarship, 2015)
Purpose – The purpose of this paper is to empirically investigate the extent of the reported low affective commitment compared to continuance commitment of Chinese casino dealers, to discern if there is a significant difference between the two types of commitment, and to identify factors that could explain the difference between them. Design/methodology/approach – Questionnaire data were obtained from 247 Chinese casino dealers working for the three major casino groups in Macau. Correlations and regressions were used to analyze the data. Findings – Dealers’ affective commitment was significantly lower than their continuance commitment, suggesting dealers do not like their jobs but do not leave them, which indicates they have cognitive dissonance about their jobs. Organizational socialization, organizational support, and supervisor integrity were positively correlated with affective commitment; while value of money, pay satisfaction, and neuroticism, were positively correlated with continuance commitment. Organizational support was the strongest predictor of affective commitment, while the value they place on money was the strongest predictor of continuance commitment. Practical implications – Casino managers could improve dealers’ affective commitment by facilitating their organizational socialization, especially training and rewards for their work, providing greater organizational support, and fair and supportive treatment from their supervisors. Originality/value – This is the first study to provide evidence of the difference between affective and continuance commitment in Chinese society, and identifies factors that influence each type of commitment, and may help resolve the employees’ dilemma about their jobs, which is an important concern for Chinese managers.

Pathophysiological, cardiovascular and neuroendocrine changes in hypertensive patients during the hemodialysis session - Gutiérrez-Adrianzén, O. A.; Moraes, M. E. A.; Almeida, A. P.; Lima, J. W. O.; Marinho, M. F.; Marques, A. L.; Madeiro, J. P. V.; Nepomuceno, L.; da Silva Jr, J. M. S.; Silva Jr, G. B.; Daher, E. F.; Rodrigues Sobrinho, C. R. M. (Journal of Human Hypertension, 2015)
The pathophysiological mechanisms of arterial hypertension during hemodialysis (HD) in patients with end-stage renal disease (ESRD) are still poorly understood. The aim of this study is to investigate physiological, cardiovascular and neuroendocrine changes in patients with ESRD and its correlation with changes in blood pressure (BP) during the HD session. The present study included 21 patients with ESRD undergoing chronic HD treatment. Group A (study) consisted of patients who had BP increase and group B (control) consisted of those who had BP reduction during HD session. Echocardiograms were performed during the HD session to evaluate cardiac output (CO) and systemic vascular resistance (SVR). Before and after the HD session, blood samples were collected to measure brain natriuretic peptide (BNP), catecholamines, endothelin-1 (ET-1), nitric oxide (NO), electrolytes, hematocrit, albumin and nitrogen substances. The mean age of the studied patients was 43±4.9 years, and 54.6% were males. SVR significantly increased in group A (P<0.001). There were no differences in the values of BNP, NO, adrenalin, dopamin and noradrenalin, before and after dialysis, between the two groups. The mean value of ET-1, post HD, was 25.9 pg ml−1 in group A and 13.3 pg ml−1 in group B (P=<0.001). Patients with ESRD showed different hemodynamic patterns during the HD session, with significant BP increase in group A, caused by an increase in SVR possibly due to endothelial dysfunction, evidenced by an increase in serum ET-1 levels.
Keywords: End-stage renal disease; Haemodialysis; Hypertension

A review of the Colloquium «Narrative, Media and Cognition» — a cartography of the borders of narrative - Castro, Maria Guilhermina; Caires, Carlos Sena; Ribas, Daniel; Palinhos, Jorge (Journal of Science and Technology of the Arts, 2015)
We present an overview and discussion of the Colloquium «Narrative, Media and Cognition», which took place at Porto's Centre of Catholic University of Portugal in July of 2015, under the organization of the Research Centre for Science and Technology of the Arts (CITAR). Several scholars of different areas presented research about the uses and advances in narrative study and practice in a broad range of areas, giving some important insights about the latest developments in Narrative Studies, Ontology of Narrative and the uses of Narrative in Art, Cinema, Performance, Journalism, Marketing and Literature, among other fields. After briefly describing the main points of each presentation in the Colloquium we try to draw some conclusions and possibilities raised by the Colloquium and take a glimpse of future paths that the use of Narrative can end up taking.

Da aptidão à aspiração: um caminho por percorrer - Correia, Ana (CECS - Publicações / eBooks, 2015)

A Heart Rate Variability-based Smart Approach to Analyze Frailty in Older Adults - Paulo do Vale Madeiro, João; César Cortez, Arnaldo Aires Peixoto Júnior, Paulo; Alexandre Lôbo Marques, João; Alisson Pessoa Guimarães, Antônio; Hebert da Silva Felix, John (The Smart Computing Review, 2015)
This paper presents an algorithm that applies metrics derived from automatic QRS detection and segmentation in electrocardiogram signals for analyzing Heart Rate Variability to study the evolution of metrics in the frequency domain of a clinical procedure. The analysis was performed on three sets of elderly people, who are categorized according to frailty phenotype. The first set was comprised of frail elderly, the second pre-frail elderly, and the third robust elderly. Investigators from many disciplines have been encouraged to contribute to the understanding of molecular and physiological changes in multiple systems that may increase the vulnerability of frail elderly. In this work, the frailty phenotype can be characterized by unintentional weight loss, as self-reported, fatigue assessed by self-report, grip strength (measured directly), physical activity level assessed by self-report and gait speed (measured). The results obtained demonstrate the existence of significant differences between Heart Rate Variability metrics for the three groups, especially considering a higher preponderance for sympathetic nervous system for the group of robust patients in response to postural maneuver.

Vocal differentiation parallels development of auditory saccular sensitivity in a highly soniferous fish - Vasconcelos, Raquel O.; Alderks, Peter W.; Ramos, Andreia; Fonseca, Paulo J.; Amorim, M. Clara P.; Sisneros, Joseph A. (Journal of Experimental Biology, 2015)
Vocal differentiation is widely documented in birds and mammals but has been poorly investigated in other vertebrates, including fish, which represent the oldest extant vertebrate group. Neural circuitry controlling vocal behaviour is thought to have evolved from conserved brain areas that originated in fish, making this taxon key to understanding the evolution and development of the vertebrate vocal-auditory systems. This study examines ontogenetic changes in the vocal repertoire and whether vocal differentiation parallels auditory development in the Lusitanian toadfish Halobatrachus didactylus (Batrachoididae). This species exhibits a complex acoustic repertoire and is vocally active during early development. Vocalisations were recorded during social interactions for four size groups (fry: <2 cm; small juveniles: 2–4 cm; large juveniles: 5–7 cm; adults >25 cm, standard length). Auditory sensitivity of juveniles and adults was determined based on evoked potentials recorded from the inner ear saccule in response to pure tones of 75–945 Hz. We show an ontogenetic increment in the vocal repertoire from simple broadband-pulsed ‘grunts’ that later differentiate into four distinct vocalisations, including low-frequency amplitude-modulated ‘boatwhistles’. Whereas fry emitted mostly single grunts, large juveniles exhibited vocalisations similar to the adult vocal repertoire. Saccular sensitivity revealed a three-fold enhancement at most frequencies tested from small to large juveniles; however, large juveniles were similar in sensitivity to adults. We provide the first clear evidence of ontogenetic vocal differentiation in fish, as previously described for higher vertebrates. Our results suggest a parallel development between the vocal motor pathway and the peripheral auditory system for acoustic social communication in fish.

John Alexander Holm (1943-2015) - Baxter, Alan N. (Journal of Pidgin and Creole Languages, 2016)

Wrestling with God - Flores, Randolf (Orientis Aura: Macau Perspectives In Religious Studies, 2016)
This study will discuss the following Old Testament texts: Gen 32:23-32; Jon 1:17; Tob 6:1-9; and Exod 4:24-26 and will argue that these are about the initiation of a person to do a divine mission. Some parallels from Asia—Epic Gilgamesh, texts from Tibetan Buddhism, Hinduism, and the Philippine epic, Biag ni Lam-ang will also be taken into consideration to shed light on them. It will also present their interpretation as typoi of the sacraments of initiations found in early Christian literature and art.

Education in Religious Freedom - Gassner, Franz (Orientis Aura: Macau Perspectives in Religious Studies, 2016)
The author emphasizes the crucial relevance of religious liberty and freedom of expression for a harmonious and peaceful development of modern societies. He follows the prophetic Declaration of Religious Freedom of Second Vatican Council (1965) with its constitutional limitation of governmental powers in matters of religion. The high value of religious freedom is judged as bulwark of all human rights and true capstone of sound human and societal developments, which have to be guarded against any form of infringements. In this regard, a reasonable education in religious freedom and liberty is indispensable for young people of the twenty-first century. Education in religious freedom in the context of moral and religious formation is based on the dignity of every human person and promotes a deeper mutual and cultural understanding by respecting the conscience of every human person. It thus carries the potential to diminish conflicts and clashes in a sustainable way. Educational reforms in countries have to include the high value of religious liberty and freedom as a main element and condition for human dignity and a peaceful global development.

Education in Religious Freedom: Path to Peace and Stability - Gassner, Franz (Orientis Aura, 2016)

Vatican II - Gomez, Fausto (Orientis Aura: Macau Perspectives In Religious Studies, 2016)
From a reason-faith perspective, I reflect on “Vatican II: Gaudium et Spes Fifty Years Later.” In the introduction, I speak briefly on the Second Vatican Council, and on its Pastoral Constitution Gaudium et Spes (“Joy and Hope”) and its ethical and social teachings.

Extending social networking into the secondary education sector - Kio, Su Iong (British Journal of Educational Technology, 2016)
Secondary schools do not have the same technical resources and capabilities as universities. They usually need to rely on ready-to-use tools to fulfill their information and communication technology (ICT) structure. Social networking site (SNS) has emerged as a practical solution to this need. However, few have collected empirical data on the application of SNS in a secondary school setting. This paper probes into the current condition of SNS usage among secondary school students using a sample of 851 students in Macau, a Special Administrative Region (SAR) of China. Data in terms of access, profile and activities are collected. The activities on SNSs are analyzed by regression techniques to produce a prediction model relating perceived academic benefit and SNS activities. The model yields a strong positive relationship between that benefit and activities such as raising questions and engaging in study-related discussions. The model also yields a weak dependency on activities such as searching for information and entertainment. The paper also evaluates the actual academic utilization of a Facebook Group for one class of secondary school students for a period of one year. At the end of the year, various opinion parameters are measured, and improvements are observed in most parameters.

Baptism as Christian Initiation in the New Testament - MONERA, A. (Orientis Aura, 2016)

The Criminalization of Verbal Sexual Harassment in Amending Macao's Criminal Code - Yang, Vincent (Socioeconomic Development Research, 2016)

Relationship between Traditional Chinese Beliefs about Aetiology of Mental Disorders and Help Seeking: A Survey of the Elderly in Macao - Found, A. (East Asian Archives of Psychiatry: Official Journal of the Hong Kong College of Psychiatrists = Dong Ya Jing Shen Ke Xue Zhi: Xianggang Jing Shen Ke Yi Xue Yuan Qi Kan, 2016)
OBJECTIVE: A wide range of factors can influence help-seeking attitudes when individuals experience a mental disorder. The current study investigated the relationship between traditional Chinese beliefs related to the aetiology of mental disorders and help-seeking attitudes among elderly participants in Macao. METHODS: In order to ensure the suitability of participants for inclusion in this study, the participants were required to complete an initial screening test using the Short Portable Mental Status Questionnaire (SPMSQ). Participants who successfully passed the test (n = 183) completed a questionnaire that included the Inventory of Attitudes Toward Seeking Mental Health Services (IASMHS), a set of 9 items related to traditional Chinese beliefs about aetiology of mental disorders and demographic items. RESULTS: The IASMHS scores were higher for female participants and for participants who had completed high school compared with those who had never attended school or who had only completed primary education. Endorsement of traditional Chinese beliefs about the aetiology of mental disorders was higher for male participants. There was a negative correlation between traditional Chinese aetiology beliefs related to mental disorders and help-seeking attitudes. CONCLUSION: Traditional Chinese beliefs related to the aetiology of mental disorders are a negative factor that inhibits help seeking. Implications for efforts to increase the utilisation of mental health services by the elderly are discussed.
Keywords: Aged; Asian People; Asian continental ancestry group; Cultural Characteristics; Female; Health Knowledge, Attitudes, Practice; Help-seeking behavior; Humans; Macau; Male; Mental Disorders; Mental disorders / etiology; Patient Acceptance of Health Care

Learning Computer Science: Dimensions of Variation Within What Chinese Students Learn - Thota, Neena; Berglund, Anders (ACM Transactions on Computing Education, 2016)
We know from research that there is an intimate relationship between student learning and the context of learning. What is not known or understood well enough is the relationship of the students’ background and previous studies to the understanding and learning of the subject area—here, computer science (CS). To show the contextual influences on learning CS, we present empirical data from a qualitative investigation of the experiences of Chinese students studying for a master degree at Sweden's Uppsala University. Data were collected of the students’ understanding and learning of CS, their experience of the teaching and their own studies, and of their personal development in Sweden. Using an analysis framework grounded in phenomenography, we analytically separated the what and how aspects of learning. In this article, we describe the what, or the content of the students’ learning, and identify dimensions of variation in the experiences of students. These dimensions relate to the foci of the CS programs, the learning outcomes, and the impact of the studies. The findings from the analyses indicate pedagogical and pragmatic implications for teaching and learning CS in higher education institutions. The study extends the traditional use of phenomenography through the discussion of the dimensions of variation in the experiences and the values within the dimensions. It opens the way for understanding the relational nature of learning in computing education.
Keywords: Computer science education; context; phenomenography; qualitative research; variation theory

Spatial modulation of the hydrological risk at Praia, Cape Verde - Silva, José Lino; Neves, Ana Cristina; Negreiros, João Garrott Marques (IOP Conference Series: Earth and Environmental Science, 2016)
Hydrology modeling became a relevant topic for the Cidade da Praia, Cabo Verde, Africa, due to negative impact risk to local population and its assets. The modeling via Geographical Information Systems (GIS) can help the decision-making process of space occupation and characterization for this type of risk. Under the municipalities of Praia, the phenomenon of flash flood is common, causing soil erosion and landslide. This constitutes a risk for the local habitat, particularly in districts with a lack of strong human infrastructures. To simulate, analyze and generate risk maps using GIS to help this county governance authorities for decision-making, thus, becomes the main aim of this article.

Mesozoic Granitic Magmatism in Macao, Southeast China - Quelhas, P. M.; Mata, J.; Lou, U. T.; Ribeiro, M. L.; Dias, Ágata (AGU Fall Meeting Abstracts, 2016)
Macao ( 30 Km2) is a territory characterized by small granitic intrusions, located along the coastal region of Southeast China (Cathaysia Block). Granitoids occur as different facies, including microgranite dykes, with distinct textural, mineralogical and geochemical features, for which a middle-upper Jurassic age ( 164 Ma) has been proposed. New data suggest that these granitoids are mostly high-K calc-alkaline metaluminous (A/CNK = 0.8 - 1.1) biotite granites, consistent with total absence of primary muscovite. They show variable amounts of SiO2 (67-77%), reflecting different degrees of magmatic evolution. There is also variability in terms of trace elements, particularly Rare Earth Elements (REEs), evidenced by decreasing (La/Sm)N, (Gd/Lu)N, (Ce/Yb)N and (Eu/Eu*)N towards the more evolved samples, which can be partly attributed to fractional crystallization processes. Most of the granitoids are characterized by (La/Yb)N = 3 - 10.8, showing negative Ba, Nb, Sr, Zr, P, Ti and Eu anomalies. On the other hand, microgranite dykes, along with a few more evolved granites, show an opposite tendency, being usually enriched in HREEs relatively to LREEs with (La/Yb)N = 0.4 - 1.1. Our data suggests intermediate genetic affinities between I-type and A-type granites. Although these granitoids are mostly metaluminous (characteristic of I-types), Ga/Al ratios, usually used to identify A-types, are close to the accepted boundary between A-type and other granite types. The affinities with A-type granites are more marked for the more evolved facies, which depict higher values of FeOt/MgO (14 - 60) and K2O/MgO (60 - 250). Their trace element characteristics are also transitional between WPG (Within-plate granites) and Syn-COLG (Collision Granites). We interpret those transitional characteristics (A/I and WPG/Syn-COLG) of Macao granitoids as reflecting an origin by melting of infracrustal sources over a period of high heat transfer from mantle to crust during an extensional tectonic setting probably contemporaneous with the subduction of the paleo-Pacific plate beneath the Eurasia, whose paleo-suture is thought to be located in the east flank of the Central Range, Taiwan.
Keywords: 8499 General or miscellaneous; VOLCANOLOGY

Espaço, história e memória: os potiguara na paraíba - Simoes, José Manuel (Sæculum – Revista de História, 2016)
últimos assumidos remanescentes provavelmente de um território cultural antes bem mais vasto vivem atualmente nos municípios de Baía da Traição, Marcação e Rio Tinto, no litoral setentrional da Paraíba - nem sobre s seus espaços, culturas e gentes. É preciso dobrar a primeira metade do século XX para se encontrar nos títulos gerais de histórias da Paraíba alguma atenção pelos Potiguara e a sua movimentação histórica no processo longo e contraditório de formação da capitania e da instalação portuguesa na região, enfrentando primeiro a concorrência comercial e militar francesa, depois no século XVII a ocupação holandesa e sempre, até quase meados de seiscentos, a oposição muitas vezes feroz e brutal de vários grupos e milícias potiguaras. A arqueologia confirma um processo recente de formação histórica dos espaços atualmente reivindicados como originais e tradicionais pelos Potiguara. Os estudos linguísticos disponíveis sobre os Potiguara também não destacam a memória rigorosa de um espaço cultural arcano e pré-colonial. Os espaços Potiguara de hoje com este sistema de organização agrícola quase binário são tudo menos naturais. Trata-se, antes, de um espaço em recorrentes transformações históricas, demográficas, económicas e sociais que desafia qualquer ideia de um espaço ‘natural’, ‘original’ ou ‘essencial’ dos Potiguara. Seja como for, estas polarizações estruturais são historicamente aquelas que presidiram à exata produção dos espaços que atualmente os Potiguara apresentam como seus, originais, antigos e tradicionais seguindo, afinal, um modelo colonial de ocupação de espaços e especialização das gentes do Brasil.
Keywords: História colonial

Early Notices Regarding Creole Portuguese in Former Portuguese Timor - Baxter, Alan N.; Cardoso, Hugo C. (Journal of Language Contact, 2017)

Temporal variation in brain transcriptome is associated with the expression of female mimicry as a sequen-tial male alternative reproductive tactic in fish. - Cardoso, S.D., Gonçalves, D., Goesmann, A., Canário, A.V.M., & Oliveira, R.F. (Molecular Ecology, 2017)

"The will and the way of inclusive education in Macao", - Correia, Ana; Teixeira, Vitor (Asian Education and Development Studies, 2017)

“Wisdom in Aristotle and Aquinas,” Existenz - Eh, E. (International Journal in Philosophy, Religion, Politics and the Arts, 2017)

Chinese Religious Syncretism in Macau | Orientis Aura: Macau Perspectives in Religious Studies - Eh, Edmond (2017)
In this paper, I address the phenomenon of syncretism with respect to Chinese religions. An analysis of the syncretism that takes place between the three major Chinese religious traditions is first done in its personal and social dimensions. The social structure of Chinese religion is then used as a framework to understand how Buddhism and Daoism were made compatible with Confucianism. All this will serve as a background for the case study of Macau, where Chinese religious syncretism is very much alive. Three popular religious festivals are celebrated annually and simultaneously on the eighth day of the fourth lunar month, namely, zuilongjie (醉龍節) Feast of the Drunken Dragon, tangongdan (譚公誕) Tam Kung Festival and fodanjie (佛誕節) Feast of the Buddha.

Wisdom in Aristotle and Aquinas: From Metaphysics to Mysticism - Eh, Edmond (Existenz: An International Journal in Philosophy, Religion, Politics, and the Arts, 2017)
This essay contains an attempt to trace the evolution of the concept of wisdom as found in the thought of Aristotle and Aquinas in terms of how the philosophical concept of wisdom as an intellectual virtue is understood and used to express the theological concept of wisdom as a gift of the Holy Spirit. The main aim is to understand how Aquinas derived the concept of wisdom from Aristotle's metaphysics and developed it in his mysticism. This research is based on a close study of Book Six of Aristotle's Nichomachean Ethics, the corresponding sections of Aquinas' Sententia libri Ethicorum and question forty-five of the second part of the second part of Aquinas' Summa Theologiae. The insights gained from the study are then used to decipher the theoretical meaning of Augustine's famous saying: "love and do what thou wilt" and to expound on the practical value of wisdom for religious leaders.

Marian Piety and Ecumenical Convergence: Challenges and Opportunities - Eleutério, JM (Orientis Aura: Macau Perspectives in Religious …, 2017)
In the Catholic world, the year 2017 is marked by the celebration of the 100th anniversary of the Apparitions of Mary in Fátima, Portugal. Although the field of the devotional and popular …

Church in the Making: An Apophatic Ecclesiology of Consubstantiality - Eleutério, João Marques (Theological Studies, 2017)

Non-Native Raters and Native Speech: Other Perspective for the Research on Comprehensibility of Second Language Input - Figueiredo, Sandra; Simões, Edlia; Martins, Margarida Alves; Fernandes da Silva, Carlos (synergy, 2017)
Abstract: This study examines how specific variables such as age, first language, nationality, school grade and socioeconomic status (SES) affect the comprehensibility of second language (L2) speech in 92 second/non-native language learners. Comprehensibility refers to the degree of speech understanding. Fluency, rhythm, grammatical features and word stressing are concurrent factors for the listening comprehension (and the listener comprehensibility) mainly in L2 context. Research evidence focused the quality and differences of speech samples produced by the L2 learners and the comprehensibility rated by native speakers. In reverse scenario there is less evidence on the judgment of L2 learners for speech samples produced by native speakers. In this study we analysed if the comprehensibility ability of 92 young Portuguese L2 learners differ in the following conditions: age, nationality, home language, school grade, proficiency and socioeconomic status. Speech (one text) was recorded by a native speaker and was judged by L2 speakers using 1-5 Likert scale for comprehension difficulty. Main results showed that neither age nor home language had influence for comprehensibility, but socioeconomic, nationality and grades accounted for statistical differences between the groups tested. Also, data suggested that phonetic features are more likely important for the beginner in second language learning compared to the semantic features of speech that heavily depend on vocabulary domain. Keywords: Speech comprehensibility, nationality, grades, socioeconomic status, second language. Read more →

Work engagement: Evolution of the concept and a new inventory. Psychological Thought, - Kuok, A.C.H.; Taormina, R.J. (2017)

Insights for management among non-gaming industries: Employees’ dissonance in a casino dominant economy - Kuok, A.C.H. (Revista de Psicología del Trabajo y de las Organizaciones, 2017)

Lusophony Risks to Be a Heritage with No Future - Leandro, F. J. (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2017)

Examining the Factor Structure of the Victorian Gambling Screen in Chinese Casino Workers. - Mordeno, I.G.; Nalipay, M.J.N.; Coteriano, C.; Leong, S.U. (Current Psychology, 2017)

Preserving Cultural Identity by Rehabilitation of Public Spaces, Case Study Analyses on the Historic Center of Macao. - Pinheiro, Francisco Vizeu (Urban Design, 2017)

Redesigning historic cities facing rapid tourism growth: The Case of Macao’s World Heritage Centre and San Ma Lou Avenue - Pinheiro, Francisco Vizeu (Worldwide Hospitality and Tourism, 2017)

澳門《新城區總體規劃方案》之建議 - Pinheiro, Francisco Vizeu (澳門研究, 2017)

《澳門旅遊業發展總體規劃》文本建議 - Pinheiro, Francisco Vizeu (澳門研究, 2017)

Overall Opinion on Macau Urban Planning and the Five-Year Plan. - Pinheiro, Francisco Vizeu; Penny, W. (Journal of Macau Studies- Boletim de Estudos de Macau, 2017)

Transparency: A Necessary First Step Toward an Ethic of Finance - Rothlin, Stephan; McCann, D; Myers, T (Silliman Journal, 2017)

Entre a tradição e a modernidade, os Potiguara. Estudo etno-histórico, narrativas de memórias e rituais, a revisitação e o turismo - Simões, José Manuel (História, histórias, 2017)
Keywords: transformações

Perceived competence and social acceptance of preschool children in Macao: a case study - Teixeira, Vitor; Correia, Ana (International Journal of Learning and Teaching, 2017)

⼆⼗世紀澳⾨錯位的記憶——《神州在望》作品簡析. - Zhou, L. (Journal of Macau Studies, 2017)

Shequ construction and service development in urban China: an examination of the Shenzhen model - Tang, Ning; Sun, Fei (Community Development Journal, 2017)

User Preference on Artificial Reverberation and Delay Time Parameters - Pestana, Pedro Duarte; Reiss, Joshua; Barbosa, Álvaro (Journal of the Audio Engineering Society, 2017)

Social network predicts loss of fertilizations in nesting males of a fish with alternative reproductive tactics - Cardoso, Sara D.; Faustino, Ana I.; Costa, Silvia S.; Valério, Fábio; Gonçalves, David; Oliveira, Rui F. (acta ethologica, 2017)
Alternative reproductive tactics (ARTs) evolve when there is strong intra-sexual competition between conspecifics for access to mates. Typically, larger “bourgeois” males reproduce by securing the access to reproductive resources while smaller “parasitic” males reproduce by stealing fertilizations from larger males. A number of factors can influence the reproductive success of each tactic, including intrinsic (e.g. size) and extrinsic (e.g. tactic relative frequency) variables. An example where plastic ARTs occur is the peacock blenny Salaria pavo, with large males reproducing by defending nests and attracting females (bourgeois tactic) and small males reproducing by achieving sneaked fertilizations (parasitic tactic). In this study, we conducted field observations on individually tagged animals to determine their social network and collected eggs from 11 nests to determine the fertilization success of each male tactic. Paternity estimates for 550 offspring indicated an average fertilization success for nest-holder males of 95%. Nest-holder male morphological traits and social network parameters were tested as predictors of fertilization success, but only the number of sneakers present in the nest-holder’s social networks was found to be a predictor of paternity loss. Although male morphological traits had been previously found to be strongly correlated with reproductive success of nest-holder males, as measured by the number of eggs collected in the male’s nest, no correlation was found between any of the measured morphological traits and fertilization success for these males. The results suggest a stronger influence of the social environment than of morphological variables in the proportion of lost fertilizations by nest-holder males of this species.

Use of stable isotopes to understand food webs in Macao wetlands - Chen, Qian; Liu, Yang; Ho, Wei-Tim; Chan, Shek Kiu; Li, Qiu-hua; Huang, Jian-Rong (Wetlands Ecology and Management, 2017)
In this study, components of the food-web in Macao wetlands were quantified using stable isotope ratio techniques based on carbon and nitrogen values. The δ13C and δ15N values of particulate organic matter (δ13CPOM and δ15NPOM, respectively) ranged from −30.64 ± 1.0 to −28.1 ± 0.7 ‰, and from −1.11 ± 0.8 to 3.98 ± 0.7 ‰, respectively. The δ13C values of consumer species ranged from −33.94 to −16.92 ‰, showing a wide range from lower values in a freshwater lake and inner bay to higher values in a mangrove forest. The distinct dietary habits of consumer species and the location-specific food source composition were the main factors affecting the δ13C values. The consumer 15N-isotope enrichment values suggested that there were three trophic levels; primary, secondary, and tertiary. The primary consumer trophic level was represented by freshwater herbivorous gastropods, filter-feeding bivalves, and plankton-feeding fish, with a mean δ15N value of 5.052 ‰. The secondary consumer level included four deposit-feeding fish species distributed in Fai Chi Kei Bay and deposit-feeding gastropods in the Lotus Flower Bridge flat, with a mean δ15N value of 6.794 ‰. The tertiary consumers group consisted of four crab species, one shrimp species, and four fish species in the Lotus Flower Bridge Flat, with a mean δ15N value of 13.473 ‰. Their diet mainly comprised organic debris, bottom fauna, and rotten animal tissues. This study confirms the applicability of the isotopic approach in food web studies.

Hydrological Risk Assessment at Praia, Cape Verde - Silva, Jose Lino; Negreiros, Joao Garrott Marques (International Journal of Environment, Agriculture and Biotechnology, 2017)
Hydrology modeling became a relevant topic for the Cidade da Praia, Cabo Verde, Africa, due to negative impact risk to local population and its assets. The modeling via Geographical Information Systems (GIS) can help the decision-making process of space occupation and characterization for this type of risk. Under the municipalities of Praia, the phenomenon of flash flood is common, causing soil erosion and landslide. This constitutes a risk for the local habitat, particularly in districts with a lack of strong human infrastructures. To simulate, analyze and generate risk maps using GIS to help this county governance authorities for decision-making, thus, becomes the main aim of this article.

Impacts of Public Support and Voices Pluralism in Macao Newspapers - Simões, José Manuel; Faustino, Paulo (Journalism and Mass Communication, 2017)

Editorial - Castro, Maria Guilhermina; Palinhos, Jorge; Ribas, Daniel; Caires, Carlos Sena (Journal of Science and Technology of the Arts, 2017)

Catholic schools and inclusive education in Macao: a journey of a thousand miles - Correia, Ana; Teixeira, Vitor (EDUCA - International Catholic Journal of Education, 2017)

Ontogenetic development of the inner ear saccule and utricle in the Lusitanian toadfish: Potential implications for auditory sensitivity - Chaves, Patrícia P.; Valdoria, Ciara M. C.; Amorim, M. Clara P.; Vasconcelos, Raquel O. (Hearing Research, 2017)
Studies addressing structure-function relationships of the fish auditory system during development are sparse compared to other taxa. The Batrachoididae has become an important group to investigate mechanisms of auditory plasticity and evolution of auditory-vocal systems. A recent study reported ontogenetic improvements in the inner ear saccule sensitivity of the Lusitanian toadfish, Halobatrachus didactylus, but whether this results from changes in the sensory morphology remains unknown. We investigated how the macula and organization of auditory receptors in the saccule and utricle change during growth in this species. Inner ear sensory epithelia were removed from the end organs of previously PFA-fixed specimens, from non-vocal posthatch fry (<1.4 cm, standard length) to adults (>23 cm). Epithelia were phalloidin-stained and analysed for area, shape, number and orientation patterns of hair cells (HC), and number and size of saccular supporting cells (SC). Saccular macula area expanded 41x in total, and significantly more (relative to body length) among vocal juveniles (2.3–2.9 cm). Saccular HC number increased 25x but HC density decreased, suggesting that HC addition is slower relative to epithelial growth. While SC density decreased, SC apical area increased, contributing to the epithelial expansion. The utricule revealed increased HC density (striolar region) and less epithelial expansion (5x) with growth, contrasting with the saccule that may have a different developmental pattern due to its larger size and main auditory functions. Both macula shape and HC orientation patterns were already established in the posthatch fry and retained throughout growth in both end organs. We suggest that previously reported ontogenetic improvements in saccular sensitivity might be associated with changes in HC number (not density), size and/or molecular mechanisms controlling HC sensitivity. This is one of the first studies investigating the ontogenetic development of the saccule and utricle in a vocal fish and how it potentially relates to auditory enhancement for acoustic communication.
Keywords: Auditory sensitivity; Batrachoididae; Hair cell; Ontogeny; Saccule; Utricle

Desafios à unidade geopolítica da lusofonia - Leandro, Francisco da Silva (IDNBrief, 2017)
info:eu-repo/semantics/publishedVersion

Use of apparatuses in science laboratory: developmental characteristics of didactical interactions. (The International Education & Learning Review, 2018)

Malacca Creole Portuguese in the 19th century: Evidence of a wider lectal range? - Baxter, Alan N. (Journal of Pidgin and Creole Languages, 2018)
Abstract Earlier linguistic research suggested that Malacca Creole Portuguese (MCP) had existed without diglossia with Portuguese ever since the Dutch conquest of Portuguese Malacca in 1642, yet it had experienced some contact with Portuguese in the 19th and 20th centuries. The present study adds significantly to this discussion. It considers a range of information from sociohistorical studies and archival sources (including linguistic data) relating to the Dutch (1642–1795, 1818–1823) and early British (1795–1818, 1823–1884) colonial periods. For the Dutch period, it is seen that contact with other Creole Portuguese communities is likely to have persisted for some time. Most significant, however, is the finding that 19th century texts in Portuguese and creole Portuguese, recently identified in archival sources in London and Graz, show that Portuguese continued to be part of the Malacca sociolinguistic setting until the early British period, and that missionary Indo-Portuguese also had a presence at that time. It is concluded that, rather than presenting a narrow lectal range akin to that of the MCP community in the late 20th century, the creole lectal grid in the 19th century was more complex, and included dimensions of a continuum in a diglossic relationship with Portuguese.

Temporal variation in brain transcriptome is associated with the expression of female mimicry as a sequential male alternative reproductive tactic in fish - Cardoso, Sara D.; Gonçalves, David; Goesmann, Alexander; Canário, Adelino V. M.; Oliveira, Rui F. (Molecular Ecology, 2018)
Distinct patterns of gene expression often underlie intra- and intersexual differences, and the study of this set of coregulated genes is essential to understand the emergence of complex behavioural phenotypes. Here, we describe the development of a de novo transcriptome and brain gene expression profiles of wild-caught peacock blenny, Salaria pavo, an intertidal fish with sex-role reversal in courtship behaviour (i.e., females are the courting sex) and sequential alternative reproductive tactics in males (i.e., larger and older nest-holder males and smaller and younger sneaker males occur). Sneakers mimic both female's courtship behaviour and nuptial coloration to get access to nests and sneak fertilizations, and later in life transition into nest-holder males. Thus, this species offers the unique opportunity to study how the regulation of gene expression can contribute to intersex phenotypes and to the sequential expression of male and female behavioural phenotypes by the same individual. We found that at the whole brain level, expression of the sneaker tactic was paralleled by broader and divergent gene expression when compared to either females or nest-holder males, which were more similar between themselves. When looking at sex-biased transcripts, sneaker males are intersex rather than being either nest-holder or female-like, and their transcriptome is simultaneously demasculinized for nest-holder-biased transcripts and feminized for female-biased transcripts. These results indicate that evolutionary changes in reproductive plasticity can be achieved through regulation of gene expression, and in particular by varying the magnitude of expression of sex-biased genes, throughout the lifetime of the same individual.
Keywords: RNA-seq; Salaria pavo; alternative reproductive tactics; behavioural plasticity; neurogenomic state; sex-biased gene expression

A Confucian Perspective on Tertiary Education for the Common Good - Eh, Edmond (The Journal of the Macau Ricci Institute, 2018)
Confucian education is best captured by the programme described in the Great Learning. Education is presented first as the process of self-cultivation for the sake of developing virtuous character. Self-cultivation then ...

Science and Laudato Si’ on the Paradigm Shift towards Sustainable Development - Gassner, Franz (The Journal of the Macau Ricci Institute, 2018)
For sustainability researchers and global policy makers it is lucid clear that a radical turnaround of modern societies is needed to approach sustainable development paths. Pope Francis takes his stand on a basic paradigm shift in his Encyclical Letter Laudato Si’: Care for our Common Home (2015). He calls for a radical shift of mindsets and ecological and cultural conversion which are needed for sustainability and a life in dignity for all. The author compares aspects from sustainability research and Laudato Si’ and shows how science and Francis spiritual-theological take converge. Both call for the need of new mindsets and spiritual resources to nourish just life-styles and sustainable societies.

The antecedents of In-service teachers’ burnout in a casino dominant economy - Kuok, A. C. H.; Lam, S. M. I (KEDI Journal of Educational Policy, 2018)

Multi-view Convolution Neural Network with Swarm Search Based Hyperparameter Optimization for Enhancing Heart Disease and Breast Cancer Detection - Lan, K.; Li, T.; Fong, S.; Marques, J.A.L.; Wong, R.K. (5th International Conference on Soft Computing and Machine Intelligence, ISCMI 2018, 2018)

Book Review: ‘The Catholic Invasion of China: Remaking Chinese Christianity’, by D. E. Mungello (Lanham, MD: Rowman & Littlefield, 2015) - Law, Cyril Jerome (Heythrop Journal, 2018)

Macau entre a “China Tropical” e a lusofonia a Oriente: Algumas achegas sobre os contextos colonial e pós-colonial - Morais, Isabel (Portuguese Studies Review, 2018)

Evaluation of Deterministic Spatial Interpolators with myGeoffice©: The Utah Grasshoppers Case - Negreiros, Joao; Phillips, Jenny O. L. (International Journal of Geology, Agriculture and Environmental Sciences, 2018)
The knowledge of spatial distribution of grasshoppers can be very relevant for agricultural planning purposes. On the other hand, the comparison of spatial interpolators for efficiency and reliability reasons is also a key factor to understand interpolation maps outcomes (versus reality). At last, but not least, the use of open Web geographical tools to disseminate true spatial inferential methods to address spatial issues is still quite limited (if none) in high schools and universities, particularly in Geography subjects. If the latter can be addressed with myGeoffice©, the first issue will use the Utah, USA, dataset (58 samples) to layout the spatial distribution of grasshoppers and understand the counties that are more pro to this kind of agriculture infestation. Inverse Distance Weighted (IDW), Moving Average (MA), Multi-quadratic, Inverse Multi-quadratic and Nearest Neighbor (NN) will produce interpolated surfaces of grasshopper’s properties. Efficiency of spatial interpolators was assessed in this writing based on the prediction error’s statistics derived from the difference between the estimation and the real samples on a cross-validation procedure. Remarkably, results show that NN was the most accurate one when compared with the remaining deterministic approaches at sample’s locations.

Professional Ethics as Training in Civic Education - Rothlin, Stephan (Hong Kong Journal of Catholic Studies, 2018)

The Long March toward Moral Leadership in Business - Rothlin, Stephan; McCann, D (Silliman Journal, 2018)

Reading acquisition in beginner readers: Typical errors in European Portuguese - Simões, Edlia; Martins, Margarida Alves (Educação e Pesquisa, 2018)

A defesa noticiosa do status quo - Simões, José Manuel (E-Revista de Estudos Interculturais, 2018)

從即興戲劇體驗討論香港幼兒美感教育環境 - 何嘉莉 (亞洲戲劇教育學刊, 2018)

The influence of SAR government performance on people’s trust toward Central government: Implications for Hong Kong and Macau civic education - Chris Cheung, Hin Wah; So, Man Yum Larry; Choi, Chi U. Francis; Chow, Chin Fung Philip (Asian Education and Development Studies, 2018)
Purpose The purpose of this paper is to explore the influence of Special Administrative Region (SAR) performance on the “trust” of Hong Kong and Macau people, who “live” under similar context of “one country, two systems,” toward Beijing Central Government. The different perceptions, relating to the abovementioned issue, of the young peoples’ are also investigated. Implication for civic education in these two societies will be brought to light. Design/methodology/approach This study adopts secondary data analysis on the captioned topic. To further illustrate the said issue, this study reviews and analyzes data from protest campaigns in both societies. Findings This paper finds that the performance of Hong Kong and Macau SAR Governments has different impacts on the peoples’ “trust” toward Central Government. It may attribute to the different perceptions about the role of Central Government and levels of democratization in these societies. Civic education emphasizing the “core spirit” of “One country, two systems,” roles of SAR and Central Governments could enable young people better comprehend their relationship with Mainland China and their role as SAR–Chinese citizens. Originality/value This paper is an exploratory study for providing implications for further research on this topic.
Keywords: Civic education; Political trust

Macao Caught between the "Tropical China" and Oriental-style: An Approach to the Colonial and Post-colonial Contexts/Macau entre a "China Tropical" e a lusofonia a Oriente: Algumas achegas sobre os contextos colonial e pos-colonial/Macao entre la "Chine tropicale" et la lusophonie a l'orientale: contribution a l'etude des contextes colonial et post-colonial. - Morais, Isabel (Portuguese Studies Review, 2018)
Gale OneFile includes Macao Caught between the "Tropical China&q by Isabel Morais. Click to explore.

Transgenerational Entrepreneurship In Chinese Family Businesses: Proposal For A Model Of Work-Life Synergy - Phillips, Jenny O. L.; Osorio, Arturo E.; Alves, José (2018)
Family business are the dominant form of business in the world, and Chinese family business (CFB) is a unique type of family business that relies on collective action to survive. This paper argues that in CFBs, entrepreneurial actions are transgenerational collective endeavors, and successors are groomed as stewards of the family legacy. Work-life relationship in CFBs is about synergy and not balance because the family identity is the business identity, and vice-versa. Using five in-depth case studies, this research introduces an alternative understanding of CFBs and proposes a model of work-life synergy in transgenerational entrepreneurship based on discussion of five theory-based propositions. This model explains that through emphasizing on the business family's shared value and entrepreneurial legacy, elements of trust, shared identity and stewardship of family members are enhanced which leads to collective action and goal of the business family, resulting in transgenerational entrepreneurship. Limitations and future research are presented.
Keywords: Chinese family business; family legacy; stewardship; transgenerational entrepreneurship; work-life synergy.

The Cultivation of Research Labor in Pacific Asia with Special Reference to Singapore - Ge, Yun; Ho, K. C. (Asia Pacific Education Review, 2018)
This paper adopts a political economy perspective in understanding how the country context frames the development of higher education doctoral science, technology, engineering, and mathematics (STEM) programs. We argue that a country's commitment to research and development spending as a strategy to maintain its economic competitiveness creates the market for research labor. This embeddedness of STEM doctoral training programs in the country's science and technology system enlarges differences between STEM and non-STEM doctoral programs. This argument is validated from a survey of doctoral students in leading Pacific Asian universities which shows that STEM doctoral programs have stronger research networks, are better financed, use better facilities, and incorporate a variety of research placements. The embeddedness of STEM programs is further illustrated from the case of Singapore. Singapore-based STEM doctoral students mention enjoying better financial support and receiving better career advice from their supervisors. They depend on collaborative peer learning and cite more varied employment options when asked about their career plans.
Keywords: Career Counseling; Cooperative Learning; Doctoral Programs; Educational Facilities; Employment Opportunities; Financial Support; Foreign Countries; Graduate Students; Networks; STEM Education; Student Attitudes; Student Placement; Student Research; Student Surveys; Supervisor Supervisee Relationship; Universities

O Espaço ao Espaço Público e ao Sentido dos Fatos que os Media nos Oferecem - Simões, José Manuel (Revista GEMInIS, 2018)
Comunicar é tornar comum e informar é dar forma à comunicação. Entre um e outro vai frequentemente uma distancia que nem sempre é possível eliminar. O objetivo deste artigo é mostrar que tanto a comunicação como a informação são um espaço ao sentido da vida. Pese embora as contrariedades e obstáculos, a conivência com os poderes, os imperativos de rentabilidade, a pressão do tempo e a aceleração, os media oferecem um espaço ao espaço público, ao sentido dos fatos, à interpelação; um espaço ao sentido da vida.

When the Gospel meets the China Dream: Religious Freedom and the Golden Rule - Chiaretto Yan, Kin Sheung (International Bulletin of Mission Research, 2018)
The issue of religious freedom affects Sino-Vatican relations, but the Roman Catholic Church shares values with Confucianism, which provides common ground for dialogue. Pope Francis is focusing the church outward by promoting a culture of encounter and by working unceasingly for a fraternal dialogue of peace. Chinese president Xi Jinping urges his people to fulfill the China dream, emphasizing the core values of harmony, friendship, and civilization. Many have believed that the Gospel can contribute to China?s spiritual civilization; normalization of relations between China and the Holy See would benefit China and the Catholic Church and contribute to world peace and harmony.

Chromosome-level reference genome of the Siamese fighting fish Betta splendens, a model species for the study of aggression - Fan, Guangyi; Chan, Judy; Ma, Kailong; Yang, Binrui; Zhang, He; Yang, Xianwei; Shi, Chengcheng; Law, Henry; Ren, Zhitao; Xu, Qiwu; Liu, Qun; Wang, Jiahao; et al. (GigaScience, 2018)

Open Innovation as Means of Building Social Capital: A Way to Globalization for Traditional SMEs - Phillips, Jenny O. L. (Journal of Strategic Innovation and Sustainability, 2018)
This research explores innovation of traditional SMEs that do not actively invest in innovation. Elements of open innovation have been identified in these firms in their effort to build social capital which they perceive as pertinent to their businesses. The result of the research shows that instead of using social capital as means for innovation, the unintentional practice of open innovation has contributed to the development of social capital, which further opens up potential for globalization. As a result, a model of open innovation as means of developing social capital for enhancing globalization potential for SMEs was developed.
Keywords: Innovation; SMEs; Social Capital; Sustainability

Placement, inclusion, law and teachers’ perceptions in Macao’s schools - Teixeira, Vitor; Correia, Ana; Monteiro, Elisa; Kuok, A. C. H.; Forlin, Chris (International Journal of Inclusive Education, 2018)
In Macao, the government has initiated a debate regarding revisions in the Decree Law in order to promote a more inclusive schooling system. In this Special Administrative Region of China, inclusive education is one of three possible types of special education that are likely be legislated in the future. The way the teachers perceive the different aspects related to inclusive education, namely the principles, concepts and law, is essential for its full implementation. The aim of this study is to understand teachers’ perceptions about the proposed amendments in the consultation document for changes in the special education regime. In particular, we focus on teachers’ acceptance of the recommended role of parents, the proposed placement models and expectations for teacher training. A mixed-methods approach with a survey of a sample of 500 teachers in private schools and interviews to a sub-sample of 20 provide the data. While agreeing in principle with the majority of the proposed changes in the Decree Law, there were several reservations made by the teachers, especially regarding the extent of parental choice, placement decisions and teacher training. Recommendations to continue the pathway for a more inclusive education system in Macao and for further research are made.
Keywords: Disability; education policy; inclusive education; special education; special education needs

Acoustic communication in marine shallow waters: testing the acoustic adaptive hypothesis in sand gobies - Amorim, Maria Clara P.; Vasconcelos, Raquel O.; Bolgan, Marta; Pedroso, Silvia S.; Fonseca, Paulo J. (Journal of Experimental Biology, 2018)
Skip to Next Section Acoustic communication is an important part of social behaviour of fish species that live or breed in shallow noisy waters. Previous studies have shown that some fish species exploit a quiet window in the background noise for communication. However, it remains to be examined whether hearing abilities and sound production of fish are adapted to marine habitats presenting high hydrodynamism. Here, we investigated whether the communication system of the painted (Pomatoschistus pictus) and the marbled (Pomatoschistus marmoratus) gobies is adapted to enhance sound transmission and reception in Atlantic shallow water environments. We recorded and measured the sound pressure levels of social vocalisations of both species, as well as snapshots of ambient noise of habitats characterised by different hydrodynamics. Hearing thresholds (in terms of both sound pressure and particle acceleration) and responses to conspecific signals were determined using the auditory evoked potential recording technique. We found that the peak frequency range (100–300 Hz) of acoustic signals matched the best hearing sensitivity in both species and appeared well adapted for short-range communication in Atlantic habitats. Sandy/rocky exposed beaches presented a quiet window, observable even during the breaking of moderate waves, coincident with the main sound frequencies and best hearing sensitivities of both species. Our data demonstrate that the hearing abilities of these gobies are well suited to detect conspecific sounds within typical interacting distances (a few body lengths) in Atlantic shallow waters. These findings lend support to the acoustic adaptive hypothesis, under the sensory drive framework, proposing that signals and perception systems coevolve to be effective within local environment constraints.

What Kinds of Comparison Are Most Useful in the Study of World Philosophies? - Sivin, Nathan; Akasoy, Anna; Anderson, Warwick; Colas, Gérard; Eh, Edmond (Journal of World Philosophies, 2018)
Keywords: comparative history; connected history; cultural manifolds; diachronic; intellectual history; inter-cultural comparison; intra-cultural comparison; mutual pollination; postcolonial history; synchronic; transnational history

The interplay between a Confucian-heritage culture and teachers’ sentiments and attitudes towards inclusion in Macao - Correia, Ana; Monteiro, Elisa; Kuok, Angus; Forlin, Christine; Teixeira, Vitor (European Journal of Special Education Research, 2019)

Lead: An iOS Application to Help in the Construction of New Habits - de Aguiar, André Wescley Oliveira; Bezerra, Jagni Dasa Horta; Marques, João Alexandre Lobo; de Alexandria, Auzuir Ripardo (International Journal of Information and Electronics Engineering, 2019)

Surface sediment composition and distribution of hydrothermal derived elements at the Duanqiao-1 hydrothermal field, Southwest Indian Ridge - Dias, Ágata; Liao, Shili; Tao, Chunhui; Su, Xin; Yang, Zhen; Ni, Jianyu; Liang, Jin; Yang, Weifang; Liu, Jia; Li, Wei; Dong, Chuanwan (Marine Geology, 2019)

Evaluating Mathematical Models for Morphological Classification of the QRS Complex - Do Vale Madeiro, J.P.; Barreto, D.; Marques, J.A.L.; Salinet, J.L. (Computing in Cardiology, 2019)

Environmental characterization of 4,4′-dichlorobenzophenone in surface waters from Macao and Hong Kong coastal areas (Pearl River Delta) and its toxicity on two biological models: Artemia salina and Daphnia magna - Ivorra, Lucia; Cardoso, Patricia G.; Chan, Shek Kiu; Tagulao, Karen; Cruzeiro, Catarina (Ecotoxicology and Environmental Safety, 2019)

College Students’ Attitudes Toward Counseling for Mental Health Issues in Two Developing Asian Countries - Kuok, A. C. H; Rashidnia, J (Spritual Psychology and Counseling, 2019)

Automatic Cardiotocography Diagnostic System Based on Hilbert Transform and Adaptive Threshold Technique - Marques, J. A. Lobo; Cortez, P. C.; Madeiro, J. P. D. V.; Fong, S. J.; Schlindwein, F. S.; Albuquerque, V. H. C. D. (IEEE Access, 2019)
The visual analysis of cardiotocographic examinations is a very subjective process. The accurate detection and segmentation of the fetal heart rate (FHR) features and their correlation with the uterine contractions in time allow a better diagnostic and the possibility of anticipation of many problems related to fetal distress. This paper presents a computerized diagnostic aid system based on digital signal processing techniques to detect and segment changes in the FHR and the uterine tone signals automatically. After a pre-processing phase, the FHR baseline detection is calculated. An auxiliary signal called detection line is proposed to support the detection and segmentation processes. Then, the Hilbert transform is used with an adaptive threshold for identifying fiducial points on the fetal and maternal signals. For an antepartum (before labor) database, the positive predictivity value (PPV) is 96.80% for the FHR decelerations, and 96.18% for the FHR accelerations. For an intrapartum (during labor) database, the PPV found was 91.31% for the uterine contractions, 94.01% for the FHR decelerations, and 100% for the FHR accelerations. For the whole set of exams, PPV and SE were both 100% for the identification of FHR DIP II and prolonged decelerations.
Keywords: Acceleration; Biomedical monitoring; Cardiography; Cardiotocography (CTG); Databases; FHR DIP II; FHR accelerations; FHR baseline detection; FHR decelerations; Fetal heart rate; Hilbert transform; Hilbert transforms; Monitoring; PPV; Transforms; accurate fetal heart rate feature detection; accurate fetal heart rate feature segmentation; adaptive threshold technique; antepartum database; automatic cardiotocography diagnostic system; auxiliary signal; cardiotocographic examinations; computerized diagnostic aid system; digital signal processing techniques; fetal distress; fetal heart rate (FHR); fetal signals; maternal signals; medical signal detection; medical signal processing; obstetrics; patient monitoring; positive predictivity value; preprocessing phase; segmentation processes; uterine contractions; uterine contractions (UC); uterine tone signals; visual analysis

Web 2.0 Tool Recommendations for Teachers - Negreiros, Joao Garrott Marques; Lei, Weng Chi (International Journal of Innovation and Research in Educational Sciences, 2019)

Is the Belt and Road Initiative in Africa Sustainable? - Nwachukwu, Francis C. (The Journal of the Macau Ricci Institute, 2019)
In 2000, the China-Africa relationship was further strengthened with the establishment of the Forum on China-Africa Cooperation (FOCAC). The FOCAC offers a platform for consultation and cooperation mechanisms aimed at deepening diplomatic, security, trade and investment relations between China and African countries. Later came the Belt and Road Initiative (BRI) in 2013, an international trade network initiated by China that connects the three continents of Asia, Europe and Africa. The BRI focuses on the following key areas: cultural exchange; policy coordination; facilities connectivity; trade and investment; and financial integration. The BRI shares development objectives similar to those of the United Nations’ Sustainable Development Goals (SDGs). In fact, the BRI implements part of the SDGs and provides a practical mechanism to strengthen the Sino-Africa relationship, which Africa can leverage to meet its Sustainable Goals. Africa is linked through the “Road” of the BRI plan and has received infrastructural projects funded by China to facilitate trade and integration of the national economies along the trading route. Through the establishment of Economic and Trade Zones which attracts investments from Chinese companies, and building infrastructures such as sea ports and railways, China through the BRI framework is helping Africa meet UN SGD Goal 9 concerning industry, innovation and infrastructure. A practical effect is that the BRI is helping African countries overcome the infrastructure gap, create jobs, acquire skills and promote integration between countries.

Análise multimodal de estratégias discursivas: debate sobre o “bailout” entre Hillary Clinton e Bernie Sanders - Rocha, Nuno (ElingUP : Revista eletrónica de Linguística dos Estudantes da Universidade do Porto, 2019)
Este trabalho consiste numa análise multimodal das estratégias discursivas de Bernie Sanders e Hillary Clinton num excerto de um debate sobre as benesses dadas pela senadora norte americana aos bancos no pós-crise económica global de 2008. Bernie Sanders e Hillary Clinton evidenciaram uma linguagem corporal diferente, tanto na posição de locutor como na de interlocutor. No entanto, mesmo utilizando estratégias de comunicação verbal e física diferentes, os gestos utilizados enquadram-se no campo dos gestos recorrentemente observados em figuras políticas em estudos feitos por outros autores. Reforça-se assim a ideia de que os gestos em questão são regularmente utilizados por figuras políticas.

O papel da imprensa em língua portuguesa de Macau: a ética, a ideologia do proissionalismo e o Código Deontológico dos Jornalistas - Simões, José Manuel (Estudos em Jornalismo e Mídia, 2019)
In Macao, Special Autonomous Region of China, there are two professional codes of journalists: one by the Portuguese and English Press Association of Macao and the other by the Macao Journalists’ Association, and there is no regulator in the territory or anyone who administers the rules or sanctions the journalists activity. here’s also no cases of known or reported censorship. However, according to the latest human rights report for this small region of Asia, “the Government has taken steps to limit the coverage of unfavorable news”, admitting the practice of self-censorship by the media.

Classroom management into learning: using phenomenography to analyse student teachers’ conceptions of classroom management - Correia, Ana Maria (Revista Portuguesa de Investigação Educacional, 2019)
Classroom management is a critical area in the curriculum of teacher education programs. Student teachers’ conceptions of the role of the teacher as a class leader are frequently backed by their intuition and experience as students and socio-cultural context rather than evidence-based. This paper examines the conceptions of classroom management held by a multicultural group of forty-four student teachers attending a teacher education program at a higher education institute in Macao. The study aims at understanding the patterns of variation expressed by student teachers regarding the purpose and relevance of the object of learning. It compares a) the patterns of variation in students’ views of classroom management, and b) the students’ learning progress based on the pre-and post-test. The phenomenographic approach was adopted as the conceptual framework. Participants handwritten transcripts from student teachers at the first and last sessions of the course are the primary type of data collection. The findings show that changes in student teachers’ understanding of the conceptions of classroom management occurred during the course. The initial preferences for disciplinary approaches to classroom leadership have given way to conceptions of promoting the integration of classroom management into learning. The participants expressed increasing adherence to classroom management systems targeting and providing behavioural and academic supports and interventions to children and adolescents with and without special needs.

Perceived efficacy of teachers in Macao and their alacrity to engage with inclusive education - Monteiro, Elisa; Kuok, A. C. H.; Correia, Ana; Forlin, Chris; Teixeira, Vitor (International Journal of Inclusive Education, 2019)
This paper reports findings of a mixed methods study examining private school teachers’ perceptions of efficacy in dealing with the challenges presented by inclusive education in Macao. This is highly pertinent after the Government invited consultation to propose changes to amendments of the Decree Law of 1996 concerning the education of students with Special Education Needs (SEN) which will likely see private schools being required to accept these students in the future. Within the context of teacher preparedness for inclusive education, the study found that a number of teachers felt that they were not at all prepared to teach students with SEN. Whilst some teachers suggested that they lacked skills and knowledge in teaching in inclusive classrooms, some felt overwhelmed with the challenges. The teachers proposed that they would need to know how to provide instructional adaptations and modifications to support students with SEN. Implications for continuous development of teacher training and education are discussed within the context of improving teacher efficacy and how private school teachers could better respond to the challenges of inclusive education in Macao.
Keywords: Inclusive education; Macao; teacher education; teacher efficacy

Characterization of the Natural Soundscape of Zebrafish and Comparison with the Captive Noise Conditions - Lara, Rafael A.; Vasconcelos, Raquel O. (Zebrafish, 2019)
Zebrafish is a well-established model organism in hearing research. Although the acoustic environment is known to shape the structure and sensitivity of auditory systems, there is no information on the natural soundscape of this species. Moreover, zebrafish are typically reared in large-scale housing systems (HS), although their acoustic properties and potential effects on hearing remain unknown. We characterized the soundscape of both zebrafish natural habitats and laboratory captive conditions, and discussed possible impact on auditory sensitivity. Sound recordings were conducted in five distinct zebrafish habitats (Southwest India), from quieter stagnant environments with diverse biological/abiotic sounds to louder watercourses characterized by current and moving substrate sounds. Sound pressure level (SPL) varied between 98 and 126 dB re 1 μPa. Sound spectra presented most energy below 3000 Hz and quieter noise windows were found in the noisiest habitats matching the species best hearing range. Contrastingly, recordings from three zebrafish HS revealed higher SPL (122-143 dB) and most energy below 1000 Hz with more spectral peaks, which might cause significant auditory masking. This study establishes an important ground for future research on the adaptation of zebrafish auditory system to the natural soundscapes, and highlights the importance of controlling noise conditions in captivity.
Keywords: Animals; Animals, Laboratory; Auditory Threshold; Batrachoidiformes; Ecosystem; Environment; Female; Hair Cells, Auditory; Hearing; Housing, Animal; India; Male; Neuronal Plasticity; Noise; Saccule and Utricle; Seasons; Sexual Behavior, Animal; Sound; Species Specificity; Vocalization, Animal; Zebrafish; ambient noise; hearing sensitivity; natural habitat; sound pressure level; soundscape

Influência da nova estrutura fiscal de impostos de Angola na gestão de escolas privadas do municipio do Lobito - Armando Carlos Hombo Nogueira; Luis Miguel Pacheco; Marcus Antonio Almeida Rodrigues (Revista Gestao em Analise, 2019)

Ten Spatial Problems with myGeoffice© for Teaching Purposes - Negreiros, Joao; Diakite, Ansoumane (Open Journal of Social Sciences, 2019)
For a long time, Geography did not hold a specific mathematical approach for any interpretation of space and this was the key reason why Geography degrees covered a wide variety of subjects such as demography, geology or topography to fulfill its curriculum. Yet from the 90’s, Geography finally created its own research agenda to meet four vital questions of any true geographer: “Where is …?”, “Is there a general spatial pattern?”, “What are the anomalies?” and “Why do these phenomena pursue certain spatial distribution?” The present review article addresses ten different spatial (point, regression and event) issues for learning and teaching aim where statistics play a major background role on the outcomes of myGeoffice© free Web GIS platform. These include cluster analysis, geographically weighted regression (GWR), ordinary least squares (OLS) regression, path analysis, minimum spanning tree, linear regression, space-time clustering and point patterns, for instance. Although the technical viewpoint of the algorithms is not explained at fully, this review paper makes a rather strong emphasis on the result’s interpretation, their respective meaning and when these techniques should be applied in a learning/teaching context.

Macao air quality forecast using statistical methods - Lei, Man Tat; Monjardino, Joana; Mendes, Luisa; Ferreira, Francisco (International Journal of Environmental Impacts: Management, Mitigation and Recovery, 2019)

Artificial selection for male winners in the Siamese fighting fish Betta splendens correlates with high female aggression - Ramos, A.; Gonçalves, D. (Frontiers in Zoology, 2019)
In Southeast Asia, males of the Siamese fighting fish Betta splendens have been selected across centuries for paired-staged fights. During the selection process, matched for size males fight in a small tank until the contest is resolved. Breeders discard losing batches and reproduce winner batches with the aim of increasing fight performance. We assessed the results of this long-term selection process by comparing under standard laboratory conditions male and female aggressive behaviour of one strain selected for staged fights (“fighters”) and one strain of wild-types. The aggressive response of adult fish was tested against their mirror image or a size-matched conspecific. Fighter males were more aggressive than wild-type males for all measured behaviours. Differences were not only quantitative but the pattern of fight display was also divergent. Fighter males had an overall higher swimming activity, performing frequent fast strikes in the direction of the intruder and displaying from a distance. Wild-type males were less active and exhibited aggressive displays mostly in close proximity to the stimuli. Females of the fighter strain, which are not used for fights, were also more aggressive than wild-type females. Aggressive behaviours were correlated across male and female fighter siblings, suggesting common genetic and physiological mechanisms to male and female aggression in this species. The study further shows that results were largely independent of the stimulus type, with the mirror test inducing similar and less variable responses than the live conspecific presentation. These results suggest that selection for male winners co-selected for high-frequency and metabolic demanding aggressive display in males and also enhanced female aggression, opening a wide range of testable hypothesis about the ultimate and proximate mechanisms of male and female aggression in B. splendens.
Keywords: Aggression; Artificial selection; Domestication; Mirror test; Sexual conflict

Macao air quality forecast using statistical methods - Lei, Man Tat; Monjardino, Joana; Mendes, Luisa; Gonçalves, David; Ferreira, Francisco (Air Quality, Atmosphere & Health, 2019)
The levels of air pollution in Macao often exceeded the levels recommended by WHO. In order for the population to take precautionary measures and avoid further health risks under high pollutant exposure, it is important to develop a reliable air quality forecast. Statistical models based on linear multiple regression (MR) and classification and regression trees (CART) analysis were developed successfully, for Macao, to predict the next day concentrations of NO2, PM10, PM2.5, and O3. All the developed models were statistically significantly valid with a 95% confidence level with high coefficients of determination (from 0.78 to 0.93) for all pollutants. The models utilized meteorological and air quality variables based on 5 years of historical data, from 2013 to 2017. Data from 2013 to 2016 were used to develop the statistical models and data from 2017 was used for validation purposes. A wide range of meteorological and air quality variables was identified, and only some were selected as significant independent variables. Meteorological variables were selected from an extensive list of variables, including geopotential height, relative humidity, atmospheric stability, and air temperature at different vertical levels. Air quality variables translate the resilience of the recent past concentrations of each pollutant and usually are maximum and/or the average of latest 24-h levels. The models were applied in forecasting the next day average daily concentrations for NO2 and PM and maximum hourly O3 levels for five air quality monitoring stations. The results are expected to be an operational air quality forecast for Macao.
Keywords: Macao; NO2; O3; PM10; PM2.5; Particulate matter

Uptake and depuration kinetics of dicofol metabolite 4,4′-dichlorobenzophenone, in the edible Asiatic clam Meretrix meretrix - Ivorra, Lucia; Cruzeiro, Catarina; Chan, Shek Kiu; Tagulao, Karen Araño; Cardoso, Patricia G. (Chemosphere, 2019)
Uptake and depuration kinetics of 4,4′-dichlorobenzophenone (main metabolite of dicofol) in the edible clam Meretrix meretrix were evaluated through a mesocosm experiment. M. meretrix was exposed to different dicofol concentrations (environmental concentration, D1 = 50 ng/L; supra-environmental concentration, D2 = 500 ng/L) for 15 days, followed by the same depuration period. To accomplish this goal, an analytical method was successfully optimized for 4,4′-DCBP using QuEChERS as extraction method with a range of concentrations 0.3–76.8 ng/g ww quantified by gas chromatography coupled to tandem mass spectrometry. Our results demonstrated different kinetics of accumulation depending on the two dicofol treatments. For D1, the uptake kinetic was best fitted using a plateau followed by one phase association kinetic model, while for D2 a one phase association kinetic model suited better. Similar bioconcentration factors were obtained for both concentrations but only animals exposed to D2, showed 4,4′-DCBP levels above the limits of quantification after 24 h exposure. These animals also showed lower uptake rate (ku) than organisms exposed to D1. During the depuration period, only organisms exposed to D1 successfully depurated after 24 h. On the other hand, although animals exposed to D2 presented higher elimination factor, they did not reach the original levels after depuration. Moreover, values detected in these clams were higher than the Maximum Residue Level (10 ng/g) established by the European legislation. This indicates that longer periods of depuration time than the ones used in this study, may be needed in order to reach safe levels for human consumption. This work also demonstrated that studies on metabolite kinetics during uptake/depuration experiments, could be a new alternative to understand the impact and metabolism of pesticides in the marine environment.
Keywords: Bivalves; GC-MS/MS; Organochlorine pesticides; QuEChERS bioconcentration; Seafood

Realizing the promises of replication studies in education - Morrison, Keith (Educational Research and Evaluation, 2019)

THE INTERPLAY BETWEEN A CONFUCIAN-HERITAGE CULTURE AND TEACHERS' SENTIMENTS AND ATTITUDES TOWARDS INCLUSION IN MACAU - Correia, Ana; Forlin, Chris; Teixeira, Vitor Manuel dos Santos; Kuok, A. C. H.; Monteiro, Elisa (2019)
Macau Special Administration Region (Macau SAR) is in the process of revising legislation concerning special and inclusive education. While the institutional discourse revolves around establishing inclusive education, it is unclear as to how the proposed changes will enable or depress this from occurring. This research, therefore, examined teachers’ attitudes towards inclusion as an indication of how well the new legislation may be received. Specifically, it investigated the interplay between 508 teachers working in private schools in Macau, that identified themselves as being inclusive schools, and teachers’ sentiments and attitudes towards the acceptance of inclusion and the role that Confucian values might play in shaping these attitudes. Discussion focusses on four key outcomes that need to be addressed if a significant improvement in including all children in regular schools in Macau is to be achieved. These include the need (1) to clarify the concept of inclusion at government, school, and teacher levels as it currently has ambiguous meaning; (2) to provide teachers with more opportunities to have systematic contacts with students with SEN, as this is crucial to improving their sentiments and attitudes toward people with disability; (3) to provide professional learning about inclusive education with better partnerships between teacher education institutions and schools to bridge theory and practice; and (4) to review the hidden influence of the subtle levels of time-honoured Confucian beliefs in Macau, which are not manifest nor easily detected but possibly have a deep impact on day-to-day practices.

Conceptualizing the Second Education Circuit for China’s Doctoral Students in Asia - Ge, Yun; Ho, Kong Chong (International Journal of Chinese Education, 2019)
The quest to become research universities of international repute has led flagship universities in East and Southeast Asia to develop a new focus on attracting international doctoral students. This paper aims to understand Chinese doctoral students’ mobility in the immediate region and their education to work perceptions. The study draws from a sample of 301 doctoral students from China who were studying at five universities in Japan, South Korea, and Singapore. Analysis on students’ decision making and after-study pathways highlights the regional exchange in related areas. We argue that this regional mobility of doctoral students, characterized as the second education circuit, is facilitated by a higher education migration infrastructure with three interactively weaved dimensions: commercial, social, and regulatory. The research findings suggest the growing importance of Asia as a regional second circuit of doctoral training for students from China.

Motives of Traditional and Emerging Donors in Aid Giving: Comparative Study between China and France - Diakite, Ansoumane D.; Phillips, Jenny O. L. (Journal of Social and Political Sciences, 2019)
Since the beginning of bilateral aid giving in the aftermath of the Second World War, the motives for aid giving have changed from being purely political and humanitarian to a mix of different interests. While poverty reduction is frequently stated as the goal of aid giving, it is commonplace for donors to use aid to advance their national interests. The rise of new, emerging donors is creating discussion in both the political and academic fields of aid giving. Traditional or western donors see emerging donors, such as China’s efforts in aid-giving as seeking the natural resources of the recipient countries. This paper provides a historical analysis of the aid-giving motivations underlying an emerging donor, China, and a traditional donor, France. The motives for China’s and France’s aid giving to African countries, with special focus on Guinea, show a great number of similarities.
Keywords: Aid Giving Motives, Emerging Donor, Traditional Donor, Poverty Reduction

On the probability flow in the Stock market I: The Black-Scholes case - Arraut, Ivan; Au, Alan; Tse, Alan Ching-biu; Marques, Joao Alexandre Lobo (arXiv.org, 2020)
It is known that the probability is not a conserved quantity in the stock market, given the fact that it corresponds to an open system. In this paper we analyze the flow of probability in this system by expressing the ideal Black-Scholes equation in the Hamiltonian form. We then analyze how the non-conservation of probability affects the stability of the prices of the Stocks. Finally, we find the conditions under which the probability might be conserved in the market, challenging in this way the non-Hermitian nature of the Black-Scholes Hamiltonian.
Keywords: General Finance

The Film Sound Analysis Framework: A Conceptual tool to Interpret the Cinematic Experience - Barbosa, Álvaro; Dizon, Kristine (Journal of Science and Technology of the Arts, 2020)
Keywords: Analysis framework; Film studies; Sound and music design

Multi-view convolutional neural network with leader and long-tail particle swarm optimizer for enhancing heart disease and breast cancer detection - Lan, K.; Liu, L.; Li, T.; Chen, Y.; Fong, S.; Marques, J.A.L.; Wong, R.K.; Tang, R. (Neural Computing and Applications, 2020)

Nonlinear characterization and complexity analysis of cardiotocographic examinations using entropy measures - Marques, J.A.L.; Cortez, P.C.; Madeiro, J.P.V.; Albuquerque, V.H.C.; Fong, S.J.; Schlindwein, F.S. (Journal of Supercomputing, 2020)

Pestilent Popes or a Pestilent Church? Judaism, Catholicism, and Skeptical Theism - McNabb, Tyler Dalton (The Heythrop Journal, 2020)

Has Oppy Done Away with the Aristotelian Proof? - McNabb, Tyler; DeVito, Michael (The Heythrop Journal, 2020)

Review of Gorard, S. (2020) Getting evidence into education: evaluating the routes to policy and practice - Morrison, Keith (Educational Research and Evaluation, 2020)

High-precision geochronology of Mesozoic magmatism in Macao, Southeast China: Evidence for multistage granite emplacement - Quelhas, Pedro; Dias, Ágata; Mata, João; Davis, Donald Wayne; Ribeiro, Maria Luísa (Geoscience Frontiers, 2020)

Anticipare il Futuro della Cina. L’eredità del vescovo gesuita Jin Luxian SJ (“Anticipating the Future of China. The Heritage of the Jesuit Bishop Jin Luxian SJ”) - Rothlin, Stephan (La Civiltà Cattolica, 2020)

Anxious immobilities: an ethnography of coping with contagion (Covid-19) in Macau - Zuev, Dennis; Hannam, Kevin (Mobilities, 2020)
In February 2020, Macau became one of the first regions where the pandemic of coronavirus or Covid-19 affected the totality of social and economic life leading to increased anxieties over movement and distance. Although Macau has had very few actual cases of the virus – 46 in total –and no deaths from it, the Macau government rapidly instituted a lock down. The aim of this article is to reflect on how the social experience of being in lockdown can provide insights into understanding the type of experience or condition that we provisionally term ‘anxious immobility.’ Such a condition is characterized by a total disruption of everyday rhythms and specifically anxious waiting for the normalization of activity while being the subject of biosocial narratives of quarantine and socially responsible. The paper is based upon 3 months of ethnographic research conducted by two researchers based in Macau. We also reflect upon some aspects of the politics of mobilities in the light of disruptions and friction points between Hong Kong, Macau, mainland China, and the rest of the world.

Statistical Forecast of Pollution Episodes in Macao during National Holiday and COVID-19 - Lei, Man Tat; Monjardino, Joana; Mendes, Luisa; Gonçalves, David; Ferreira, Francisco (International Journal of Environmental Research and Public Health, 2020)
Statistical methods such as multiple linear regression (MLR) and classification and regression tree (CART) analysis were used to build prediction models for the levels of pollutant concentrations in Macao using meteorological and air quality historical data to three periods: (i) from 2013 to 2016, (ii) from 2015 to 2018, and (iii) from 2013 to 2018. The variables retained by the models were identical for nitrogen dioxide (NO2), particulate matter (PM10), PM2.5, but not for ozone (O3) Air pollution data from 2019 was used for validation purposes. The model for the 2013 to 2018 period was the one that performed best in prediction of the next-day concentrations levels in 2019, with high coefficient of determination (R2), between predicted and observed daily average concentrations (between 0.78 and 0.89 for all pollutants), and low root mean square error (RMSE), mean absolute error (MAE), and biases (BIAS). To understand if the prediction model was robust to extreme variations in pollutants concentration, a test was performed under the circumstances of a high pollution episode for PM2.5 and O3 during 2019, and the low pollution episode during the period of implementation of the preventive measures for COVID-19 pandemic. Regarding the high pollution episode, the period of the Chinese National Holiday of 2019 was selected, in which high concentration levels were identified for PM2.5 and O3, with peaks of daily concentration exceeding 55 μg/m3 and 400 μg/m3, respectively. The 2013 to 2018 model successfully predicted this high pollution episode with high coefficients of determination (of 0.92 for PM2.5 and 0.82 for O3). The low pollution episode for PM2.5 and O3 was identified during the 2020 COVID-19 pandemic period, with a low record of daily concentration for PM2.5 levels at 2 μg/m3 and O3 levels at 50 μg/m3, respectively. The 2013 to 2018 model successfully predicted the low pollution episode for PM2.5 and O3 with a high coefficient of determination (0.86 and 0.84, respectively). Overall, the results demonstrate that the statistical forecast model is robust and able to correctly reproduce extreme air pollution events of both high and low concentration levels.
Keywords: COVID-19; air pollution; air quality forecast; modelling; national holiday; pollution episodes

The Importance of Readiness for Change, a Leadership Perspective Based on a Case Study in Macau, SAR China - Marques, João; Reis, Joana; Phillips, Jenny O. L.; Diakite, Ansoumane (Journal of Advanced Management Science, 2020)

Reawakening Macanese identity: the impact of Chinese outbound tourism - Lou, Lai-Chu Ivy; Xie, Philip Feifan (Journal of Policy Research in Tourism, Leisure and Events, 2020)
The purpose of this paper examines the potential role of Chinese outbound tourism as a catalyst of change for the Macanese identity. There is an emerging trend to have a new identity amongst Macanese residents to valorize cultural and heritage assets. By using Bourdieu’s concept of habitus, it proposes that the social media space is built to voice concerns of language, place attachment and induced public participation. The study utilizes a mixed method approach comprising a survey for netizens and content analysis of online discussions, in order to fully understand changes due to Chinese outbound tourism.
Keywords: China; Identity; Macau; linguistic sensitivity; place attachment; public participation

Unravelling potentials and limitations of sharing economy in reducing unnecessary consumption: A social science perspective - Lai, Michael K. W.; Ho, Amy P. Y. (Resources, Conservation and Recycling, 2020)
Hyper-consumption in capitalist economies has had a severe impact on the environment that no one can escape. In recent year, there has been a high degree of optimism in sharing economy with regard to coping with the environmental problems caused by consumption. However, most of the current literature focuses on business perspectives in which a sharing economy is portrayed as a new business model, but not as a way to curb environmental degradation. This paper, based on a social science perspective, investigates the potentials and limitations of the strategies adopted in sharing economy projects towards social transformation (especially coping with environmental degradation and hyper-consumption), with the adoption of Erik Olin Wright’s concept of real utopia. A case study approach has been adopted in terms of a sharing economy project named ‘Waste-no-mall (Yuen Long)’ in Hong Kong. The project founder embraces ideological-led strategies based on collective responsibility, self-determination and reflexivity, encouraging the participants to reflect on their consumption behaviours, and thus increasing the level of awareness of the need to reduce unnecessary consumption. However, it is a double-edge sword that limits its impact to those who are active participants, without spreading to others the need for change. It is also limited for their interstitial strategies within the project, and is unable to call for a concrete symbiotic transformation when it comes to policy. The significance of this paper is two-fold. First, it adopts a social science perspective that centres on exploring the proclaimed social implications of sharing economy, an aspect which is under-studied given that most of current studies are from a business perspective; second, it extends Wright’s concept to an operational level by showing an important pathway aiming to solve environmental problems through the simultaneous achievement of both horizontal and vertical balancing strategies, based on Wright’s concept of real utopia.
Keywords: Hong Kong; Mindful consumption; Real utopia; Sharing economy; Social transformation

XRD Identification of Ore Minerals during Cruises: Refinement of Extraction Procedure with Sodium Acetate Buffer - Milinovic, Jelena; Dias, Ágata; Janeiro, Ana I.; Pereira, Manuel F. C.; Martins, Sofia; Petersen, Sven; Barriga, Fernando J. A. S. (Minerals, 2020)
The on-board identification of ore minerals during a cruise is often postponed until long after the cruise is over. During the M127 cruise, 21 cores with deep-seafloor sediments were recovered in the Trans-Atlantic Geotraverse (TAG) field along the Mid Atlantic Ridge (MAR). Sediments were analyzed on-board for physicochemical properties such as lightness (L*), pH and Eh. Selected samples were studied for mineral composition by X-ray powder diffraction (XRD). Based on XRD data, sediment samples were separated into high-, low- and non-carbonated. Removal of carbonates is a common technique in mineralogical studies in which HCl is used as the extraction agent. In the present study, sequential extraction was performed with sodium acetate buffer (pH 5.0) to remove carbonates. The ratio between the highest calcite XRD reflection in the original samples (Iorig) vs its XRD-reflection in samples after their treatment with the buffer (Itreat) was used as a quantitative parameter of calcite removal, as well as to identify minor minerals in carbonated samples (when Iorig/Itreat > 24). It was found that the lightness parameter (L*) showed a positive correlation with calcite XRD reflection in selected TAG samples, and this could be applied to the preliminary on-board determination of extraction steps with acetate buffer (pH 5.0) in carbonated sediment samples. The most abundant minerals detected in carbonated samples were quartz and Al- and Fe-rich clays. Other silicates were also detected (e.g., calcic plagioclase, montmorillonite, nontronite). In non-carbonated samples, Fe oxides and hydroxides (goethite and hematite, respectively) were detected. Pyrite was the dominant hydrothermal mineral and Cu sulfides (chalcopyrite, covellite) and hydrothermal Mn oxides (birnessite and todorokite) were mineral phases identified in few samples, whereas paratacamite was detected in the top 20 cm of the core. The present study demonstrates that portable XRD analysis makes it possible to characterize mineralogy at cored sites, in particular in both low- and high-carbonated samples, before the end of most cruises, thus enabling the quick modification of exploration strategies in light of new information as it becomes available in near-real time.

Group work and cultural characteristics in a Chinese school - Morrison, Keith; Garcia, Alejandro Salcedo; Wong, Sin Teng (Educational Research and Evaluation, 2020)

The scalpel model of educational research - Morrison, Keith; van der Werf, Greetje (Educational Research and Evaluation, 2020)

Multilingual freedom of the press in Macau - Simões, José Manuel; Mayes, Lee ([RMd] RevistaMultidisciplinar, 2020)
There can be no conclusive determining regarding true press freedom in Macau, and perhaps this statement can be applied elsewhere as well. Issues of self-censorship, partisanship, or cultural loyalty exist in cities and countries around the world, and most of the time there is simply no reliable measurement to determine their impact. The Special Administrative Region (SAR) of Macau is separate and distinct from mainland China, but that does not mean that it is entirely without question regarding its freedom of the press, ethical journalistic practices, and interference by non-authorized agencies at the three languages local newspapers.
Keywords: autocensura; ingerência; liberdade de imprensa; partidarismo; práticas éticas

Who has the power? A reflection on teaching drama improvisation with young children - Ho, Ka Lee Carrie (Journal of Early Childhood Research, 2020)
The following study reflects and explores the dynamics of aesthetic experiences within drama improvisations. This arts-based research was carried out in Hong Kong with six Cantonese children who were aged 3?5?years. Data were collected from the video transcripts of five workshops and the researcher?s own research journal. Two significant milieus were observed: switching in-between roles and intuitive creativity is not talkback. I argue that because each of these two milieus provide the foreground for the complex ? and at times contradictory ? nature of children?s aesthetic experiences where Deleuzian power is at play, opportunities arise for both, challenging the traditional adult?child power relations, and in so doing, educators can be able to reconfigure and reconceptualise teaching goals and practices, both generally and specifically, within the context of early childhood education.

Are Work Engaged Employees Perceive Career Success? A Study of Hospitality at Macau - Kuok, A. C. H (Journal of Hospitality, 2020)
This study examined 206 casino dealers in hospitality at Macau to investigate the extent of their subjective career success and work engagement. Casino dealers were work engaged, but their subjective career success was fairly low, with significant difference between them, which indicates they have cognitive dissonance about their jobs. Several personality variables (emotional suppression and work ethic), organizational variables, i.e., organizational socialization (training, understanding, coworker support, future prospects), and distributive justice, were assessed in relation to subjective career success and work engagement. Organizational socialization, work ethic, and distributive justice were positively correlated with and predictors of subjective career success and work engagement; while emotion suppression was negatively correlated with and predictor of work engagement. This study provides evidence of extending the theories of subjective career success and work engagement in Chinese society and hospitality. Also, it identifies factors that could resolve the employees’ cognitive dissonance, and implementations for management were discussed.
Keywords: Subjective career success; emotion suppression; hospitality; human resources; socialization; work engagement

Statistical Forecast Applied to Two Macao Air Monitoring Stations - Lei, M.; Monjardino, J.; Mendes, L.; Gonçalves, D.; Ferreira, F. (IOP Conference Series: Earth and Environmental Science, 2020)
The levels of air pollution in Macao often exceeded the levels recommended by WHO. In order for the population to take precautionary measures and avoid further health risks under high pollutant exposure, it is important to develop a reliable air quality forecast. Statistical models based on multiple regression (MR) analysis were developed successfully for Macao to predict the next day concentrations of PM10, PM2.5, and NO2. All the developed models were statistically significantly valid with a 95% confidence level with high coefficients of determination (from 0.89 to 0.92) for all pollutants. The models utilized meteorological and air quality variables based on five years of historical data, from 2013 to 2017. The data from 2013 to 2016 were used to develop the statistical models and data from 2017 were used for validation purposes. A wide range of meteorological and air quality variables were identified, and only some were selected as significant dependent variables. Meteorological variables were selected from an extensive list of variables, including geopotential height, relative humidity, atmospheric stability, and air temperature at different vertical levels. Air quality variables translate the resilience of the recent past concentrations of each pollutant and usually are maximum and/or the average of latest 24-hour levels. The models were applied in forecasting the next day average daily concentrations for PM10, PM2.5, and NO2 for the air quality monitoring stations. The results are expected to be an operational air quality forecast for Macao.

Inclusive Education Teachers—Strategies of Working Collaboratively With Parents of Children With Special Educational Needs in Macau - Ng, Shun Wing; Kwan, Yee Wan (International Journal of Educational Reform, 2020)
Education for learners with special education needs has become one of the major concerns of education policies in every corner of the world. In Macau, however, the transformation of schools into inclusive environments is reported to be slow because many teachers in Macau have not accepted the key values of inclusive education and possess little knowledge of their responsibilities as inclusive education teachers. Despite being nonempirical, the aim of this article is twofold: to inform inclusive education teachers, especially those in Macau and other developing regions, of the necessary knowledge, skills and strategies of working collaboratively with parents of children with SEN and provide policy makers concerned with practical ideas of designing effective professional development programmes for teachers working in the inclusive environment. The ultimate aim is to ensure that children with SEN benefit from an education process that includes quality learning opportunities.

Design for Classroom Units: A Collaborative Multicultural Studio Development with Chinese Students - Caires, C. S.; Barbosa, A.; Hanyou, W. (International Journal of Educational and Pedagogical Sciences, 2020)
Design for Classroom Units: A Collaborative Multicultural Studio Development with Chinese Students

Evaluation of mathematical models for QRS feature extraction and QRS morphology classification in ECG signals - do Vale Madeiro, João Paulo; Lobo Marques, João Alexandre; Han, Tao; Coury Pedrosa, Roberto (Measurement, 2020)
It is plausible to assume that the component waves in ECG signals constitute a unique human characteristic because morphology and amplitudes of recorded beats are governed by multiple individual factors. According to the best of our knowledge, the issue of automatically classifying different ’identities’ of QRS morphology has not been explored within the literature. This work proposes five alternative mathematical models for representing different QRS morphologies providing the extraction of a set of features related to QRS shape. The technique incorporates mechanisms of combining the mathematical functions Gaussian, Mexican-Hat and Rayleigh probability density function and also a mechanism for clipping the waveform of those functions. The searching for the optimal parameters which minimize the normalized RMS error between each mathematical model and a given QRS search window enables to find an optimal model. Such modeling behaves as a robust alternative for delineating heartbeats, classifying beat morphologies, detecting subtle and anomalous changes, compression of QRS complex windows among others. The validation process evaluates the ability of each model to represent different QRS morphology classes within 159 full ECG signal records from QT database and 584 QRS search windows from MIT-BIH Arrhythmia database. From the experimental results, we rank the winning rates for which each mathematical model best models and also discriminates the most predominant QRS morphologies Rs, rS, RS, qR, qRs, R, rR’s and QS. Furthermore, the average time errors computed for QRS onset and offset locations when using the corresponding winner mathematical models for delineation purposes were, respectively, 12.87±8.5 ms and 1.47±10.06 ms.
Keywords: ECG feature extraction; Mathematical modeling; Morphology classification; QRS complex delineation

Review of Biesta. G. (2020) Educational research: an unorthodox introduction, Educational Research and Evaluation - Morrison, Keith (Educational Research and Evaluation, 2020)

The truth, the whole truth, and nothing but the truth - Morrison, Keith; van der Werf, Greetje (Educational Research and Evaluation, 2020)

Noise-induced hearing loss in zebrafish: investigating structural and functional inner ear damage and recovery - Breitzler, Lukas; Lau, Ieng Hou; Fonseca, Paulo J.; Vasconcelos, Raquel O. (Hearing Research, 2020)
Exposure to continuous moderate noise levels is known to impair the auditory system leading to Noise-Induced Hearing Loss (NIHL) in animals including humans. The mechanism underlying noise-dependent auditory Temporary Threshold Shifts (TTS) is not fully understood. In fact, only limited information is available on vertebrates such as fishes, which share homologous inner ear structures to mammals and have the ability to regenerate hair cells. The zebrafish Danio rerio is a well-established model in hearing research providing an unmatched opportunity to investigate the molecular and physiological mechanisms of NIHL at the sensory receptor level. Here we investigated for the first time the effects of noise exposure on TTS and functional recovery in zebrafish, as well as the associated morphological damage and regeneration of the inner ear saccular hair cells. Adult specimens were exposed for 24h to white noise at various amplitudes (130, 140 and 150 dB re. 1 μPa) and their auditory sensitivity was subsequently measured with the Auditory Evoked Potential (AEP) recording technique. Sensory recovery was tested at different times post-treatment (after 3, 7 and 14 days) and compared to individuals kept under quiet lab conditions. Results revealed noise level-dependent TTS up to 33 dB and increase in response latency. Recovery of hearing function occurred within 7 days for fish exposed to 130 and 140 dB noise levels, while fish subject to 150 dB only returned to baseline thresholds after 14 days. Hearing impairment was accompanied by significant loss of hair cells only at the highest noise treatment. Full regeneration of the sensory tissue (number of hair cell receptors) occurred within 7 days, which was prior to functional recovery. We provide first baseline data of NIHL in zebrafish and validate this species as an effective vertebrate model to investigate the impact of noise exposure on the structure and function of the adult inner ear and its recovery process.
Keywords: Fish; Hair cells; Hearing sensitivity; Noise; Sound pressure level; Temporary threshold shift

Psychometric properties of a Chinese version of the Constructivist Learning Environment Survey among secondary-school students in Hong Kong - Kwan, Yee Wan (Learning Environments Research, 2020)
The study examined the factor structure, reliability and validity of a Chinese version of the Constructivist Learning Environment Survey (C-CLES), an instrument for assessing students’ perceptions of the extent of constructivist approaches prevalent in classrooms. A convenience sample of 967 students in Secondary Three (Grade 9) in Hong Kong participated in this study by completing a self-administered questionnaire in their class time. Exploratory and confirmatory factor analyses supported the hypothesised factor structure, indicating five theoretical constructivist environment dimensions that showed goodness-of-fit to 25 items: Personal Relevance, Uncertainty, Critical Voice, Shared Control, and Student Negotiation. Criterion-related validity, involving evidence based on relations to other variables, was assessed by correlations between the constructivist environment dimensions and cognitive strategies and academic ability. Most correlations were statistically significant and in the positive direction. The C-CLES with 25 items provides a useful measure for educational practice and research among school students.
Keywords: Cognitive outcomes; Constructivist learning environment; Secondary schools; Validation

Health and Well-Being Education: Extending the SCARF Learning Analytics Model for Identifying the Learner Happiness Indicators - Li, Tengyue; Marques, Joao Alexandre Lobo; Fong, Simon (International Journal of Extreme Automation and Connectivity in Healthcare (IJEACH), 2020)
The use of learning analytics (LA) in real-world educational applications is growing very fast as academic institutions realize the positive potential that is possible if LA is integrated in decision making. Education in schools on public health need to evolve in response to the new knowledge and th...

Crowdsensing-Based Gamification for Collective Assistance for Post-Era of Coronavirus Epidemic in Community Living - Luo, Renfei; Marques, João Alexandre Lôbo; Ong, Kok-Leong; Fong, Simon (International Journal of Extreme Automation and Connectivity in Healthcare (IJEACH), 2020)
Crowdsensing exploits the sensing abilities offered by smart phones and users' mobility. Users can mutually help each other as a community with the aid of crowdsensing. The potential of crowdsensing has yet to be fully realized for improving public health. A protocol based on gamification to encoura...

Enhancing Student Learning and Teacher Development: Does “Assessment for Learning” Matter? - Ng, Shun Wing; Kwan, Yee Wan; Huey Lei, Ka Hio (International Journal of Educational Reform, 2020)
This paper aims to report a case study of exploring the effect of ?assessment for learning? on improving student learning and facilitating teachers? professional development in the examination-oriented context of Hong Kong. By adopting Variation Theory of the Lesson Study approach, data were collected through pre- and post-tests, interviews with students and teacher participants and observation field-notes in order to help diagnose students? learning difficulties and provide evidence for teachers to refine their teaching strategies to enhance students? learning effectiveness. The students? improvement in learning performance informed the teacher participants of the usefulness of ?assessment for learning? in the classroom.

Editorial: On Cinema - Ribas, Daniel; Crespo, Nuno; Caires, Carlos Sena (Journal of Science and Technology of the Arts, 2020)
In the past decades, the field of cinema has undergone several transformations. The digital turn increasingly called for new forms of production, distribution, and exhibition, which imply different ways of thinking, doing, and experimenting cinema. These new forms also reduced the gap between cinema to other so-called visual arts. If cinema and visual arts were already in the process of merging, the last years forced the naturalization of thinking in similar theoretical grounds. This special issue aims to be a forum for the discussion of new practices of researching cinema, and the changes in cinema’s forms of experience and production.
Keywords: Art and cinema; Cinema; Contemporary cinema; Digital turn; Visual Arts

Parental stress and parenting in Chinese immigrant families: The mediating role of social support - Liu, Shu-Wen; Zhai, Fuhua; Gao, Qin (Child & Family Social Work, 2020)
Abstract As the population of Chinese immigrants has been growing rapidly in the United States, it has been understudied on the parenting behaviours as well as the roles parental stress and social support playing in parenting in this group. This study investigated whether parental stress was associated with parenting and whether this relationship was mediated by social support in a sample of 255 Chinese immigrant parents from the Survey of Asian American Families in New York City. Regression analyses with a rich array of control variables found that a higher level of parental stress and the presence of one or more stressors such as unemployment, low income, and low education were positively associated with the use of harsh discipline and parent?child conflicts and negatively associated with positive parenting practices. Social support functioned as a significant mediator in the relationships between parental stress and positive parenting practices but not in the relationships of parental stress with parent?child conflict or the use of harsh discipline.
Keywords: Chinese immigrants; harsh discipline; parental stress; parenting practices; parent–child conflict; social support

The Effect of Self-Efficacy and Role Understanding on Teachers’ Emotional Exhaustion and Work Engagement in Inclusive Education in Macao (SAR) - Kuok, A. C. H.; Teixeira, Vitor; Forlin, Chris; Monteiro, Elisa; Correia, Ana (International Journal of Disability, Development and Education, 2020)
This study examined responses from 508 full-time teachers working in inclusive schools in Macao (SAR). The intention was to understand the teachers’ perceptions about their roles and how they responded to inclusive practices in their school. Teachers’ perceived levels of emotional exhaustion and cognitive work engagement were assessed in relation to several professional competencies (self-efficacy with using inclusive instruction, collaborating with parents and paraprofessionals, and managing disruptive behaviours), as well as the organisational variable of role understanding. Regression analysis showed that teachers’ self-efficacy with using inclusive instruction was found to be the most powerful negative predictor of emotional exhaustion; while self-efficacy for managing disruptive behaviours was a positive predictor of teachers’ cognitive work engagement. Teachers’ level of understanding of their role and that of their schools was a negative predictor of emotional exhaustion and a positive predictor of cognitive work engagement. Moreover, it further confirmed that the concept of co-existence between work engagement and burnout can be applied to inclusive teachers. Results were interpreted in relation to management in inclusive schools in Macao and were followed by a discussion on the implications of enhancing inclusive education.

Sulfur isotopic compositions of sulfides along the Southwest Indian Ridge: implications for mineralization in ultramafic rocks - Dias, Ágata; Ding, Teng; Tao, Chunhui; Liang, Jin; Chen, Jie; Wu, Bin; Ma, Dongsheng; Zhang, Rongqing; Wang, Jia; Liao, Shili; Wang, Yuan; Yang, Weifang; et al. (Mineralium Deposita, 2020)

Methods, understandings, and expressions of causality in educational research - Morrison, Keith; van der Werf, Greetje (Educational Research and Evaluation, 2020)

Analysis of reading errors in Portuguese : digraphs and complex syllabic structures - Simões, Edlia; Martins, Margarida Alves (Análise Psicológica, 2020)
Abstract: The Portuguese language poses several challenges for children in the initial phase of learning how to read, particularly in the case of letters that may correspond to more than one phoneme, two letters that correspond to a single phoneme and in the case of words containing complex syllabic structures. The objective of this study was to perform a psycholinguistic analysis of the reading errors of children, attending the 1st (n=175) and 2nd year (n=137) of schooling, specifically in the case of words containing digraphs or complex syllabic structures and to analyse the differences between children’s reading errors in these two years. An oral reading test was used for data collection. A quantitative and qualitative analysis of the type of reading errors was conducted using words with consonant digraphs (ch, nh, lh, gu, rr, ss), and words with complex syllables <CVC and CCV>. This analysis showed that children presented greater difficulties in some specific digraphs and tended to simplify complex syllables, either by adding or deleting phonemes. The quantity and quality of the reading errors of children attending both grades were discussed in light of reading acquisition theories and children’s phonological development.

Mary and Fátima: A Modest C-Inductive Argument for Catholicism - Mcnabb, Tyler Dalton; Blado, Joseph E. (Perichoresis, 2020)
AbstractC-Inductive arguments are arguments that increase the probability of a hypothesis. In this paper, we offer a C-Inductive argument for the Roman Catholic hypothesis. We specifically argue that one would expect the Miracle of Fátima on Roman Catholicism more so than on alternative hypotheses. Since our argument draws on confirmation theory, we first give a primer for how confirmation theory works. We then, provide the historical facts surrounding the Miracle of Fátima. We offer up two competing naturalistic explanations that attempt to explain the historical facts, but then, argue that a supernatural explanation is superior. Having established that something miraculous likely occurred at Fátima, we move to argue for the overall thesis of the paper. Finally, we engage several objections to our argument.

Pandemic (Im)mobilities - Adey, Peter; Hannam, Kevin; Sheller, Mimi; Tyfield, David (Mobilities, 2021)

Post-disaster Temporary Housing System based on Generative Design Method - Afonso, Filipe G.; Lu, Jun C. (International Journal of Structural and Civil Engineering Research, 2021)

Personal Care and Cosmetic Products as a Potential Source of Environmental Contamination by Microplastics in a Densely Populated Asian City - Bashir, Saidu M.; Kimiko, Sam; Mak, Chu-Wa; Fang, James Kar-Hei; Gonçalves, David (Frontiers in Marine Science, 2021)
The prevalence of microplastics in the environment has become a major global conservation issue. One primary source of environmental microplastics is personal care and cosmetic products (PCCPs) containing microbeads. The market availability of PCCPs containing microbeads and the level of contamination of coastal sediments by microplastics was studied in one of the most densely populated cities in the world, Macao in China. We found that PCCPs containing microbeads are still widely available for sale in the region, with over 70% of surveyed PCCPs containing at least one type of microbeads as an ingredient, with polyethylene (PE) being the most common one. In an estimate, the use of PCCPs in the territory may release over 37 billion microbeads per year into the environment via wastewater treatment plants. The density of microplastics in coastal sediments varied between 259 and 1,743 items/L of sediment, amongst the highest reported in the world. The fraction of < 1 mm was the most abundant, representing an average of 98.6% of the total, and correlated positively with the abundance of larger sized fragments. The results show that although environmental pollution with microplastics released from PCCPs usage is significant, other sources, namely fragmentation of larger plastic debris, likely contribute more to the issue. The study highlights the magnitude of the problem at a local level and suggests possible mitigating strategies.

Home–School Collaboration in Assessment, Placement, and Individual Education Plan Development for Children With Special Education Needs in Macao: The Views of Parents - Correia, Ana; Teixeira, Vitor; Forlin, Chris (School Community Journal, 2021)
The aim of this study was to explore home–school collaboration in the areas of assessment, placement, and Individual Education Plan (IEP) development for children identified with disabilities or special educational needs (SEN) in Macao. Despite the noted benefits of parent–school partnerships from prior research, minimal research has been conducted from the perspective of parents of children with SEN to examine whether these partnerships materialize in the context of Macao. Participants included 115 parents of school-aged children diagnosed with SEN. They provided demographic information and completed a 36-item questionnaire derived from two validated instruments. The research identified a range of factors which hinder parental involvement in decision-making and in the inclusion of children with SEN in optimal ways in Macao schools. Parents indicated they were not receiving relevant information and assessment feedback from the teachers; they were minimally involved in the IEP process, and their children were not receiving one-to-one support, regardless of the type of placement. Parents also underlined issues related to the timing of assessment procedures. Parents of children attending special classes in regular schools voiced more satisfaction with support provision than parents of children following the full inclusion model. Recommendations about how services could be improved for greater parental involvement are discussed. Key Words: parental involvement, school–family collaboration, inclusion, special educational needs, Macao, Individual Education Plans, IEP

Aristotle, Lubich And Ratzinger On A New Economic Paradigm - Eh, Edmond (The Journal of the Macau Ricci Institute, 2021)

Ethical Investment’s Visible Hand: Methods And Transformative Potentials - Gassner, Franz (The Journal of the Macau Ricci Institute, 2021)

“To Listen to the Language of Nature and to Act Accordingly” :: Natural Law as Beacon guiding to Human Flourishing and Ecological Civilization - Gassner, Franz (Orientis Aura: Macau Perspectives in Religious Studies, 2021)
The article sets off from a speech given by Benedict XVI in the German Bundestag in 2011, where he requested an ecological learning process to aim at sustainable human development. Appreciating the Ecological Movement, he asked to learn to listen to Nature’s language and act accordingly, which he applies analogically to “human ecology”. The article bridges elements of “Listening to Nature” and the Natural Moral Law Tradition in Benedict’s speech and in Francis’ Encyclical Letter Laudatu Si’ inview of serving human flourishing in an ecological civilization. Keywords: Natural Moral Law; Nature, Laudatu Si’, Benedict XVI, Francis; Ecological Civilization/生態文明, Sustainable Development, Ecology of Man.

Tourist’s mobilities: Walking, cycling, driving and waiting - Hannam, Kevin; Butler, Gareth; Witte, Alexandra; Zuev, Dennis (Tourist Studies, 2021)
This commentary reviews recent research in terms of tourist’s mobilities in terms practices of walking, cycling and driving. It concludes by reflecting on the contemporary lock down of travel in terms of the global pandemic and its consequences for waiting, stillness and immobility – particularly in terms of flying.

A Preliminary Psychometric Investigation of a Chinese Version of the Engaged Teachers Scale (C-ETS) - Ho, Sammy K.; Chan, Hang; Chan, Edmund Sze-Shing; Fung, Kwok-Kin; Hung, Shirley Suet-Lin (Frontiers in Education, 2021)
This study examines the psychometric properties of a Chinese version of the Engaged Teacher Scale (C-ETS). A translated questionnaire with 16 items was administered to a sample of 341 primary and secondary school teachers in Hong Kong. A series of confirmatory factor analyses were performed to assess the construct, convergent, and discriminant validity of the scale in alternative models. Results provide support for a second-order model with teacher engagement as an overarching construct with four hypothesized dimensions: emotional engagement, cognitive engagement, social engagement (students), and social engagement (colleagues). The C-ETS provides a useful measure for teacher engagement in Chinese societies. Contributions and limitations of the study are discussed.

Does Romans 2:14 Refer to the Natural Law? - Leong, Chi Hei (Orientis Aura: Macau Perspectives in Religious Studies, 2021)
Whilst after decades of research, exegetes have all agree on the complexity of Paul’s line of thinking in Rom 2:14–16, the ITC in its 2009 document, In Search of a Universal Ethic, still in an oversimplified manner propagates the view that Rom 2:14 presupposes a theory/theology of the natural law. This article makes plain the major disagreements among Pauline exegetes whether such presupposition stands by reviewing some major contributions to the discussion by raising major questions regarding the issue of φύσει in those verses, the nature of the law mentioned by Paul, the identity of the people Paul calls “Gentiles.” This article offers a more nuanced understanding of Rom 2:14. Keywords: Rom 2:14, ITC, Universal Ethic, Natural Law, φύσει, Gentiles

Papal Bull: A Response to Contemporary Papal Scholarship - McNabb, Tyler Dalton (Journal of Biblical and Theological Studies, 2021)

Ceremonies of the Sarum Missal: A Careful Conjecture by R. J. Urquhart (review) - Morgan, Stephen (Antiphon: A Journal for Liturgical Renewal, 2021)

‘Em Procissão Solene a Deus Orando, para os Batéis Viemos Caminhando’—The Long Ebb-Tide of Catholic Public Piety in the Former-Portuguese Enclave of Macao - Morgan, Stephen (Religions, 2021)
When the City of the Name of God of Macao marked 400 years of Portuguese administration in 1956, the Catholic community’s participation was marked by a wide range of activities that included liturgical celebrations, public processions and other devotions that involved large numbers of the lay faithful, members of confraternities, in addition to the clergy and religious of the enclave. Twenty-one years later the Diocese of Macao celebrated its own quatercentenary with celebrations of a decidedly more sober character and at the retrocession of Macao to Chinese control in December 1999, other than a few liturgical events and hierarchical presence at civic ceremonies, the Church was all but invisible. As the Diocese of Macao plans for its 450th anniversary, some of the former richness has begun to return. This paper outlines the long ebb tide and now-nascent flow of the tide of Catholic public piety in Macao over this period by reference to the Catholic religious processions of the City and seeks to offer tentative explanations grounded in the theological, ecclesial, political and cultural winds that have blown across the Pearl River Delta since the end of the Second World War.
Keywords: Catholic Church; China; Macao; Portugal; Vatican II; confrarias; processions; public piety

The Anglican Patrimony in Catholic Communion ed. by Tracey Rowland (review) - Morgan, Stephen (Antiphon: A Journal for Liturgical Renewal, 2021)

A performance académica como ritual de criação e ativismo na era pós-digital - Pérez, P; Pereira, S; Fernandes-Marcos, A (AVANCA CINEMA, 2021)

Geological Map of the Macao Special Administrative Region (China) - Quelhas, P; Borgens, R; Dias, Ágata; Ribeiro, L; Costa, P; Mata, J (Journal of Maps, 2021)

Geology of the Macao Special Administrative Region (China) - Quelhas, Pedro; Borges, Ricardo; Dias, Ágata Alveirinho; Ribeiro, Maria Luísa; Costa, Pedro; Mata, João (Journal of Maps, 2021)
A 1:12,000 geological map of the Macao Special Administrative Region has been produced through detailed field work supported by petrographic, mineralogical, geochronological and geochemical data obtained in previous studies. This map aims to represent a reliable tool to understand the geological evolution of the region and for management of the territory. The geology of Macao is dominated by two groups of Jurassic granitic rocks belonging to an intrusive suite located along the coast of Southeast China: Macao Group I (MGI: 164.5 ± 0.6 to 162.9 ± 0.7 Ma) and Macao Group II (MGII: 156.6 ± 0.2 to 155.5 ± 0.8 Ma), including the associated microgranite, aplite and pegmatite dikes and quartz veins. Remnants of the metasedimentary wall-rock are present as Devonian xenoliths enclosed within the granites. Younger Jurassic to Cretaceous andesite to dacite dikes (150.6 ± 0.6 to <120 Ma) intrude the granitic rocks. Additionally, Quaternary sedimentary deposits cover the older lithologies.
Keywords: Jurassic; Macao (South China); Mesozoic; geological map; granites; magmatic rocks

Magmatic Evolution of Garnet-Bearing Highly Fractionated Granitic Rocks from Macao, Southeast China: Implications for Granite-Related Mineralization Processes - Quelhas, Pedro; Mata, João; Dias, Ágata (Journal of Earth Science, 2021)
The widespread W-(Mo)-Sn-Nb-Ta polymetallic mineralization in Southeast (SE) China is genetically associated with Mesozoic highly fractionated granitic rocks. Such rocks have enigmatic mineralogical and geochemical features, making its petrogenesis an intensely debated topic. To better understand the underlying magma evolution processes, petrography, garnet chemistry and whole-rock major and trace element data are reported for Jurassic highly fractionated granitic rocks and associated microgranite and aplitepegmatite dikes from Macao and compared with coeval similar granitic rocks from nearby areas in SE China. Despite the fact that the most evolved rocks in Macao are garnet-bearing aplite-pegmatite dikes, the existence of coeval two-mica and garnet-bearing biotite and muscovite granites displaying more evolved compositions (e.g, lower Zr/Hf ratios) indicates that the differentiation sequence reached higher degrees of fractionation at a regional scale. Although crystal fractionation played an important role, late-stage fluid/melt interactions, involving F-rich fluids, imparted specific geochemical characteristics to Macao and SE China highly fractionated granitic rocks such as the non-CHARAC (CHArge-and-RAdius-Controlled) behavior of trace elements, leading, for example, to non-chondritic Zr/Hf ratios, Rare Earth Elements (REE) tetrad effects and Nb-Ta enrichment and fractionation. Such process contributed to the late-stage crystallization of accessory phases only found in these highly evolved facies. Among the latter, two populations of garnet were identified in MGI (Macao Group I) highly fractionated granitic rocks: small grossular-poor euhedral grains and large grossular-rich skeletal garnet grains with quartz inclusions. The first group was mainly formed through precipitation from highly evolved Mn-rich slightly peraluminous melts under low-pressure and relatively low temperature (∼700 °C) conditions. Assimilation of upper crust metasedimentary materials may have contributed as a source of Mn and Al to the formation of garnet. The second group has a metasomatic origin related to the interaction of magmatic fluids with previously crystallized mineral phases and, possibly, with assimilated metasedimentary enclaves or surrounding metasedimentary strata. The highly fractionated granitic rocks in Macao represent the first stage in the development of granite-related W-(Mo)-Sn-Nb-Ta mineralization associated with coeval more evolved lithotypes in SE China.

Triggering a Change of The Economic Paradigm - Rothlin, Stephan (The Journal of the Macau Ricci Institute, 2021)

Physiology, endocrinology and chemical communication in aggressive behaviour of fishes - Silva, Melina Coelho da; Canário, Adelino Vicente Mendonça; Hubbard, Peter Colin; Gonçalves, David (Journal of Fish Biology, 2021)
Fishes show remarkably diverse aggressive behaviour. Aggression is expressed to secure resources; adjusting aggression levels according to context is key to avoid negative consequences for fitness and survival. Nonetheless, despite its importance, the physiological basis of aggression in fishes is still poorly understood. Several reports suggest hormonal modulation of aggression, particularly by androgens, but contradictory studies have been published. Studies exploring the role of chemical communication in aggressive behaviour are also scant, and the pheromones involved remain to be unequivocally characterized. This is surprising as chemical communication is the most ancient form of information exchange and plays a variety of other roles in fishes. Furthermore, the study of chemical communication and aggression is relevant at the evolutionary, ecological and economic levels. A few pioneering studies support the hypothesis that aggressive behaviour, at least in some teleosts, is modulated by “dominance pheromones” that reflect the social status of the sender, but there is little information on the identity of the compounds involved. This review aims to provide a global view of aggressive behaviour in fishes and its underlying physiological mechanisms including the involvement of chemical communication, and discusses the potential use of dominance pheromones to improve fish welfare. Methodological considerations and future research directions are also outlined.

Modelling the barriers that are preventing e-commerce to thrive – a case study from Portugal, international journal of business excellence - Silva, Susana Costa e; Machado, Joana Costa; Martins, Carla; Duarte, Paulo; Marques, João Alexandre Lobo (International Journal of Business Excellence, 2021)
The identification of barriers for e-commerce to thrive in specific countries is a topic of great interest. This work proposes two models to study the barriers to B2C e-commerce adoption in Portugal, highlighting obstacles less exploited by previous research: the impact of offline shopping pleasure and the influence of the distance to shopping malls on online shopping intent. An online survey was conducted based on different constructs. A multivariate OLS hierarchical regression was used to analyse the proposed models regarding the intention to buy online and the number of online purchases. The results revealed that customer satisfaction is a strong predictor of intent to buy online and that perceived product risk remains a barrier to e-commerce. Consumers living in high urbanised areas have more propensity to buy online. Helpful information is provided regarding the impact of context, culture, product, and individual barriers, showing that multichannel strategies are best suited for success.
Keywords: E-commerce barriers; Online shopping; Portugal; Retail

Learning dynamics of kernel-based deep neural networks in manifolds - Wu, Wei; Jing, Xiaoyuan; Du, Wencai; Chen, Guoliang (Science China Information Sciences, 2021)

The Probability Flow in the Stock Market and Spontaneous Symmetry Breaking in Quantum Finance - Arraut, Ivan; Lobo Marques, João Alexandre; Gomes, Sergio (Mathematics, 2021)
The spontaneous symmetry breaking phenomena applied to Quantum Finance considers that the martingale state in the stock market corresponds to a ground (vacuum) state if we express the financial equations in the Hamiltonian form. The original analysis for this phenomena completely ignores the kinetic terms in the neighborhood of the minimal of the potential terms. This is correct in most of the cases. However, when we deal with the martingale condition, it comes out that the kinetic terms can also behave as potential terms and then reproduce a shift on the effective location of the vacuum (martingale). In this paper, we analyze the effective symmetry breaking patterns and the connected vacuum degeneracy for these special circumstances. Within the same scenario, we analyze the connection between the flow of information and the multiplicity of martingale states, providing in this way powerful tools for analyzing the dynamic of the stock markets.
Keywords: Hermiticity; conservation of the information; degenerate vacuum; flow of information; martingale condition; random fluctuations; spontaneous symmetry breaking; vacuum condition

Evidence for mixed contribution of mantle and lower and upper crust to the genesis of Jurassic I-type granites from Macao, SE China - Quelhas, Pedro; Mata, João; Dias, Ágata (GSA Bulletin, 2021)
Abstract Much controversy has occurred in the past few decades regarding the nature of the sources, the petrogenetic processes, and the tectonic regime(s) of the Jurassic magmatism within the Southeast China magmatic belt. This study aims to contribute to the discussion with mineral chemistry, and whole-rock element and Sr-Nd-Hf-Pb isotopic geochemical data from granitic rocks and microgranular mafic enclaves from Macao, where two discrete groups of I-type biotite granites have been identified (referred to as Macao Group I [MGI] and Macao Group II [MGII]). It is proposed that the granitic magmas were generated by partial melting of infracrustal medium- to high-K, basaltic Paleoproterozoic to Mesoproterozoic protoliths (Nd depleted mantle model age [TDM2] = 1.7–1.6 Ga and Hf TDM2 = 1.8–1.6 Ga), triggered by underplating of hot mantle-derived magmas in an extensional setting related to the foundering of a previously flat slab (paleo–Pacific plate) beneath the SE China continent. The main differences between the two groups of Macao granites are attributed to assimilation and fractional crystallization processes, during which upper-crustal Paleozoic metasediments were variably assimilated by MGI magmas. This is evidenced by an increase in initial 87Sr/86Sr ratios with degree of evolution, presence of metasedimentary enclaves, and high percentage of zircon xenocrysts with Paleozoic ages. In addition, other processes like late-stage fluid/melt interaction and magma mixing also left some imprints on granite compositions (rare earth element tetrad effect plus non–charge-and-radius-controlled behavior of trace elements and decoupling between different isotope systems, respectively). The distribution of isotopically distinct granites in SE China reflects the nature of the two Cathaysia crustal blocks juxtaposed along the Zhenghe-Dapu fault.

The Political and Economic Dependence of the Press in Macao under Portuguese and Chinese Rule: Continuity and Change - Costa-Ribeiro, Nelson; Simões, José Manuel (Communication & Society, 2021)
The article analyses the media system in Macao, a special administrative region of China that transitioned from Portuguese to Chinese sovereignty in 1999, becoming one of cities in the world with the largest number of published newspapers per capita. Combining historical research with the analysis of contemporary empirical data collected through interviews with journalists working on the ground, the research demonstrates how there is a long tradition of state control that goes back to the colonial era and that has assumed different forms, ranging from outright censorship to physical intimidation of journalists and economic dependence on the government. Limitations and control strategies imposed on news reporting during the Portuguese administration continue to be practiced today by the Chinese authorities. Even so, journalists operating on the Macao media market tend to overstate the level of freedom they are given, which can be attributed to media outlets being economically dependent on the state. Nevertheless, the level of freedom attributed to the press is today higher than it had been during the colonial period with some critical voices being allowed to reach the media. This needs to be understood in the context of what has been defined as the Chinese safety valve strategy.
Keywords: Censorship; Journalism Practice; Media Systems; Press Freedom; Press Subsidies

COVID-19: Psychological and Psychosocial Impact, Fear, and Passion - Dey, Nilanjan; Mishra, Rishabh; Fong, Simon James; Santosh, K. C.; Tan, Stanna; Crespo, Rubén González (Digital Government: Research and Practice, 2021)

Un nuovo paradigma economico.(“Ideas for a New Economic Paradigm”) - Rothlin, Stephan (La Civiltà Cattolica, 2021)
La crisi del Covid-19 ha evidenziato il disagio e il divario sempre più ampio tra ricchi e poveri. La crisi finanziaria del 2007-2009 era già risuonata come un campanello d'allarme sulla necessità di

An Improved Double Channel Long Short-Term Memory Model for Medical Text Classification - Liang, Shengbin; Chen, Xinan; Ma, Jixin; Du, Wencai; Ma, Huawei (Journal of Healthcare Engineering, 2021)
There are a large number of symptom consultation texts in medical and healthcare Internet communities, and Chinese health segmentation is more complex, which leads to the low accuracy of the existing algorithms for medical text classification. The deep learning model has advantages in extracting abstract features of text effectively. However, for a large number of samples of complex text data, especially for words with ambiguous meanings in the field of Chinese medical diagnosis, the word-level neural network model is insufficient. Therefore, in order to solve the triage and precise treatment of patients, we present an improved Double Channel (DC) mechanism as a significant enhancement to Long Short-Term Memory (LSTM). In this DC mechanism, two channels are used to receive word-level and char-level embedding, respectively, at the same time. Hybrid attention is proposed to combine the current time output with the current time unit state and then using attention to calculate the weight. By calculating the probability distribution of each timestep input data weight, the weight score is obtained, and then weighted summation is performed. At last, the data input by each timestep is subjected to trade-off learning to improve the generalization ability of the model learning. Moreover, we conduct an extensive performance evaluation on two different datasets: cMedQA and Sentiment140. The experimental results show that the DC-LSTM model proposed in this paper has significantly superior accuracy and ROC compared with the basic CNN-LSTM model.

Divine foreknowledge and human free will: Embracing the paradox - DeVito, Michael; McNabb, Tyler Dalton (International Journal for Philosophy of Religion, 2021)

Identification of Latent Risk Clinical Attributes for Children Born Under IUGR Condition Using Machine Learning Techniques - Nguyen Van, Sau; Lobo Marques, J. A.; Biala, T. A.; Li, Ye (Computer Methods and Programs in Biomedicine, 2021)
Background and objective Intrauterine Growth Restriction (IUGR) is a condition in which a fetus does not grow to the expected weight during pregnancy. There are several well documented causes in the literature for this issue, such as maternal disorder, and genetic influences. Nevertheless, besides the risk during pregnancy and labour periods, in a long term perspective, the impact of IUGR condition during the child development is an area of research itself. The main objective of this work is to propose a machine learning solution to identify the most significant features of importance based on physiological, clinical or socioeconomic factors correlated with previous IUGR condition after 10 years of birth. Methods In this work, 41 IUGR (18 male) and 34 Non-IUGR (22 male) children were followed up 9 years after the birth, in average (9.1786 ± 0.6784 years old). A group of machine learning algorithms is proposed to classify children previously identified as born under IUGR condition based on 24-hours monitoring of ECG (Holter) and blood pressure (ABPM), and other clinical and socioeconomic attributes. In additional, an algorithm of relevance determination based on the classifier is also proposed, to determine the level of importance of the considered features. Results The proposed classification solution achieved accuracy up to 94.73%, and better performance than seven state-of-the-art machine learning algorithms. Also, relevant latent factors related to HRV and BP monitoring are proposed, such as: day-time heart rate (day-time HR), day-night systolic blood pressure (day-night SBP), 24-hour standard deviation (SD) of SBP, dropped, morning cortisol creatinine, 24-hour mean of SDs of all NN intervals for each 5 minutes segment (24-hour SDNNi), among others. Conclusion With outstanding accuracy of our proposed solutions, the classification system and the indication of relevant attributes may support medical teams on the clinical monitoring of IUGR children during their childhood development.
Keywords: ABPM (Ambulatory Blood Pressure Monitoring); HRV (Heart Rate Variability); IUGR (Intrauterine Growth Restriction); Machine Learning

Impact of noise on development, physiological stress and behavioural patterns in larval zebrafish - Lara, Rafael A.; Vasconcelos, Raquel O. (Scientific Reports, 2021)
Noise pollution is increasingly present in aquatic ecosystems, causing detrimental effects on growth, physiology and behaviour of organisms. However, limited information exists on how this stressor affects animals in early ontogeny, a critical period for development and establishment of phenotypic traits. We tested the effects of chronic noise exposure to increasing levels (130 and 150 dB re 1 μPa, continuous white noise) and different temporal regimes on larval zebrafish (Danio rerio), an important vertebrate model in ecotoxicology. The acoustic treatments did not affect general development or hatching but higher noise levels led to increased mortality. The cardiac rate, yolk sac consumption and cortisol levels increased significantly with increasing noise level at both 3 and 5 dpf (days post fertilization). Variation in noise temporal patterns (different random noise periods to simulate shipping activity) suggested that the time regime is more important than the total duration of noise exposure to down-regulate physiological stress. Moreover, 5 dpf larvae exposed to 150 dB continuous noise displayed increased dark avoidance in anxiety-related dark/light preference test and impaired spontaneous alternation behaviour. We provide first evidence of noise-induced physiological stress and behavioural disturbance in larval zebrafish, showing that both noise amplitude and timing negatively impact key developmental endpoints in early ontogeny.
Keywords: Embryology; Environmental impact; Freshwater ecology

Malacca Portuguese Creole - Pillai, Stefanie; Baxter, Alan N.; Soh, Wen-Yi (Journal of the International Phonetic Association, 2021)
Malacca Portuguese Creole (MPC) (ISO 639-3; code: mcm), popularly known as Malacca Portuguese or locally as (Papiá) Cristang, belongs to the group of Portuguese-lexified creoles of (South)east Asia, which includes the extinct varieties of Batavia/Tugu (Maurer 2013) and Bidau, East Timor (Baxter 1990), and the moribund variety of Macau (Baxter 2009). MPC has its origins in the Portuguese presence in Malacca, and like the other creoles in this subset, it is genetically related to the Portuguese Creoles of South Asia (Holm 1988, Cardoso, Baxter & Nunes 2012).

Resource estimation of the sulfide-rich deposits of the Yuhuang-1 hydrothermal field on the ultraslow-spreading Southwest Indian Ridge - Yu, Junyu; Tao, Chunhui; Liao, Shili; Dias, Ágata; Liang, Jin; Yang, Weifang; Zhu, Chuanwei (Ore Geology Reviews, 2021)
Seafloor massive sulfide (SMS) deposits are important deep-sea mineral resources expected to occur predominantly on slow- and ultraslow-spreading mid-ocean ridges. Resource estimates are already available for some of the largest SMS deposits on slow-spreading ridges but not on ultraslow-spreading ridges. Based on geological mapping and sampling, this study investigates the distribution and content of sulfide-rich deposits in the Yuhuang-1 hydrothermal field (YHF), located on the ultraslow-spreading Southwest Indian Ridge. The sulfide-rich deposits in the YHF are composed of two areas ∼500 m apart: the southwest sulfide area (SWS) and the northeast sulfide area (NES). We calculated the volume of sulfide-rich mounds in the YHF and arrived at a total accumulation of ∼10.6 × 106 tons, including at least ∼7.5 × 105 tons of copper and zinc and ∼18 tons of gold. Furthermore, considering the coverage of layered hydrothermal sediment mixed with sulfide-rich breccias, which may have underlying massive sulfide deposits, the maximum total mass was estimated at ∼45.1 × 106 tons. This suggests that the YHF is one of the largest SMS deposits worldwide and confirm that ultraslow-spreading ridges have the greatest potential to form large-scale SMS deposits.
Keywords: Resource estimate; Seafloor massive sulfide deposits; Southwest Indian Ridge; Yuhuang-1 hydrothermal field

Can mangroves work as an effective phytoremediation tool for pesticide contamination? An interlinked analysis between surface water, sediments and biota - Ivorra, Lucia; Cardoso, Patricia G.; Chan, Shek Kiu; Cruzeiro, Catarina; Tagulao, Karen Arano (Journal of Cleaner Production, 2021)
Mangroves are a unique group of plants growing along tropical and sub-tropical coastlines, with the ability to remove several types of contaminants such as heavy metals and other persistent organic compounds in coastal waters. However, little attention has been given to the possible role of mangroves in the removal of organochlorinated pesticides (OCPs) from the environment. Used worldwide, these pesticides were banned in the late 80s, withal they can still be quantified in aquatic environments due to their high stability. Moreover, as persistent and lipophilic compounds, OCPs are known for their tendency to bioaccumulate and biomagnify through the food chain, affecting local ecosystems, and potentially human health. This work aimed to investigate the potential benefits of mangrove ecosystems as OCP phytoremediators. For this purpose, a total of seventy-three articles from non-mangrove and mangrove areas around the world were gathered, integrated and re-analysed as a whole. These data include information from four different matrices (water, sediment, benthic fauna and mangrove plants). A common trend of less pesticide contamination in mangrove areas was observed for all the selected matrices. As a complement, average concentrations were discussed considering International Directives, such as the European legislation 2013/39/EU for water policy and the Dutch List together with the International Sediment Quality Guideline, for sediments. Additionally, theoretical risk assessments were also included. Since information regarding OCPs in mangroves ecosystem is very scarce compared to non-mangrove areas, this review provides valuable insights regarding these environments, and the importance of preserving them as a relevant remediation unit.
Keywords: Benthic fauna; Intertidal environments; Organochlorinated pesticides; Persistent organic compounds; Toxicological assessment

Androgens and corticosteroids increase in response to mirror images and interacting conspecifics in males of the Siamese fighting fish Betta splendens - Ramos, Andreia; Alex, Deepa; Cardoso, Sara D.; Gonçalves, David (Hormones and Behavior, 2021)
The role of hormones as modulators of aggressive behavior in fish remains poorly understood. Androgens and corticosteroids, in particular, have been associated with aggressive behavior in fish but it is still not clear if animals adjust the secretion of these hormones to regulate behavior during ongoing fights, in response to fight outcomes in order to adjust aggressive behavior in subsequent fights, or both. With its stereotyped displays and high aggression levels, the Siamese fighting fish Betta splendens is an excellent model to investigate this question. Here, we compared the behavioral and endocrine response of male B. splendens to fights where there is no winner or loser by presenting them with a size-matched live interacting conspecific behind a transparent partition or with a mirror image. The aggressive response started with threat displays that were overall similar in frequency and duration towards both types of stimuli. Fights transitioned to overt attacks and interacting with a live conspecific elicited a higher frequency of attempted bites and head hits, as compared with the mirror image. There was a pronounced increase in plasma androgens (11-ketotestosterone and testosterone) and corticosteroids (cortisol) levels in response to the aggression challenge, independent of stimulus type. Post-fight intra-group levels of these hormones did not correlate with measures of physical activity or aggressive behavior. A linear discriminant analysis including all behavioral and endocrine data was a poor classifier of fish from the conspecific and mirror trials, showing that overall the behavioral and endocrine response to mirror images and conspecifics was similar. The results show that fight resolution is not necessary to induce an evident increase in peripheral levels of androgens and corticosteroids in B. splendens. However, the function of these hormones during present and future aggressive contests remains to be clarified.
Keywords: Aggression; Androgens; Corticosteroids; Live conspecific test; Mirror test

Origin of the Qiyugou gold deposit in the southern margin of the North China Craton: Insights from trace elements of pyrite and mineralogy of Bi-minerals - Wu, Qiang; Zhao, Tai-Ping; Chen, Wei Terry; Gao, Xin-Yu; Meng, Lei; Qiu, Wenhong Johnson (Ore Geology Reviews, 2021)
The Qiyugou gold deposit, located in the Xiong’ ershan area of the North China Craton, contains abundant bismuth-sulfosalts that are closely associated with gold mineralization. Pyrite is the dominant Au-hosted mineral, and has been formed in three generations (Py1, Py2, and Py3). Py1 grains, generally intergrown with milky quartz, are coarse (>1 mm), euhedral in shape, and Au-depleted in composition. In contrast, subhedral Py2 grains, associated with light gray quartz, are medium to coarse (0.2–3 mm) and are enriched in gold that is both invisible and visible. Py3 grains (0.1–0.5 mm), intergrown with abundant sulfide minerals, are relatively fine and Au-depleted. The time-resolved LA-ICP-MS depth profiles of the Py2 grains indicate that invisible gold occurs as either solid solution or nano-particles of native gold and electrum. Visible gold occurs as small blebs in the Py2 grains where inclusions of native bismuth, galenobismutite, lillianite homologs, tetradymite, and galena are also present. In addition, it is common that electrum in microfracture infillings or along grain boundaries of the Py1 and Py2, are intergrown with bismuthinite derivatives, Bi-Cu sulfosalts, emplectite, tetradymite, chalcopyrite, galena, and Py3. Based on textural relationships and mineral assemblages, calculation of physicochemical conditions show that gold was formed in conditions of fTe2 = ~10−11 and fS2 = ~10−11 to 10−12 for Py2, and fTe2 = ~10−9 to 10-11and fS2 = ~10−10 to 10−11 for Py3. We thus proposed that such physicochemical conditions may have triggered the precipitation of Bi melt, and sulfidation driven by cooling or increase in sulfur content results in the transformation of the Au-Bi liquid into a stable assemblage of native gold and bismuthinite. These bismuth minerals are associated with native gold/Au-bearing minerals, indicating that the Au mineralization of the Qiyugou gold deposit might be genetically associated with Bi melt. The present study highlights the role of Bi as important gold scavengers in arsenic-deficient ore-forming fluid.
Keywords: Bi melts scavenging Au; Bismuth minerals; Qiyugou gold deposit; The southern margin of the North China craton; Trace element of pyrite

Elite athletes’ mental well-being and life satisfaction: a study of elite athletes’ resilience and social support from an Asian unrecognisedNational Olympic Committee - Kuok, A. C. H; K. I. Chio, David; C. H. Pun, Alan (Health Psychology Report, 2021)
Introduction This study aimed to investigate elite athletes’ mental well-being, and to ascertain whether the personal factor resilience and the social factor social support can play a role in promoting mental well-being and life satisfaction. In addition, this is one of the first studies to investigate well-being among elite athletes who are from a region belonging to an unrecognised National Olympic Committee and are not eligible to join the Olympic Games. Material and methods Eighty-four full-time elite athletes (37 males, 47 females) with mean age of 22.36 years old participated in this quantitative research study. Formal letters describing the purpose and organiser of the study were sent to the sport entities in Macao asking their permission for the researchers to contact the elite athletes to participate in this study. After gaining the permission, the elite athletes belonging to these entities were approached individually, to inform them of the purpose of the study and receive their consent. Results Regression revealed that emotional support and adaptability of resilience were strong positive predictors of mental well-being. Additionally, mental well-being was found to be a strong positive predictor of life satisfaction. The results reflected that in elite athletes possessing high adaptability and receiving more emotional support could help to maintain their mental well-being. Conclusions Implications (based on the findings) are discussed in order to provide insights for policy makers or coaches how to promote elite athletes’ mental well-being.

Transforming struggling reform implementers into effectual reform agents: Hong Kong preschool teachers’ voices on process drama - Tam, Po Chi; Sun, C. R. (Youth Theatre Journal, 2021)

Post-Digital Fashion: The Evolution and Creation Cycle - Pereira, Selma; Fernandes-Marcos, Adérito (ZoneModa Journal, 2021)
In the face of the Covid-19 pandemic, the fashion industry was surprised and quickly had to adapt to digital media. However, the relationship between fashion and the multiplicity of screens is not new. Fashion emerged and took its first steps with Cinema, in Modernity. Although there are times when these two systems are further apart from each other, the alliance survived. To analyse contemporaneity, we take as main reference the studies of Gilles Lipovetsky, and his reflections on aesthetic capitalism. The fashion system has many Western fields of life, including art and technology. In this article we discuss how this relationship of fashion adapts and develops with aesthetic capitalism and post-digital art while we analyse representative artefacts from/about fashion. We propose to put the recent digital fashion artefacts in dialogue with post-digital aesthetics theories, discussing the blurred boundaries between the digital and the post-digital, and proposing the instantiation of a post-digital creation cycle applied to fashion artefacts.

Acculturative stress and coping among migrant workers: A global mixed-methods systematic review - Liem, Andrian; Renzaho, Andre M. N.; Hannam, Kevin; Lam, Agnes I. F.; Hall, Brian J. (Applied Psychology: Health and Well-Being, 2021)
No existing review has synthesized key questions about acculturation experiences among international migrant workers. This review aimed to explore (1) What are global migrant workers’ experiences with acculturation and acculturative stress? (2) What are acculturative stress coping strategies used by migrant workers? And (3) how effective are these strategies for migrant workers in assisting their acculturation in the host countries? Peer-reviewed and gray literature, without time limitation, were searched in six databases and included if the study: focused on acculturative stress and coping strategies; was conducted with international migrant workers; was published in English; and was empirical. Eleven studies met the inclusion criteria. Three-layered themes of acculturation process and acculturative stress were identified as: individual layer; work-related layer; and social layer. Three key coping strategies were identified: emotion-focused; problem-focused; and appraisal-focused. These coping strategies were used flexibly to increase coping effectiveness and evidence emerged that a particular type of acculturative stress might be solved more effectively by a specific coping strategy. Migrant workers faced numerous challenges in their acculturative process. Understanding this process and their coping strategies could be used in developing research and interventions to improve the well-being of migrant workers.
Keywords: acculturation; cultural adaptation; global mental health; health disparities; healthcare access; migrant health

A network analysis investigation of the comorbidity between sleep dysfunction and PTSD symptomatology among Filipino domestic workers in Macao (SAR) China- ClinicalKey - Wang, Siyuan; Sit, Hao Fong; Garabiles, Melissa R.; Blum, Daniel; Hannam, Kevin; Armour, Chérie; Hall, Brian J. (Journal of Psychiatric Research, 2021)

Houston, Do We Have a Problem?: Extraterrestrial Intelligent Life and Christian Belief - McIntosh, C. A.; McNabb, Tyler Dalton (Philosophia Christi, 2021)
Would the existence of extraterrestrial intelligent life (ETI) conflict in any way with Christian belief? We identify six areas of potential conflict. If there be no conflict in any of these areas—and we argue ultimately there is not—we are confident in declaring that there is no conflict, period. This conclusion underwrites the integrity of theological explorations into the existence of ETI, which has become a topic of increasing interest among theologians in recent years.

Occurrence and remobilization of gold in the Dayingezhuang deposit in Jiaodong, North China Craton: Evidence from textural and geochemical features of pyrite - Yuan, Zhong-Zheng; Li, Zhan-Ke; Li, Jian-Wei; Zhao, Xin-Fu; Wu, Ya-Fei; Xu, Hai-Jun; Sun, Hua-Shan (Ore Geology Reviews, 2021)
The Dayingezhuang gold deposit in the Jiaodong district, eastern margin of the North China Craton is hosted in Mesozoic granitic rocks and consists of quartz-sulfide veins/veinlets and sulfide disseminations in alteration envelopes. Previous studies mainly focused on the geochronology, sources of ore-forming fluids and metals to investigate the ore genesis. However, enrichment mechanism of Au and other associated trace metals remain unclear. In this study, we present detailed textures and in-situ LA-ICP-MS trace-element compositions of different generations of pyrite, as well as EMP analysis of Au-bearing minerals to discuss the occurrence and enrichment mechanism of Au at this deposit. Three generations of pyrite (Py1, Py2 and Py3) formed during three hydrothermal ore stages (I, II, and III) at Dayingezhuang. Py1 occurs as disseminations in sericitic alteration assemblages and is characterized by low Au (mean 0.15 ppm), Ag, As and Te contents. The time-resolved depth-concentration profiles indicate that Au in Py1 mainly occurs as nanoparticles and/or micron-sized inclusions. Py2 can be further divided into the early undeformed Py2a and later Py2b, which is the product of deformed Py2a with different degrees of brittle to plastic deformation and recrystallization. Py2a in pyrite-siderite-quartz veins is relatively enriched in invisible Au (mean 0.41 ppm), Ag, As, and Te compared to Py1, and contains numerous micron-sized Au inclusions. In contrast, Py2b contains lesser invisible Au (0.21 ppm) and host abundant gold minerals along the grain boundaries and microfractures. Py3 in polymetallic sulfide veins has little Au. As a whole, Au in pyrite is positively correlated with Ag and Te, which is consistent with the results of EMP analysis showing the occurrence of Au as electrum, native gold and minor petzite in pyrite. Such evidences show that the deformation and recrystallization of auriferous Py2a potentially caused local remobilization of Au (mainly as micron-sized inclusion Au) via solid-state ductile flow and subsequent reconcentration of Au in microfractures of Py2b. The pyrite deformation and Au remobilization events were suggested to be related to the continuous reactivation of the regional Zhaoping Fault contemporaneous with gold mineralization. Our study highlights the importance of remobilization and reconcentration of Au triggered by syn-ore tectonic activities at Dayingezhuang and possibly other Au deposits in the Jiaodong district.
Keywords: Dayingezhuang; EBSD; Gold remobilization; Jiaodong; Pyrite deformation

International collaboration for mutual benefit: a Southwest China and Southeast United States partnership - Jackson, M. Sebrena; Gardell, Debra Nelson; Williams, Javonda; Tang, Ning; Yang, Fan (China Journal of Social Work, 2021)
China’s return to social work education, after a nearly 35-year absence, opened the door for partnerships like the 2012 China Collaborative partnership between the Council on Social Work Education’s (CSWE) Katherine A. Kendall Institute, the China Association of Social Work Education (CASWE) and the International Association of Schools of Social Work (IASSW). The University of Alabama School of Social Work (UA SSW) was selected to participate in the collaborative and was connected to the Southwest China Region, specifically partnered with Yunnan University. This manuscript will share the strategies used to engage faculty and students from each partnering institution. Data collected by UA SSW over the five-year partnership will be utilised to contribute to the discussion of the extent to which Western knowledge and theory about social work education might usefully be applied to the Chinese context.
Keywords: China collaborative; International social work; University of Alabama; Yunnan University; social work education

Basic Beliefs, the Embryo Rescue Case, and Single-Issue Voting: A Response to Dustin Crummett - McNabb, Tyler; DeVito, Michael (The National Catholic Bioethics Quarterly, 2021)
In this essay, we respond to Dustin Crummett’s argument that one cannot consistently appeal to body count reasoning to justify being a single-issue pro-life voter if one is also committed to the usual response to the embryo rescue case. Specifically, we argue that a modified version of BCR we call BCR* is consistent with the usual response. We then move to address concerns about the relevance of BCR* to Crummett’s original thesis.

An improved ant colony optimization algorithm based on context for tourism route planning - Liang, Shengbin; Jiao, Tongtong; Du, Wencai; Qu, Shenming (PLOS ONE, 2021)
To solve the problem of one-sided pursuit of the shortest distance but ignoring the tourist experience in the process of tourism route planning, an improved ant colony optimization algorithm is proposed for tourism route planning. Contextual information of scenic spots significantly effect people’s choice of tourism destination, so the pheromone update strategy is combined with the contextual information such as weather and comfort degree of the scenic spot in the process of searching the global optimal route, so that the pheromone update tends to the path suitable for tourists. At the same time, in order to avoid falling into local optimization, the sub-path support degree is introduced. The experimental results show that the optimized tourism route has greatly improved the tourist experience, the route distance is shortened by 20.5% and the convergence speed is increased by 21.2% compared with the basic algorithm, which proves that the improved algorithm is notably effective.

The use Robotics in the intervention with children with ASD in Macao: a pilot study with Milo - Teixeira, Vitor; Lai, Michael (Revista Portuguesa de Investigação Educacional, 2021)
Robotics are being used in the intervention with children with Autism Spectrum Disorder (ASD) in many places and already for many years. Many robots were developed and different studies are being made in order to evaluate its effectiveness. “Socially Assistive Robotics” is shown to be effective in different areas mainly in social and emotional development. Milo, a robot developed by a team led by Richard Margolin for the Robots4Autism program (RoboKind, 2020), is one of the robots whose use is reported to be successful. In Macao there is no report of studies or experiences on the use of robots in the intervention with children with ASD. In a collaboration between the Macao Science Centre, the Macao Autism Association (MAA) and the University of Saint Joseph, an exploratory study was developed to understand the applicability of Milo to the work with children with ASD in Macao. The study showed that the robot is able to facilitate social and emotional competences of children with ASD. However, several limitations including language, cultural differences, the inexperienced facilitators and the level of sessions are too simple for the participants to be aware of that may affect the effectiveness of the intervention. It is important to show that the adoption of Milo in Macao for intervening children with ASD can be further implemented, with better practical solutions.

Sediments in the mangrove areas contribute to the removal of endocrine disrupting chemicals in coastal sediments of Macau SAR, China, and harbour microbial communities capable of degrading E2, EE2, BPA and BPS - Moreira, Irina S.; Lebel, Alexandre; Peng, Xianzhi; Castro, Paula M. L.; Gonçalves, David (Biodegradation, 2021)
The occurrence of endocrine disrupting chemicals (EDCs) is a major issue for marine and coastal environments in the proximity of urban areas. The occurrence of EDCs in the Pearl River Delta region is well documented but specific data related to Macao is unavailable. The levels of bisphenol-A (BPA), estrone (E1), 17α-estradiol (αE2), 17β-estradiol (E2), estriol (E3), and 17α-ethynylestradiol (EE2) were measured in sediment samples collected along the coastline of Macao. BPA was found in all 45 collected samples with lower BPA concentrations associated to the presence of mangrove trees. Biodegradation assays were performed to evaluate the capacity of the microbial communities of the surveyed ecosystems to degrade BPA and its analogue BPS. Using sediments collected at a WWTP discharge point as inoculum, at a concentration of 2 mg l−1 complete removal of BPA was observed within 6 days, whereas for the same concentration BPS removal was of 95% after 10 days, which is particularly interesting since this compound is considered recalcitrant to biodegradation and likely to accumulate in the environment. Supplementation with BPA improved the degradation of bisphenol-S (BPS). Aiming at the isolation of EDCs-degrading bacteria, enrichments were established with sediments supplied with BPA, BPS, E2 and EE2, which led to the isolation of a bacterial strain, identified as Rhodoccoccus sp. ED55, able to degrade the four compounds at different extents. The isolated strain represents a valuable candidate for bioremediation of contaminated soils and waters.
Keywords: Biodegradation; Bisphenols; EDCs-degrading bacteria; Endocrine disrupting chemicals (EDCs); Estrogens; Mangrove

Relações entre o pós-digital e o complexo industrial do capitalismo: reformulações sobre a tecnologia como ideologia e lixo digital na arte - Paquete, Hugo; Fernandes-Marcos, Adérito; Bastos, Paulo Bernardino (AVANCA | CINEMA, 2021)
This essay presents a mapping of the historical concepts that contributed to the emergence of post-digital aesthetics and their connections to the concept of post-media in historical terms. It also analyzes the transition from techno-positivism to discourse of resistance against the effects of the capital technological industrial complex and how these advances in technology influence artistic discourses, practices and are the leverage of art and technology which is nothing more than a representation of the aesthetics of capital. Following art and capitalism as an ideology of innovation. Is proposed an unstinting theory about technology, geology, and the importance of these conditions to the post-digital aesthetics in terms of material disponible and conceptual articulation. Producing a reconfiguration of the post-digital conceptual approach as I propose beyond the dysfunctional aesthetics and connected with the concept of radical ecology centered in the usability of electronic garbage and technical obsolescent technologies in the arts.

‘Navigation for an ocean of interminable scepticism’ revisited: John Henry Newman and the place of theology in the university - Morgan, Stephen (International Journal for the Study of the Christian Church, 2021)
The place of theology is under threat in the modern university. It is denied a place, except insofar as it is useful in the training of religious professionals or as a phenomenon in its own right, on the grounds that relate to an unscientific scientism that both makes metaphysical assumptions it itself does not recognise as scientific or denies its own epistemological commitments. This article argues that the notion of education in ‘liberal knowledge’ or ‘universal knowledge’, the idea at the heart of John Henry Newman’s The Idea of a University provides a sufficiently robust counter to these assaults on the place of theology proper in the modern university and that refusing such a place to it undermines the claim of universities to use the name at all. It is precisely the uselessness of theology that guarantees its place in the university committed to universal knowledge and universal enquiry.
Keywords: Derrida; Newman; education; liberal education; religious studies; secularisation; theology; university

Towards an efficient prognostic model for fetal state assessment - Silva Neto, Manuel Gonçalves da; Madeiro, João Paulo do Vale; Marques, João Alexandre Lobo; Gomes, Danielo G. (Measurement, 2021)
Monitoring signals such as fetal heart rate (FHR) are important indicators of fetal well-being. Computer-assisted analysis of FHR patterns has been successfully used as a decision support tool. However, the absence of a gold standard for the building blocks decision-making in the systems design process impairs the development of new solutions. Here we propose a prognostic model based on advanced signal processing techniques and machine learning algorithms for the fetal state assessment within a comprehensive evaluation process. Feature-engineering-based and time-series-based machine learning classifiers were modeled into three data segmentation schemas for CTU-UHB, HUFA, and DB-TRIUM datasets and the generalization performance was assessed by a two-way cross-dataset evaluation. It has been shown that the feature-based algorithms outperformed the time-series ones on data-limited scenarios. The Support Vector Machines (SVM) obtained the best results on the datasets individually: specificity (85.6% ) and sensitivity (67.5%). On the other hand, the most effective generalization results were achieved by the Multi-layer perceptron (MLP) with a specificity of 71.6% and sensitivity of 61.7%. The overall process provided a combination of techniques and methods that increased the final prognostic model performance, achieving relevant results and requiring a smaller amount of data when compared to the state-of-the-art fetal status assessment solutions.
Keywords: Cardiotocography; Classification; Fetal state assessment; Prognostic model; System design

Constraints of Fe-S-C stable isotopes on hydrothermal and microbial activities during formation of sediment-hosted stratiform sulfide deposits - Qiu, Wenhong Johnson; Zhou, Mei-Fu; Li, Xiaochun; Huang, Fang; Malpas, John (Geochimica et Cosmochimica Acta, 2021)
Microbial and hydrothermal venting activities on the seafloor are important for the formation of sediment-hosted stratiform sulfide (SHSS) deposits. Fe isotopic compositions are sensitive to both microbial and hydrothermal activities and may be used to investigate the formation of these deposits. However, to the best of our knowledge, no Fe isotopic studies have been conducted on SHSS deposits. In the Devonian Dajiangping SHSS-type pyrite deposit (389 Ma), South China, laminated pyrite ores were precipitated from exhalative hydrothermal fluids, whereas black shales were deposited during intervals with no exhalation. Pyrite grains from black shales mostly display positive δ56Fe-py (0.01–0.73‰), higher than marine sediments (ca. 0‰), due to pyrite deriving Fe from basinal shuttled Fe(III) (hydr-)oxides and slowly crystallizing in pores of sediments with equilibrium fractionation, except for negative δ56Fe-py (−0.17‰ to −0.24‰) of two samples caused by mixing of Fe from underlain laminated ores. The positive δ34S-py (3.50–24.5‰) of black shales reflect that sulfur of pyrite originated from quantitative reduction of sulfate in closed pores of sediments. In contrast, pyrite grains of laminated ores have negative δ56Fe-py (−0.60‰ to −0.21‰), which were not only inherited from the negative δ56Fe of hydrothermal fluids but also caused by kinetic fractionation during rapid precipitation of a pyrite precursor (FeS) in hydrothermal plumes. These ores have negative δ34S-py (−28.7‰ to −1.82‰), because H2S for pyrite mineralization was produced by bacterial sulfate reduction (BSR) in a sulfate-rich seawater column or shallow sediments. The δ56Fe-py values of laminated ores co-vary positively with δ34S-py and δ13C-carbonate along the ore stratigraphy, with δ13C-carbonate values ranging from −12.0‰ to −2.50‰. However, they correlate negatively with aluminum-normalized total organic carbon (TOC/Al2O3). Organic carbon is thus considered to enhance the production of H2S by BSR activities, increase pyrite precipitation rates and promote the expression of kinetic fractionation of Fe isotopes. Intriguingly, in the ore units with vigorous hydrothermal venting activities, δ56Fe-py, δ34S-py and δ13C-carbonate values display a consistently increasing trend. Such results suggest that venting hydrothermal fluids significantly inhibited the H2S production of BSR, which then reduced the pyrite crystallization rate and decreased the kinetic fractionation of Fe isotopes. Our study reveals that the formation of SHSS deposits relies on H2S from microbial activities and metals from hydrothermal exhalation on the seafloor, but that vigorous exhalation can inhibit microbial activities and thus sulfide precipitation rates. The integrated use of Fe, S, and C isotopes can effectively elucidate these dynamic interactions between hydrothermal venting and microbial activities during the formation of SHSS deposits.
Keywords: Iron isotope; Isotope fractionation; Sediment-hosted stratiform sulfide deposit; Sulfur isotope

Chemical toxicity prediction based on semi-supervised learning and graph convolutional neural network - Chen, Jiarui; Si, Yain-Whar; Un, Chon-Wai; Siu, Shirley W. I. (Journal of Cheminformatics, 2021)
As safety is one of the most important properties of drugs, chemical toxicology prediction has received increasing attentions in the drug discovery research. Traditionally, researchers rely on in vitro and in vivo experiments to test the toxicity of chemical compounds. However, not only are these experiments time consuming and costly, but experiments that involve animal testing are increasingly subject to ethical concerns. While traditional machine learning (ML) methods have been used in the field with some success, the limited availability of annotated toxicity data is the major hurdle for further improving model performance. Inspired by the success of semi-supervised learning (SSL) algorithms, we propose a Graph Convolution Neural Network (GCN) to predict chemical toxicity and trained the network by the Mean Teacher (MT) SSL algorithm. Using the Tox21 data, our optimal SSL-GCN models for predicting the twelve toxicological endpoints achieve an average ROC-AUC score of 0.757 in the test set, which is a 6% improvement over GCN models trained by supervised learning and conventional ML methods. Our SSL-GCN models also exhibit superior performance when compared to models constructed using the built-in DeepChem ML methods. This study demonstrates that SSL can increase the prediction power of models by learning from unannotated data. The optimal unannotated to annotated data ratio ranges between 1:1 and 4:1. This study demonstrates the success of SSL in chemical toxicity prediction; the same technique is expected to be beneficial to other chemical property prediction tasks by utilizing existing large chemical databases. Our optimal model SSL-GCN is hosted on an online server accessible through: https://app.cbbio.online/ssl-gcn/home.
Keywords: ADMET; Chemical toxicity; Deep learning; Graph convolutional neural network; Mean teacher; Semi-supervised learning; Tox21

IoT-Based Smart Health System for Ambulatory Maternal and Fetal Monitoring - Marques, João Alexandre Lobo; Han, Tao; Wu, Wanqing; Madeiro, João Paulo do Vale; Neto, Aloísio Vieira Lira; Gravina, Raffaele; Fortino, Giancarlo; de Albuquerque, Victor Hugo C. (IEEE Internet of Things Journal, 2021)
The adoption of IoT for smart health applications is a relevant tool for distributed and intelligent automatic diagnostic systems. This work proposes the development of an integrated solution to monitor maternal and fetal signals for high-risk pregnancies based on IoT sensors, feature extraction based on data analytics, and an intelligent diagnostic aid system based on a 1-D convolutional neural network (CNN) classifier. The fetal heart rate and a group of maternal clinical indicators, such as the uterine tonus activity, blood pressure, heart rate, temperature, and oxygen saturation are monitored. Multiple data sources generate a significant amount of data in different formats and rates. An emergency diagnostic subsystem is proposed based on a fog computing layer and the best accuracy was 92.59% for both maternal and fetal emergency. A smart health analytics system is proposed for multiple feature extraction and the calculation of linear and nonlinear measures. Finally, a classification technique is proposed as a prediction system for maternal, fetal, and simultaneous health status classification, considering six possible outputs. Different classifiers are evaluated and a proposed CNN presented the best results, with the F1-score ranging from 0.74 to 0.91. The results are validated based on the diagnosis provided by two specialists. The results show that the proposed system is a viable solution for maternal and fetal ambulatory monitoring based on IoT.
Keywords: Artificial intelligence (AI); Biomedical monitoring; Cloud computing; Feature extraction; Fetal heart rate; Internet of Things; Medical diagnostic imaging; Monitoring; convolutional neural networks (CNNs); feature extraction; fetal monitoring; health analytics; maternal monitoring

Data Augmentation for Deep Neural Networks Model in EEG Classification Task: A Review - He, Chao; Liu, Jialu; Zhu, Yuesheng; Du, Wencai (Frontiers in Human Neuroscience, 2021)
Classification of electroencephalogram (EEG) is a key approach to measure the rhythmic oscillations of neural activity, which is one of the core technologies of brain-computer interface systems (BCIs). However, extraction of the features from non-linear and non-stationary EEG signals is still a challenging task in current algorithms. With the development of artificial intelligence, various advanced algorithms have been proposed for signal classification in recent years. Among them, deep neural networks (DNNs) have become the most attractive type of method due to their end-to-end structure and powerful ability of automatic feature extraction. However, it is difficult to collect large-scale datasets in practical applications of BCIs, which may lead to overfitting or weak generalizability of the classifier. To address these issues, a promising technique has been proposed to improve the performance of the decoding model based on data augmentation (DA). In this article, we investigate recent studies and development of various DA strategies for EEG classification based on DNNs. The review consists of three parts: what kind of paradigms of EEG-based on BCIs are used, what types of DA methods are adopted to improve the DNN models, and what kind of accuracy can be obtained. Our survey summarizes the current practices and performance outcomes that aim to promote or guide the deployment of DA to EEG classification in future research and development.

Power Allocation for 5G Mobile Multiuser Cooperative Networks - Yin, Fagen; Du, Wencai (Journal of Advanced Transportation, 2021)
With the fifth generation (5G) communication technology, the mobile multiuser networks have developed rapidly. In this paper, the performance analysis of mobile multiuser networks which utilize decode-and-forward (DF) relaying is considered. We derive novel outage probability (OP) expressions. To improve the OP performance, we study the power allocation optimization problem. To solve the optimization problem, we propose an intelligent power allocation optimization algorithm based on grey wolf optimization (GWO). We compare the proposed GWO approach with three existing algorithms. The experimental results reveal that the proposed GWO algorithm can achieve a smaller OP, thus improving system efficiency. Also, compared with other channel models, the OP values of the 2-Rayleigh model are increased by 81.2% and 66.6%, respectively.

To follow or overcome our nature? - Cai, Yulin (GREGORIANUM, 2022)
The doctrine of original sin gives people the impression that the goodness of human nature is under-evaluated in the Christian theological tradition. The Chinese philosopher Mencius is famous for his teaching on the goodness of human nature. Reading Mencius and Thomas Aquinas side by side, this article argues that the Mencian teaching on human nature brings us to affirm the goodness of human nature by recovering the significance of the image of God for the Christian doctrine of human nature. If we seek the goodness of human nature in the possibilities to become good, it is natural to see that even in the fallen state the possibilities of becoming like God remain in human nature imprinted with the image of God. It is open to the culmination of a gradual progression to its perfection.

CCAAT/Enhancer-Binding Protein Alpha Is a Novel Regulator of Vascular Smooth Muscle Cell Osteochondrogenic Transition and Vascular Calcification - Chen, Pengyuan; Hong, Wanzi; Chen, Ziying; Gordillo-Martinez, Flora; Wang, Siying; Fan, Hualin; Liu, Yuanhui; Dai, Yining; Wang, Bo; Jiang, Lei; Yu, Hongjiao; He, PengCheng (Frontiers in Physiology, 2022)
AimsVascular calcification is a common clinical complication of chronic kidney disease (CKD), atherosclerosis (AS), and diabetes, which is associated with increased cardiovascular morbidity and mortality in patients. The transdifferentiation of vascular smooth muscle cells (VSMCs) to an osteochondrogenic phenotype is a crucial step during vascular calcification. The transcription factor CCAAT/enhancer-binding protein alpha (C/EBPα) plays an important role in regulating cell proliferation and differentiation, but whether it regulates the calcification of arteries and VSMCs remains unclear. Therefore, this study aims to understand the role of C/EBPα in the regulation of vascular calcification.Methods and ResultsBoth mRNA and protein expression levels of C/EBPα were significantly increased in calcified arteries from mice treated with a high dose of vitamin D3 (vD3). Upregulation of C/EBPα was also observed in the high phosphate- and calcium-induced VSMC calcification process. The siRNA-mediated knockdown of C/EBPα significantly attenuated VSMC calcification in vitro. Moreover, C/EBPα depletion in VSMCs significantly reduced the mRNA expression of the osteochondrogenic genes, e.g., sex-determining region Y-box 9 (Sox9). C/EBPα overexpression can induce SOX9 overexpression. Similar changes in the protein expression of SOX9 were also observed in VSMCs after C/EBPα depletion or overexpression. In addition, silencing of Sox9 expression significantly inhibited the phosphate- and calcium-induced VSMC calcification in vitro.ConclusionFindings in this study indicate that C/EBPα is a key regulator of the osteochondrogenic transdifferentiation of VSMCs and vascular calcification, which may represent a novel therapeutic target for vascular calcification.

Exploring the participation and agency of students with special education needs in a Macau-Chinese secondary school - Correia, Ana M.; Forlin, Chris; Sio, Eva (Journal of Research in Special Educational Needs, 2022)
The research explores the perceptions of five secondary school students with special education needs (SEN) about their participation in learning, group membership, and agency within an inclusive school in Macau SAR. This goal is achieved by using students' voices documented in open-ended interviews and is underpinned by the conceptual framework of heutagogy. The aim is to shed light on students' perceptions on school effectiveness in supporting their needs through successful participation and agentic possibilities. Findings showed that students were more prone to social rejection and being isolated or bullied than their peers. They were struggling to feel included or participate, their needs were only partially being met, and they had few opportunities to exert influence on their educational trajectories. Recommendations are provided to assist educators and schools in enhancing students with SEN to connect to the learning process and community, with the provision of appropriate learning adjustments and more active approaches to ensure their acceptance by mainstream students, including the formation of coaching peers to assist in developing social and academic skills under teacher's scaffolding practices. This study highlights the contribution of the heutagogical perspective to advance research on the participation and agency of students with SEN in mainstream schools.
Keywords: Macau SAR; Special education needs; agency; disability; inclusive education; participation; students' voice

Religious Vows in their Mystic and Prophetic Dimensions - Gallares, Judette (Religious Life Asia, 2022)

Learning God’s Mercy: Spiritual Transformation According to Hos 11:8 - Gassner, Franz (The Journal of the Macau Ricci Institute, 2022)
A growing focus on God’s mercy and forgiveness emerged in the wake of the recent Pontificates of John Paul II, Benedict XVI, and Francis. Our time with its multiple crises cries for healing, forgiveness, and the experience of God’s mercy. In social, political, and global terms, humanity craves for “lasting peace, born of the marriage of justice and mercy” (John Paul II, 2001, no. 15). The experience of God’s forgiveness, merciful healing and new life has been expressed many times in the Bible. But, theologically, it has never been formulated as directly as in Hosea 11:8, when God’s own heart becomes “turned over”, “converted” following the blaze of his own overwhelming compassion, paving the way for a fundamental spiritual transformation, rooted in forgiveness and mercy, that opens wellsprings of dignity, healing, and new life for all.

The Influence of Society on the Behavioral Intention to Use a Technology: Evidence from the Battery Electric Vehicles Domain - Lampo, Alessandro; Silva, Susana C.; Duarte, Paulo (International Journal of Business Excellence, 2022)

An exploration of building up the quality of parent-child relationship in residential childcare in Macao - Leong, On Na Ribeiro; Liu, Shu-Wen (Asian Social Work and Policy Review, 2022)

Message from Program Chairs - Ma, J.; Du, W.; Lu, W. (Proceedings - 2022 IEEE/ACIS 22nd International Conference on Computer and Information Science, ICIS 2022, 2022)

Climate Alarmism or Lukewarming? How So-Called American Conservatives Should Think About Climate Change - McNabb, T. D; Devito, M (Ethics & the Environment, 2022)
In this essay we argue that, based on current scientific data, the most prudential course of future actions that an American conservative can take, is one that assumes what we call climate change alarmism. In order to establish this thesis, we first provide a basic overview of the relevant climate change science, as well as give an analysis of the alarmist and lukewarming dialectic (the two primary interpretations of the data). We then move to develop our environmental wager. Finally, following Roger Scruton, we end this work by proposing what sort of policies conservatives should endorse going further.

Cognitive Science of Religion and Classical Theism: A Synthesis - McNabb, Tyler Dalton; DeVito, Michael (Religions, 2022)
Launonen and Mullins argue that if Classical Theism is true, human cognition is likely not theism-tracking, at least, given what we know from cognitive science of religion. In this essay, we develop a model for how classical theists can make sense of the findings from cognitive science, without abandoning their Classical Theist commitments. We also provide an argument for how our model aligns well with the Christian doctrine of general revelation.

Going to Church in Medieval England by Nicholas Orme (review) - Morgan, Stephen (Antiphon: A Journal for Liturgical Renewal, 2022)

The Fire “Once Kindled on Moriah”: Wojtyła and Newman on the Conditions for the Proposal of Christ - Morgan, Stephen (Newman Studies Journal, 2022)

The Emergence of Resources Seeking Chinese Firms’ Specific Advantages in Emerging Market - Ojo, Olukayode Iwaloye; Im, Hong Kei; Adeniyi, Damilola Olarewaju; Gbadamosi, Ayantunji; Alves, Jose; Link to external site, this link will open in a new window; Trimarchi, Michael (Sustainability, 2022)
It is argued that the role of the Chinese government to support the cross-border operations of Chinese firms is to assist these firms in overcoming their limited established brands, and their disadvantages in technology and managerial resources, which were also the reasons why such firms decided to enter emerging markets instead of developed markets. This strategic choice is preferred to avoid direct confrontation with established firms from developed countries endowed with superior ownership advantages. Therefore, Chinese resources seeking firms innovate by increasing investment in developing and emerging markets to develop unique ownership advantages for sustainable market development and competitive advantage. This research investigates the ownership advantages of resources seeking Chinese firms in these markets using the OLI theory. The paper contributes to explaining the specific advantages of Chinese MNEs when entering emerging markets. The study applied a two-stage qualitative methodology to examine Chinese firms operating in Nigeria. The first stage included an exploratory study based on interviews with key informants and experts while the second stage included a case study methodology. The study focused on resources seeking Chinese MNEs operating in Nigeria.
Keywords: OLI theory and Chinese firms; emerging markets; ownership advantages; resources seeking MNEs

Selection for winners impacts the endocrine system in the Siamese fighting fish - Ramos, A.; Gonçalves, D. (General and Comparative Endocrinology, 2022)
In southeast Asia, males of the Siamese fighting fish, Betta splendens, have been selected across centuries for winning paired staged fights and previous work has shown that males from fighter strains are more aggressive than wild-types. This strong directional selection for winners is likely to have targeted aggression-related endocrine systems, and a comparison between fighter and wild-type strains can bring into evidence the key hormones implicated in aggression. Here, we compared the plasma levels of the androgen 11-ketotestosterone (KT) and of the corticosteroid cortisol (F) in F2 males of a fighter and a wild-type strain raised under similar laboratory conditions. We show that F was generally lower in fighter as compared with wild-type males, while no overall differences in KT levels were detected between strains. When presented with a mirror-induced aggressive challenge, post-fight levels of F increased but more significantly so in wild-type males, while KT increased in males of both strains. After the challenge, fighter males had higher levels of KT as compared with wild-type males, while the pattern for F was opposite. As compared with animals in social groups, wild-type males placed under social isolation had lower F levels, while KT decreased for fighters. Taken together, this data suggests that while wild-type males responded to aggression with an increase in circulating levels of both androgens and corticosteroids, males selected for winning fights maintained a blunt F response, increasing only KT levels. These data agree with the hypothesis that a combination of high levels of androgens and low levels of corticosteroids is associated with high aggression. Overall, these results seem to indicate that selection for winning had a stronger impact in the hypothalamus-pituitary-interrenal axis than in the hypothalamus-pituitary–gonadal axis in B. splendens.

Mangrove Conservation in Macao SAR, China: The Role of Environmental Education among School Students - Tagulao, Karen Araño; Bernardo, Allan B. I.; Kei, Loi Hoi; Calheiros, Cristina Sousa Coutinho (International Journal of Environmental Research and Public Health, 2022)
Mangrove forests are one of the most ecologically valuable ecosystems in the world and provide a wide variety of ecosystem services to coastal communities, including cities. Macao, a highly urbanized coastal city located on the southern coast of China west of the Pearl River, is home to several species of mangroves with many associated flora and fauna. Mangrove forests in Macao are vulnerable to threats due to pressure from rapid and massive urban developments in the area, which led to mangrove loss in the past decades. To address this issue, the local authorities established special Ecological Zones for the management of the local mangroves. To reinforce local conservation efforts, educating the local population about the value of mangroves, especially school students, is of utmost importance. To evaluate the impact of environmental education activities on the environmental orientation, knowledge, and values of students toward mangrove conservation in Macao, a quasi-experimental study was undertaken. The effectiveness of a mangroves exhibition and field visit were evaluated using the New Environmental Paradigm (NEP) Scale—Macao version in a group of local school students who participated in the activities. Overall, the results provided consistently positive evaluations of the impact of the environmental education program. The strongest improvements were found in the students’ pro-environmental orientations, knowledge about mangroves, and value for environmental protection.
Keywords: NEP-New Ecological Paradigm; conservation; environmental orientation; environmental protection; urban mangroves

An Integrated Learning Platform Focusing on STEAM and Collaborative Modules for Macau - Cheng, Un Man; Martins de Abreu, F. (International Journal of Creative Interfaces and Computer Graphics (IJCICG), 2022)
In Macau, the effectiveness of traditional classroom learning is questioned as the problem is discovered by the changes in technology advances, social media, and the varieties of learning methods. Learning experiences, interests, discoveries, and creativity development are considered essential to ac...

Trace-element compositions of sulfides from inactive Tianzuo hydrothermal field, Southwest Indian Ridge: Implications for ultramafic rocks hosting mineralization - Ding, Teng; Wang, Jia; Tao, Chunhui; Dias, Ágata Alveirinho; Liang, Jin; Wang, Yuan; Chen, Jie; Wu, Bin; Huang, Hui (Ore Geology Reviews, 2022)
The recently explored inactive Tianzuo hydrothermal field, in the amagmatic segment of the ultraslow-spreading Southwest Indian Ridge (SWIR), is closely associated with detachment faults. In this site, sulfide minerals are hosted by serpentine-bearing ultramafic rocks and include high-temperature (isocubanite, sphalerite, and minor pyrrhotite) and low-temperature (pyrite I, marcasite, pyrite II, and covellite) phases. In this study, trace-element concentrations of isocubanite and pyrite II were used to elucidate mineralization processes in ultramafic rocks hosting sulfides. Results show that isocubanite is enriched in metals such as Cu, Co, Sn, Te, Zn, Se, Pb, Bi, Cd, Ag, In, and Mn, and pyrite II is enriched in Mo and Tl. The marked enrichment in Te, Cu, Co, and In in isocubanite (compared with Se, Zn, Ni, and Sn, respectively) is most likely due to the contribution of magmatic fluids from gabbroic intrusions beneath the hydrothermal field. The intrusion of gabbroic magmas would have enhanced serpentinization reactions and provided a relatively oxidizing environment through the dissolution of anhydrite precipitated previously in the reaction zone, within high temperature and low pH conditions. This might have facilitated the extraction of metals by initial hydrothermal fluids, leading to the general enrichment of most metals in isocubanite. Metals in pyrite II have compositions similar to those of isocubanite, except for strong depletion in magmatically derived Te, Cu, Co, and In. This means that serpentinization processes had a dominating role in pyrite II precipitation as well. The enrichment of pyrite II in Mo and Tl is also indicative of seawater contribution in its composition. The study concludes that serpentinization reactions contribute effectively both to high- and low-temperature sulfide mineralization at Tianzuo hydrothermal field, with gabbroic intrusions further promoting high-temperature sulfide mineralization, providing additional metals, fluids and heat. In contrast, low-temperature sulfide mineralization occurred during the cooling of gabbroic intrusions, with decreasing rates of serpentinization reactions and a significant influence of seawater.
Keywords: SWIR; Serpentinization; Sulfide; Tianzuo; Trace-element; Ultramafic rocks

Design Explorations for 3D-Printed Modular Markers for eXtended-Reality Tangible User Interfaces: - Iok Fong, Chau; Cardoso, Jorge C. S.; Estadieu, Gerald Vincent (International Journal of Creative Interfaces and Computer Graphics, 2022)
Various materials, objects, and sensors have been explored earlier for creating tangible user interfaces (TUIs). However, there is little work on 3D-printed TUIs based on visual markers for smartphone-based extended reality (XR) experiences. The combination of visual markers and smartphones results in cheap, accessible XR systems within reach of many people. Combined with 3D printing, it could foster do-it-yourself (DIY) projects for XR experiences, which may further expand and open-up possibilities for accessible and tangible interaction. This work explores the design space of modular 3D-printed tangibles for smartphone-based XR. The authors report the design exploration process, provide several interactive 3D-printed markers, and reflect on the resulting possibilities.

Quality of life during the pandemic: a cross sectional study about attitude, individual perspective and behavior change affecting general population in daily life - Khatoon, F.; Kumar, M.; Khalid, A. A.; Alshammari, A. D.; Khan, F.; Alshammari, R. D.; Balouch, Z.; Verma, D.; Mishra, P.; Abotaleb, M.; Makarovskikh, T.; El-kenawy, E. M.; et al. (2022)
Quality of life in general population before and during pandemic is topic need to be address by researcher in terms of mobility, self-care, usual activities, pain/discomfort and anxiety/depression. The study was carried out among Saudi population. Data were collected from general population using questionnaire during the period from 22 August 2021 to 10th January 2022. As a result, total 214 participants have included in this study. Among them prevalent age group include 40 years (n= 63, 29.4%) shadowed by the age group 25-35 (n= 61, 28.5%) while above 60 years group were least frequent (n= 1, 0.5%). On questioning the applicants whether they were satisfied with their health and how would they rate their quality of life, their answers were as follows: yes, or satisfied (n= 86, 40.2%), very Satisfied (n= 102, 47.7%) Dissatisfied (n= 11, 5.1%) and neither satisfied nor dissatisfied (n= 15, 7%). Due to pandemic, they were rate quality of life very good (n= 94, 43.9%), good (n= 63, 29.4 %) poor (n= 5, 2.3 %) and neither good and nor poor (n= 52, 24.3 %). During pandemic 96 participants feel no change in their weight but 110 participants respond that there is increase in coffee intake during the pandemic. Similarly increased in smoking habits and decrease rate in social activities (n=119,41.4%). The psychosomatic well-being of people has been interrupted by disturbing their social activities during pandemic.

An Attempt to Examine Digital Native and Digital Immigrant Macau Graphic Designers' Perceptions of Adopting Generative Design - Lau, Ching Man; Caires, Carlos Sena (International Journal of Creative Interfaces and Computer Graphics (IJCICG), 2022)
The manifestation of generating digital visuals through an algorithm is gaining worldwide attention in the graphic design industry. It is a new form of computing that visualizes data input by the designer or collected in the physical environment and turns them into artwork. The generative design of...

Multimodal Game Design Framework for Creativity in Macau's Educational System Through Digital and Tangible Games: Chinese, Portuguese, and English Languages - Martins de Abreu, F.; Barbosa, Álvaro Mendes (International Journal of Creative Interfaces and Computer Graphics (IJCICG), 2022)
Creativity and collaboration are crucial to learning development in today's fast-paced educational environment. New technology can bridge humans and their natural needs through immersion in digital environments with physical objects. As knowledge and information evolve, digital interactive experienc...

In Memorial and Serenity: Introducing VR Grave Mourning in the Chapel of St. Michael in Macao - Olga Ng Ka Man, Sandra; Caires, Carlos Sena (International Journal of Creative Interfaces and Computer Graphics, 2022)
Macao inhabit a population of 683,100. The birth rate has been dropping while the death rate has risen compared to two years ago. Cemeteries are becoming crowded, and burial spots are demanding. In this case, video calls and social media can be the solution. How about our beloved ancestors? Can we video call them on their memorial days? This paper presents a VR experience of immersing oneself in the 3D VR of the Chapel of St. Michael of Macao to create a peaceful atmosphere for grave mourning. The chapel is also a personal space where we can be truly isolated in serenity. It is a retreat to pray, disconnect, and reconnect to the beloved deaths that may not be buried in an easily accessible location. The authors propose a possible future of mourning our loved ones through virtual reality and telepresence: an immersive experience connected with Macao's extraordinary and cultural unicity.

Constructing an aesthetic discourse: Aesthetic education where Daoism meets postmodernism - Ho, Ka Lee Carrie (Education Inquiry, 2022)
Despite the prevalence of aesthetic education as one of the main developmental objectives in curricular worldwide, the mainstream philosophical discourse on its definition is predominately framed by western philosophy due to a paucity of cross-cultural studies on the subject. The article aims to achieve a contemporary understanding of aesthetic education from both the Chinese and Western aesthetic perspectives. Through the lens of postmodernism, the relationship between Daoist aesthetics and the western postmodern aesthetic perspectives, particularly the Deleuzian concept of rhizome, is identified. Both aesthetic perspectives concern de-authorship and promote self-consciousness/self-awareness. The study reconceptualises the functions of aesthetic education with the Chinese aesthetic philosophy that promotes the nurture of better people through benevolence.
Keywords: Aesthetic experiences; Daoism; Deleuze; aesthetic environments; rhizome

How can environmental conditions influence dicofol genotoxicity on the edible Asiatic clam, Meretrix meretrix? - Ivorra, Lucia; Cruzeiro, Catarina; Ramos, Alice; Tagulao, Karen; Cardoso, Patricia G. (Environmental Pollution, 2022)
Genotoxic effects of dicofol on the edible clam Meretrix meretrix were investigated through a mesocosm experiment. Individuals of M. meretrix, were exposed to environmental concentration (D1 = 50 ng/L) and supra-environmental concentration (D2 = 500 ng/L) of dicofol for 15 days, followed by the same depuration period. DNA damage (i.e., strand breaks and alkali-labile sites) was evaluated at day 1, 7 and 15, during uptake and depuration, using Comet assay (alkaline version) and nuclear abnormalities (NAs) as genotoxicity biomarkers. The protective effects of dicofol against DNA damage induced by ex vivo hydrogen peroxide (H2O2) exposure were also assessed. Comet assay results revealed no significant DNA damages under dicofol exposure, indicating 1) apparent lack of genotoxicity of dicofol to the tested conditions and/or 2) resistance of the animals due to optimal adaptation to stress conditions. Moreover, ex vivo H2O2 exposure showed an increase in the DNA damage in all the treatments without significant differences between them. However, considering only the DNA damage induced by H2O2 during uptake phase, D1 animals had significantly lower DNA damage than those from other treatments, revealing higher protection against a second stressor. NAs data showed a decrease in the % of cells with polymorphic, kidney shape, notched or lobbed nucleus, along the experiment. The combination of these results supports the idea that the clams used in the experiment were probably collected from a stressful environment (in this case Pearl River Delta region) which could have triggered some degree of adaptation to those environmental conditions, explaining the lack of DNA damages and highlighting the importance of organisms’ origin and the conditions that they were exposed during their lives.
Keywords: Bivalves; Comet assay; DNA damage; Nuclear abnormalities; Organochlorine pesticides

An Exploratory Study on the Possibility of Harmonizing Investment Protection Regimes within the OHADA Zone - Diakité, A. D.; Thiam, A. B. (Transnational Dispute Management (TDM), 2022)
Abstract With its large population and natural resources, Africa needs investors who can sustain its development. At the same time, foreign investors expect returns on their investments. In ...

Conceptual replications, research, and the “what works” agenda in education - Morrison, Keith (Educational Research and Evaluation, 2022)

A touristic habitation: automobilities of Chinese driving tourists - Yang, Peng; Xu, Honggang; Hannam, Kevin (Tourism Geographies, 2022)
As an emergent tourism sector, driving tourism connects car use and touristic activities intimately. Following the notion of the ‘inhabited car’, this article explores how and why Chinese tourists inhabit a travelling car for drivers/passengers in the leisure automobility and driving tourism context. Through three different road trips and ‘mobile methods’, it was found that Chinese tourists inhabit the car in four ways: driving, gazing, listening, and communicating. Through this embodied habitation, the car is turned into a ‘touristic inhabitation’ space for protecting the tourists generating touristic emotions、social interactions, and tourism meanings. The study contributes to automobility and tourism literature and provides implications for driving tourism development in China.
Keywords: Automobilities; China; cars; driving tourism; habitation

Exploratory Research on Key Technology of Human-Computer Interactive 2.5-Minute Fast Digital Early Warning for Mild Cognitive Impairment - Li, Nan; Yang, Xiaotong; Du, Wencai; Ogihara, Atsushi; Zhou, Siyu; Ma, Xiaowen; Wang, Yujia; Li, Shuwu; Li, Kai (Computational Intelligence and Neuroscience, 2022)
Objective. As the preclinical stage of Alzheimer’s disease (AD), Mild Cognitive Impairment (MCI) is characterized by hidden onset, which is difficult to detect early. Traditional neuropsychological scales are main tools used for assessing MCI. However, due to its strong subjectivity and the influence of many factors such as subjects’ educational background, language and hearing ability, and time cost, its accuracy as the standard of early screening is low. Therefore, the purpose of this paper is to propose a new key technology of fast digital early warning for MCI based on eye movement objective data analysis. Methodology. Firstly, four exploratory indexes (test durations, correlation degree, lengths of gaze trajectory, and drift rate) of MCI early warning are determined based on the relevant literature research and semistructured expert interview; secondly, the eye movement state is captured based on the eye tracker to realize the data extraction of four exploratory indexes. On this basis, the human-computer interactive 2.5-minute fast digital early warning paradigm for MCI is designed; thirdly, the rationality of the four early warning indexes proposed in this paper and their early warning effectiveness on MCI are verified. Results. Through the small sample test of human-computer interactive 2.5 fast digital early warning paradigm for MCI conducted by 32 elderly people aged 70–90 in a medical institution in Hangzhou, the two indexes of “correlation degree” and “drift rate” with statistical differences are selected. The experiment results show that AUC of this MCI early warning paradigm is 0.824. Conclusion. The key technology of human-computer interactive 2.5 fast digital early warning for MCI proposed in this paper overcomes the limitations of the existing MCI early warning tools, such as low objectification level, high dependence on professional doctors, long test time, requiring high educational level, and so on. The experiment results show that the early warning technology, as a new generation of objective and effective digital early warning tool, can realize 2.5-minute fast and high-precision preliminary screening and early warning for MCI in the elderly.

Noise-induced hearing loss correlates with inner ear hair cell decrease in larval zebrafish - Lara, Rafael A.; Breitzler, Lukas; Lau, Ieng Hou; Gordillo-Martinez, Flora; Chen, Fangyi; Fonseca, Paulo J.; Bass, Andrew H.; Vasconcelos, Raquel O. (Journal of Experimental Biology, 2022)
Anthropogenic noise can be hazardous for the auditory system and wellbeing of animals, including humans. However, very limited information is known on how this global environmental pollutant affects auditory function and inner ear sensory receptors in early ontogeny. The zebrafish (Danio rerio) is a valuable model in hearing research, including investigations of developmental processes of the vertebrate inner ear. We tested the effects of chronic exposure to white noise in larval zebrafish on inner ear saccular sensitivity and morphology at 3 and 5 days post-fertilization (dpf), as well as on auditory-evoked swimming responses using the prepulse inhibition (PPI) paradigm at 5 dpf. Noise-exposed larvae showed a significant increase in microphonic potential thresholds at low frequencies, 100 and 200 Hz, while the PPI revealed a hypersensitization effect and a similar threshold shift at 200 Hz. Auditory sensitivity changes were accompanied by a decrease in saccular hair cell number and epithelium area. In aggregate, the results reveal noise-induced effects on inner ear structure–function in a larval fish paralleled by a decrease in auditory-evoked sensorimotor responses. More broadly, this study highlights the importance of investigating the impact of environmental noise on early development of sensory and behavioural responsiveness to acoustic stimuli.

From Maximum Illud 1919 to the First National Synod Primum Concilium Sinensis 1924 in Shanghai: Historical & Theological Perspectives - Gassner, Franz (Orientis Aura: Macau Perspectives in Religious Studies, 2022)

Minimising Maximum Illud: Early Resistance to Missionary Inculturation in China - Law, Cyril Jerome (Orientis Aura: Macau Perspectives in Religious Studies, 2022)

A Deep Neural Network Based on Circular Representation for Target Detection - Lin, Cong; Chen, Zhoujian; Huang, Yiquan; Jiang, Haoyu; Du, Wencai; Chen, Qiong (Journal of Sensors, 2022)
Convolutional neural network (CNN) model based on deep learning has excellent performance for target detection. However, the detection effect is poor when the object is circular or tubular because most of the existing object detection methods are based on the traditional rectangular box to detect and recognize objects. To solve the problem, we propose the circular representation structure and RepVGG module on the basis of CenterNet and expand the network prediction structure, thus proposing a high-precision and high-efficiency lightweight circular object detection method RebarDet. Specifically, circular tubular type objects will be optimized by replacing the traditional rectangular box with a circular box. Second, we improve the resolution of the network feature map and the upper limit of the number of objects detected in a single detect to achieve the expansion of the network prediction structure, optimized for the dense phenomenon that often occurs in circular tubular objects. Finally, the multibranch topology of RepVGG is introduced to sum the feature information extracted by different convolution modules, which improves the ability of the convolution module to extract information. We conducted extensive experiments on rebar datasets and used AB-Score as a new evaluation method to evaluate RebarDet. The experimental results show that RebarDet can achieve a detection accuracy of up to 0.8114 and a model inference speed of 6.9 fps while maintaining a moderate amount of parameters, which is superior to other mainstream object detection models and verifies the effectiveness of our proposed method. At the same time, RebarDet’s high precision detection of round tubular objects facilitates enterprise intelligent manufacturing processes.

The evolutionary argument against naturalism: a Wittgensteinian response - DeVito, Michael; McNabb, Tyler (International Journal for Philosophy of Religion, 2022)
In this essay, we put forth a novel solution to Plantinga’s Evolutionary Argument Against Naturalism, utilizing recent work done by Duncan Pritchard on radical skepticism. Key to the success of Plantinga’s argument is the doubting of the reliability of one’s cognitive faculties. We argue (viz. Pritchard and Wittgenstein) that the reliability of one’s cognitive faculties constitutes a hinge commitment, thus is exempt from rational evaluation. In turn, the naturalist who endorses hinge epistemology can deny the key premise in Plantinga’s argument and avoid the dilemma posed on belief in the conjunction of naturalism and evolution.

Measuring Specific Traditional Chinese Values in Relation to Satisfaction of the Five Maslow Needs - Taormina, Robert J.; Gao, Jennifer H.; Kuok, A. C.H. (Psychological Thought, 2022)
To determine whether living according to specific traditional Chinese cultural values was associated with satisfaction of the five needs in Maslow’s motivational hierarchy and overall life satisfaction, a mixed-method approach was employed, with an empirical questionnaire and supplemental interviews. The questionnaire assessed the hypothesized relationships that traditional Chinese values had with personal life outcomes, including health, employment, satisfaction of the five needs from Maslow’s hierarchy, and life satisfaction. The interviews examined the relationships that several demographic variables had with living by traditional Chinese values. The results of the empirical data revealed that most Chinese people today are still living according to the traditional Chinese cultural values, and that living by those traditional values are strongly associated with satisfaction of all five of the human needs in the Maslow hierarchy, as well as with overall life satisfaction. Additionally, the results of the qualitative interviews readily supported the empirical findings, and also revealed that the time during which inter-generational transmission of the Chinese cultural values occurs is when parents teach those values to their children at a very early age, that is, between 3 and 8 years old, before the children start primary school.

La terre des autochtones potiguara du brésil: une construction sociale et politique - Simões, José Manuel (E-Journal of Intercultural Studies, 2022)
The land of the potiguara indians of Brazil: a social and political construction The space in which the potiguaras of Brazil live is, today as in the past, the result of a longterm process, many negotiations and well-managed refuges. Paradoxically, despite their recurrent discourse invoking the ancestry of their lands of origin, the Potiguara fight and continue to fight politically for the return to the spaces where their colonial refuge took place.

Internationalisation of higher education: new players in a changing scene - Ge, Yun (Educational Research and Evaluation, 2022)

Belt and Road Initiatives: implications for China’s internationalisation of tertiary-level education - Ge, Yun; Ho, Kong Chong (Educational Research and Evaluation, 2022)
Since the launch of the One Belt and One Road Initiative (BRI) in 2013, the internationalisation of China’s tertiary education has entered a new stage. Central to the BRI is investment and strategic planning for talent cultivation, knowledge production, and transmission. This paper explains how the BRI redirects, reinforces, and intensifies China’s strategic planning and actions for internationalising its education. It adopts a policy analysis approach and reviews three key aspects of development and shifting emphasis of internationalisation under the impact of the BRI: international education networks along the Six BRI Economic Corridors, vocational colleges as new players in international education, and promotion of the Chinese language as a new global language. The analysis captures an important moment in which international education processes are being visibly altered through China’s strategies to take the lead in economic globalisation and to compete for a central place in the world via the BRI.
Keywords: Belt and Road Initiatives; Chinese language; Internationalisation of higher education; vocational education

A positivist approach to work engagement: moderating effects of perceived organizational support - Kuok, A. C. H; Taormina, Robert J. (Dynamic Relationships Management Journal, 2022)

Self-Efficacy, Stress and Job Satisfaction among Pre-Service, Novice and Experienced English Teachers: A Study of their Occupational Health - Lam, Stacy; Kuok, A. C. H.; Sze, Tat Ming (Health Psychology Report, 2022)
Background This study aimed to investigate English teachers’ self-efficacy for student engagement, classroom management, instructional strategies and literacy instruction, as well as to discover teacher stress and job satisfaction can play a role in interfering their occupational health (in terms of self-efficacy). In addition, this is one of the first studies to understand the differences in self-efficacy among pre-service, novice and experienced in-service teachers in a Chinese society, where English is positioned as a foreign language. Participants and procedure 271 English teachers (90 pre-service, 181 in-service) with mean teaching experience of 5.57 months for per-service, and 98.51 months for in-service were participated in this quantitative research study, as the targets were not be able to approach randomly, the English teachers were approaching individually though referral sampling, informing that the purpose of the study and receive their consent. Results It discovered both pre-service and novice in-service teachers posses lowest self-efficacy. Moreover, teachers’ stress from classroom predicted their self-efficacy for student engagement and classroom management negatively. On the other hand, teachers’ job satisfaction predicts their self-efficacy for student engagement, instructional strategies and literacy instruction positively. Conclusions Implications (based on the findings) are discussed in order to provide insights for for schools and education departments to strengthen the teachers’ capability of teaching and their occupational health.

Geochemistry, sulfur and lead isotopic composition of hydrothermal sulfide from the Duanqiao hydrothermal field on the Southwest Indian Ridge: implications for ore genesis - Yang, Weifang; Liao, Shili; Alveirinho Dias, Ágata; Liang, Jin; Li, Wei; Ding, Teng; Tao, Chunhui (International Geology Review, 2022)
Hydrothermal activities on ultraslow-spreading ridges exhibit diverse characteristics, long histories with multiple participants, and might form large-scale, high-grade sulfide deposits. The Duanqiao hydrothermal field (DHF) is located at the segment with the thickest oceanic crust and a large axial magma chamber on the Southwest Indian Ridge, providing unique perspective of sulfide metallogenesis on ultraslow-spreading ridges. Previous studies revealed that DHF sulfide exhibits distinct features of enrichment of ore-forming elements in comparison with those of hydrothermal fields on sediment-starved mid-ocean ridges. However, the genesis and processes responsible for such differences remain poorly constrained. In this study, mineralogical, geochemical and S and Pb isotopic analyses were performed on relict sulfide mound samples to characterize DHF formation. The samples show clear concentric mineral zonation from the interior to the exterior wall. Assemblages of chalcopyrite, sphalerite, and pyrite are distributed mainly in the interior wall, whereas pyrite and marcasite are distributed mainly in the exterior wall. The low Cu content and Pb isotopic composition of the sulfide indicate that the metals are derived mainly from basement basalts. The δ34S values exhibit positive values distributed over a reasonably narrow range (2.42‰–7.97‰), which suggests approximately 62.1%–88.5% of S with basaltic origin. Compared with most hydrothermal fields along the sediment starved mid-ocean ridges, the DHF sulfide shows particularly high contents of Pb (263–2630 ppm), As (234–726 ppm), Sb (7.32–44.3 ppm), and Ag (35.2 to >100 ppm). The δ34S values exhibit an increasing tendency from the sample exterior to the interior. We propose that these features probably reflect the existence of a subsurface zone refining process. Our results provide new insight into the sulfide formation process and contribute to understanding the metallogenic mechanism of hydrothermal sulfides on ultraslow-spreading ridges.
Keywords: Hydrothermal sulfide; geochemistry; southwest Indian ridge; sulfur isotope; zone refining

A metamorphic devolatilization model for the genesis of the Baiyun gold deposit in the North China Craton: A novel Fe-S isotopes perspective - Liu, Shuaijie; Chen, Bin; Zheng, Jiahao; Wu, Yafei; Bao, Chuang; Zhao, Guochun (Gondwana Research, 2022)
The Mesozoic gold deposits in the North China Craton (NCC) were hosted by the Precambrian basement and Mesozoic intrusions. Thus, most researchers consider that these gold deposits were genetically linked to the Mesozoic intrusions. However, we suggest that a metamorphic devolatilization model provides an alternative based on a combined Fe and in-situ S isotopes study on auriferous pyrites from the Baiyun gold deposit in the NCC. The Triassic Baiyun gold deposit contains the quartz vein and altered rock ores that were developed in the Paleoproterozoic metavolcanic-sedimentary rocks (the Liaohe Group). Our in-situ S isotopic analyses show that pyrites from the quartz vein ores are characterized by negative δ34S values (-10.7 ∼ -5.5‰), while those from the altered rock ores have two distinct groups of δ34S values, one being positive (+13.5 ∼ +16.2‰) and the other negative (-10.6 ∼ -3.0‰). We suggest that pyrite grains with positive δ34S values should be relicts from the host rocks, because they show comparable δ34S values with those from the host rocks schists (+3.3 ∼ +16.1‰). Thus, only the negative δ34S values of pyrites in ores (-10.7 ∼ -3.0‰) and the Fe isotopes of the quartz vein ores (δ56Fe = +0.30 ∼ +0.48‰) can represent the isotopic characteristics of ore-forming fluids at Baiyun. Our study shows that the sulfur were probably from the pyritic volcanic-sedimentary sequences of the Liaohe Group, rather than from magmas. The calculated δ56Fe values of the ore-forming fluids (-0.78 ∼ -0.37‰; pyrite-fluid isotope fractionation) could be modelled in a metamorphic devolatilization model with Fe-species (pyrite&magnetite) of the Liaohe Group as sources. Therefore, our combined S- and Fe- isotope data indicate that the metamorphic devolatilization of the Liaohe Group could account for the genesis of the Baiyun gold deposit.
Keywords: Baiyun gold deposit; Fe isotope; Metamorphic devolatilization model; Orogenic gold deposits; S isotope

A Neuropeptide Y/F-like Polypeptide Derived from the Transcriptome of Turbinaria peltata Suppresses LPS-Induced Astrocytic Inflammation - Chen, Qian; Liang, Zirong; Yue, Qian; Wang, Xiufen; Siu, Shirley Weng In; Pui-Man Hoi, Maggie; Lee, Simon Ming-Yuen (Journal of Natural Products, 2022)
Neuropeptides are a group of neuronal signaling molecules that regulate physiological and behavioral processes in animals. Here, we used in silico mining to predict the polypeptide composition of available transcriptomic data of Turbinaria peltata. In total, 118 transcripts encoding putative peptide precursors were discovered. One neuropeptide Y/F-like peptide, named TpNPY, was identified and selected for in silico structural, in silico binding, and pharmacological studies. In our study, the anti-inflammation effect of TpNPY was evaluated using an LPS-stimulated C8-D1A astrocyte cell model. Our results demonstrated that TpNPY, at 0.75–3 μM, inhibited LPS-induced NO production and reduced the expression of iNOS in a dose-dependent manner. Furthermore, TpNPY reduced the secretion of proinflammatory cytokines. Additionally, treatment with TpNPY reduced LPS-mediated elevation of ROS production and the intracellular calcium concentration. Further investigation revealed that TpNPY downregulated the IKK/IκB/NF-κB signaling pathway and inhibited expression of the NLRP3 inflammasome. Through molecular docking and using an NPY receptor antagonist, TpNPY was shown to have the ability to interact with the NPY Y1 receptor. On the basis of these findings, we concluded that TpNPY might prevent LPS-induced injury in astrocytes through activation of the NPY-Y1R.

Ockham on the Side of the Angels: Why a Classical Theist Shouldn't be Moved by Oppy's Argument from Simplicity - McNabb, Tyler; DeVito, Michael (New Blackfriars, 2022)

Temporary transnational labour mobility and gendered individualization in Europe - Harsløf, Ivan; Zuev, Dennis (Mobilities, 2022)
In a context of a new transnational division of labour, temporary international labour mobility is on the rise in Europe. In particular, recent decades have seen considerably more women seeking work experience abroad. Observers have been concerned with how such mobility is related to individualization, and in particular how it may challenge collective institutions, communities and families. The aim of this study is to explore such issues among women and men with international work experience. Using data from European Social Survey, the paper investigates previously mobile workers in terms of their current working and living conditions. Across genders, we consider different forms of individualization that may be associated with transnational labour mobility. While both women and men with transnational work experience generally feature strong strategic individualization, this is most pronounced among men. Hence, men's mobility is among other things associated with increased autonomy in working life, while – in contrast to women – it does not seem to hamper their integration in the sphere of social reproduction.
Keywords: Europe; Temporary labour mobility; individualization; sphere of production; sphere of social reproduction; transnational division of labour

Instance-based deep transfer learning with attention for stock movement prediction - He, Qi-Qiao; Siu, Shirley Weng In; Si, Yain-Whar (Applied Intelligence, 2022)
Stock movement prediction is one of the most challenging problems in time series analysis due to the stochastic nature of financial markets. In recent years, a plethora of statistical methods and machine learning algorithms were proposed for stock movement prediction. Specifically, deep learning models are increasingly applied for the prediction of stock movement. The success of deep learning models relies on the assumption that massive training data are available. However, this assumption is impractical for stock movement prediction. In stock markets, a large number of stocks do not have enough historical data, especially for the companies which underwent initial public offering in recent years. In these situations, the accuracy of deep learning models to predict the stock movement could be affected. To address this problem, in this paper, we propose novel instance-based deep transfer learning models with attention mechanism. In the experiments, we compare our proposed methods with state-of-the-art prediction models. Experimental results on three public datasets reveal that our proposed methods significantly improve the performance of deep learning models when limited training data are available.
Keywords: Attention mechanism; Deep transfer learning; Instance-based; Stock movement prediction

Trying a board game intervention on children with autism spectrum disorder in Macau: how do they react? - Lok, Ka Ieong; Chiang, Hsu-Min; Lin, Yueh-Hsien; Jiang, Chunlian (International Journal of Developmental Disabilities, 2022)
Limited special education and related services are available for children with autism spectrum disorder (ASD) in Macau, especially those who are educated in general education classrooms. No intervention study has been conducted on these children. This study was conducted to explore the relationship between a board game play intervention and board game play behaviors and social communication of children with ASD educated in general education classrooms in Macau. A repeated measures design was used and the results of this study showed the mean occurrence of unprompted board game play behaviors per session during intervention was not significantly different from that during pre- or post-intervention. The mean occurrence of social communication per session during intervention was significantly higher than that during pre- and post-intervention. These findings suggest a positive relationship existed between the board game intervention used in this study and social communication of children with ASD.
Keywords: Autism Spectrum Disorder; Macau; board game; play; social communication

Material Source of Sediments from West Clarion–Clipperton Zone (Pacific): Evidence from Rare Earth Element Geochemistry and Clay Minerals Compositions - Qiu, Zhongrong; Tao, Chunhui; Ma, Weilin; Dias, Ágata Alveirinho; Hu, Siyi; Shao, Yuexiao; Yang, Kehong; Zhang, Weiyan (Journal of Marine Science and Engineering, 2022)
The geochemistry and mineralogy of sediments provide relevant information for the understanding of the origin and metallogenic mechanism of ferromanganese nodules and crusts. At present, there are still few studies on the sediment origin of the Clarion–Clipperton Zone (CCZ) of the east Pacific, particularly on the systematic origin of sediments with a longer history/length. Here, bulk sediment geochemistry and clay mineral compositions were analyzed on a 5.7 m gravity core (GC04) obtained at the CCZ, an area rich in polymetallic nodules. The results indicate that the average total content of rare earth elements (REE), including yttrium (REY), in sediments is 454.7 ppm and the REEs distribution patterns normalized by the North American Shale Composite of samples are highly consistent, with all showing negative Ce anomalies and more obvious enrichment in heavy REE (HREE) than that of light REE (LREE). Montmorillonite/illite ratio, discriminant functions and smear slide identification indicate multiple origins for the material, and are strongly influenced by contributions from marine biomass, while terrestrial materials, seamount basalts and their alteration products and authigenic source also make certain contributions. The REY characteristics of the sediments in the study area are different from those of marginal oceanic and back-arc basins, and more similar to pelagic deep-sea sediments. Based on LREE/HREE-1/δCe and LREE/HREE-Y/Ho diagrams, we conclude that samples from the study area had pelagic sedimentary properties which suffered from a strong “seawater effect”.
Keywords: Clarion–Clipperton Zone; material source; rare earth elements; sediments geochemistry

Multi-Branch-CNN: Classification of ion channel interacting peptides using multi-branch convolutional neural network - Yan, Jielu; Zhang, Bob; Zhou, Mingliang; Kwok, Hang Fai; Siu, Shirley W. I. (Computers in Biology and Medicine, 2022)
Ligand peptides that have high affinity for ion channels are critical for regulating ion flux across the plasma membrane. These peptides are now being considered as potential drug candidates for many diseases, such as cardiovascular disease and cancers. In this work, we developed Multi-Branch-CNN, a CNN method with multiple input branches for identifying three types of ion channel peptide binders (sodium, potassium, and calcium) from intra- and inter-feature types. As for its real-world applications, prediction models that are able to recognize novel sequences having high or low similarities to training sequences are required. To this end, we tested our models on two test sets: a general test set including sequences spanning different similarity levels to those of the training set, and a novel-test set consisting of only sequences that bear little resemblance to sequences from the training set. Our experiments showed that the Multi-Branch-CNN method performs better than thirteen traditional ML algorithms (TML13), yielding an improvement in accuracy of 3.2%, 1.2%, and 2.3% on the test sets as well as 8.8%, 14.3%, and 14.6% on the novel-test sets for sodium, potassium, and calcium ion channels, respectively. We confirmed the effectiveness of Multi-Branch-CNN by comparing it to the standard CNN method with one input branch (Single-Branch-CNN) and an ensemble method (TML13-Stack). The data sets, script files to reproduce the experiments, and the final predictive models are freely available at https://github.com/jieluyan/Multi-Branch-CNN.
Keywords: Classification; Deep learning; Drug discovery; Ion channel; Multi-Branch-CNN; Peptides

Modulações em português de imagens, experiências e estesias orientais: revisão das razões do fascínio de alguma dicção poética chinesa e japonesa como utopia da poesia - Borges, Vera (Alea: Estudos Neolatinos, 2022)
Resumo O fascínio do Ocidente pela dicção poética oriental está atestado em várias latitudes e línguas, e resultou numa profícua produção na área da poesia. Sabe-se que a reinvenção da poesia chinesa da autoria de Pound, em grande medida na origem da sua proposta de revolução do idioma poético, nas primeiras décadas do séc. XX, assentou, na verdade, numa falácia; numa concepção errada da natureza da escrita chinesa (e japonesa) como essencialmente pictográfica e ideogramática, na base de propriedades expressivas reconhecidas na poesia que resultariam numa particular eficácia na apreensão e tradução do real. Pessanha enaltece, em termos similares aos da exaltação poundiana, a escrita da poesia chinesa clássica. Interessa-nos rever alguns inventários dos traços da dicção poética chinesa e japonesa que explicam que ela seja tomada como metonímia e metáfora da poesia, ou como meta e utopia da poesia, para perceber o que terá levado autores muito díspares a tentar a mão nos haikus, processo em que sondaremos algumas formulações poéticas em língua portuguesa. Consideramos também que esse fascínio por uma (sonhada) origem da dicção poética, quando cruzada com o habitar (não metafórico, neste caso) do pequenino enclave de Macau, de autores que nele lançaram raízes, resultou em alguns exercícios poéticos particularmente felizes e singulares. Serão trazidos à colação nesta abordagem poemas de Eugénio de Andrade, Sophia de Mello Breyner Andresen, José Tolentino Mendonça, Yao Feng, Fernanda Dias e Fernando Sales Lopes.
Keywords: Macau; Pound; falácia; haiku; poesia; poesia chinesa; trocar de voz

Using Machine Learning Methods to Forecast Air Quality: A Case Study in Macao - Lei, Thomas M. T.; Siu, Shirley W. I.; Monjardino, Joana; Mendes, Luisa; Ferreira, Francisco (Atmosphere, 2022)
Despite the levels of air pollution in Macao continuing to improve over recent years, there are still days with high-pollution episodes that cause great health concerns to the local community. Therefore, it is very important to accurately forecast air quality in Macao. Machine learning methods such as random forest (RF), gradient boosting (GB), support vector regression (SVR), and multiple linear regression (MLR) were applied to predict the levels of particulate matter (PM10 and PM2.5) concentrations in Macao. The forecast models were built and trained using the meteorological and air quality data from 2013 to 2018, and the air quality data from 2019 to 2021 were used for validation. Our results show that there is no significant difference between the performance of the four methods in predicting the air quality data for 2019 (before the COVID-19 pandemic) and 2021 (the new normal period). However, RF performed significantly better than the other methods for 2020 (amid the pandemic) with a higher coefficient of determination (R2) and lower RMSE, MAE, and BIAS. The reduced performance of the statistical MLR and other ML models was presumably due to the unprecedented low levels of PM10 and PM2.5 concentrations in 2020. Therefore, this study suggests that RF is the most reliable prediction method for pollutant concentrations, especially in the event of drastic air quality changes due to unexpected circumstances, such as a lockdown caused by a widespread infectious disease.
Keywords: COVID-19; air pollution; air quality; air quality forecast; gradient boosting; multiple linear regression; random forest; support vector regression

Anti-epileptic Kunitz-like peptides discovered in the branching coral Acropora digitifera through transcriptomic analysis - Chen, Hanbin; Siu, Shirley Weng In; Wong, Clarence Tsun Ting; Qiu, Jianwen; Cheung, Alex Kwok-Kuen; Lee, Simon Ming Yuen (Archives of Toxicology, 2022)
Approximately 50 million people are suffering from epilepsy worldwide. Corals have been used for treating epilepsy in traditional Chinese medicine, but the mechanism of this treatment is unknown. In this study, we analyzed the transcriptome of the branching coral Acropora digitifera and obtained its Kyoto Encyclopedia of Genes and Genomes (KEGG), EuKaryotic Orthologous Groups (KOG) and Gene Ontology (GO) annotation. Combined with multiple sequence alignment and phylogenetic analysis, we discovered three polypeptides, we named them AdKuz1, AdKuz2 and AdKuz3, from A. digitifera that showed a close relationship to Kunitz-type peptides. Molecular docking and molecular dynamics simulation indicated that AdKuz1 to 3 could interact with GABAA receptor but AdKuz2–GABAA remained more stable than others. The biological experiments showed that AdKuz1 and AdKuz2 exhibited an anti-inflammatory effect by decreasing the aberrant level of nitric oxide (NO), IL-6, TNF-α and IL-1β induced by LPS in BV-2 cells. In addition, the pentylenetetrazol (PTZ)-induced epileptic effect on zebrafish was remarkably suppressed by AdKuz1 and AdKuz2. AdKuz2 particularly showed superior anti-epileptic effects compared to the other two peptides. Furthermore, AdKuz2 significantly decreased the expression of c-fos and npas4a, which were up-regulated by PTZ treatment. In addition, AdKuz2 reduced the synthesis of glutamate and enhanced the biosynthesis of gamma-aminobutyric acid (GABA). In conclusion, the results indicated that AdKuz2 may affect the synthesis of glutamate and GABA and enhance the activity of the GABAA receptor to inhibit the symptoms of epilepsy. We believe, AdKuz2 could be a promising anti-epileptic agent and its mechanism of action should be further investigated.
Keywords: Anti-epileptic; GABAA; Kunitz peptide; Transcriptome

The effect of time regime in noise exposure on the auditory system and behavioural stress in the zebrafish - Wong, Man Ieng; Lau, Ieng Hou; Gordillo-Martinez, Flora; Vasconcelos, Raquel O. (Scientific Reports, 2022)
Anthropogenic noise of variable temporal patterns is increasing in aquatic environments, causing physiological stress and sensory impairment. However, scarce information exists on exposure effects to continuous versus intermittent disturbances, which is critical for noise sustainable management. We tested the effects of different noise regimes on the auditory system and behaviour in the zebrafish (Danio rerio). Adult zebrafish were exposed for 24 h to either white noise (150 ± 10 dB re 1 μPa) or silent control. Acoustic playbacks varied in temporal patterns—continuous, fast and slow regular intermittent, and irregular intermittent. Auditory sensitivity was assessed with Auditory Evoked Potential recordings, revealing hearing loss and increased response latency in all noise-treated groups. The highest mean threshold shifts (c. 13 dB) were registered in continuous and fast intermittent treatments, and no differences were found between regular and irregular regimes. Inner ear saccule did not reveal significant hair cell loss but showed a decrease in presynaptic Ribeye b protein especially after continuous exposure. Behavioural assessment using the standardized Novel Tank Diving assay showed that all noise-treated fish spent > 98% time in the bottom within the first minute compared to 82% in control, indicating noise-induced anxiety/stress. We provide first data on how different noise time regimes impact a reference fish model, suggesting that overall acoustic energy is more important than regularity when predicting noise effects.
Keywords: Ecology; Neuroscience; Physiology; Zoology

Diversity and Variation in China's Yao Ancient Wood Frame Structures Through Genetic Algorithms: - Afonso, Filipe; Jedenov, Kirill; Januário, Pedro Gomes; Almeida, Paulo (International Journal of Creative Interfaces and Computer Graphics, 2022)
This study, focusing on the China's Yao minority community, investigates the feasibility to create a generative computational method to replicate the diversity of the existing Yao traditional wood buildings, addressing the critical issues currently facing computational design methods, in the attempt to adapt genetic-generative algorithms to the study of local ancient architecture. The project develops a computational tool to generate a network of three-dimensional prototypes, or building structures, derived from traditional wood frame village houses. It studies possible housing structures that illustrate some of the key working methods available in digital systems such as ‘generating' and ‘compositing' taking as a starting point computational strategies oriented towards geometry and where a set of local variables play a decisive role: available local technologies, use of raw materials, and the dimensioning of timber components based on data collected from Yao architecture.

A Critical Look at Blockchain-Interactive Generative Art - Farinha, Daniel Filipe (International Journal of Creative Interfaces and Computer Graphics, 2022)
Artists are increasingly using blockchain as a tool for trading digital artwork as non-fungible tokens (NFTs); however, some are also beginning to experiment with the blockchain as a medium for generative art, using it as a seed for a generative process or to continuously modify an evolving piece. This paper surveys, reviews, and classifies the state-of-the-art in blockchain-interactive NFTs and presents a liberal-arts critique of the opportunities and threats posed by this technology, whilst addressing existing criticism on the broader topic of art-related NFTs. The paper examines some of the most experimental pieces minted on the Hic et Nunc (HEN) and Teia NFT marketplaces, for which a purpose-built research tool was developed. The survey reveals some reliance on centralised infrastructure, namely blockchain indexers, placing undesired trust on third parties which undermines the potential longevity of the artwork. The paper concludes with recommendations for artists and NFT platform designers for developing more resilient and economically sustainable architectures.
Keywords: Art Preservation; Blockchain; Crypto Art; Dynamic NFT; Generative Art; Non-Fungible Token; Provenance

How social media affects the purchase intentions of female consumers in Macao - watching beauty and cosmetics product experience videos on YouTube - Chan, Velda; Silva, Susana C.; Lampo, Alessandro (Revista Gestão em Análise, 2022)
YouTube has become increasingly popular for marketing purposes. As corporate and user-generated content is widely available on this platform, beauty-related professionals need to understand how to create videos that make their products more appealing and stand out from the clutter. In this study, we examine four factors (i.e., perceived usefulness of the information, perceived credibility of the information, attitude toward the purchase, and perceived video characteristics) that affect the purchase intentions of female consumers. After viewing beauty-related videos, a sample of 204 female consumers was analyzed by structural equation modeling. The findings showed that videos with more views, likes, and comments tend to have a greater effect on the respondents' intentions to purchase. Also, the factors of perceived usefulness of the information, perceived credibility of the information, and attitude toward the purchase exhibited a significant effect on the intention to buy beauty-related products. The result showed that perceived video characteristics (such as quality and visuals) did not significantly influence the purchase intention, however, there is evidence that this factor should not be ignored by content creators. Finally, our research provides insights, strategies, and future directions for industry practitioners and marketers.
Keywords: YouTube beauty products; YouTube marketing; beauty and cosmetics marketing; purchase intention

Recent Progress in the Discovery and Design of Antimicrobial Peptides Using Traditional Machine Learning and Deep Learning - Yan, Jielu; Cai, Jianxiu; Zhang, Bob; Wang, Yapeng; Wong, Derek F.; Siu, Shirley W. I. (Antibiotics, 2022)
Antimicrobial resistance has become a critical global health problem due to the abuse of conventional antibiotics and the rise of multi-drug-resistant microbes. Antimicrobial peptides (AMPs) are a group of natural peptides that show promise as next-generation antibiotics due to their low toxicity to the host, broad spectrum of biological activity, including antibacterial, antifungal, antiviral, and anti-parasitic activities, and great therapeutic potential, such as anticancer, anti-inflammatory, etc. Most importantly, AMPs kill bacteria by damaging cell membranes using multiple mechanisms of action rather than targeting a single molecule or pathway, making it difficult for bacterial drug resistance to develop. However, experimental approaches used to discover and design new AMPs are very expensive and time-consuming. In recent years, there has been considerable interest in using in silico methods, including traditional machine learning (ML) and deep learning (DL) approaches, to drug discovery. While there are a few papers summarizing computational AMP prediction methods, none of them focused on DL methods. In this review, we aim to survey the latest AMP prediction methods achieved by DL approaches. First, the biology background of AMP is introduced, then various feature encoding methods used to represent the features of peptide sequences are presented. We explain the most popular DL techniques and highlight the recent works based on them to classify AMPs and design novel peptide sequences. Finally, we discuss the limitations and challenges of AMP prediction.
Keywords: antimicrobial peptide; classification; deep learning; machine learning; medicine; regression; therapeutic peptide

Understanding of base-10 concept and its application: a cross-cultural comparison between Japan and Singapore - Marcruz, Ong Yew Lee; Carrie, Ho Ka Lee; Manabu, Kawata; Mayumi, Takahashi; Kumpei, Mizuno (International Journal of Early Years Education, 2022)
It has become increasingly clear that the early use of decomposition for addition is associated with later mathematical achievement. This study examined how younger children execute a base-10 decomposition strategy to solve complex arithmetic (e.g. two-digit addition). 24 addition problems in two modalities (WA: Written Arithmetic; OA: Oral Arithmetic) with sums less than 100 were administered to 22 Japanese and 22 Singaporean 6-year-old kindergarteners. Our findings reveal that they were able to solve complex addition. For instance, Japanese kindergarteners tended to solve complex arithmetic using base-10 decomposition across the modality, whereas Singaporean kindergarteners used standard algorithms and basic counting to solve complex WA and OA problems, respectively. We speculate that Japanese kindergarteners might have a clearer understanding of the base-10 concept and were able to use this knowledge more readily than Singaporean kindergarteners. Mathematical experiences in kindergarten and number-naming systems have been put forward as two of the crucial contributors for such cross-cultural differences. This study also provides new directions for future research on the understanding of the base-10 concept and its application among young children.
Keywords: Base-10 concept; decomposition strategy; kindergarten; mathematical experiences; number-naming system

Attentive recurrent adversarial domain adaptation with Top-k pseudo-labeling for time series classification - He, Qi-Qiao; Siu, Shirley Weng In; Si, Yain-Whar (Applied Intelligence, 2022)
The key challenge of Unsupervised Domain Adaptation (UDA) for analyzing time series data is to learn domain-invariant representations by capturing complex temporal dependencies. In addition, existing unsupervised domain adaptation methods for time series data are designed to align marginal distribution between source and target domains. However, existing UDA methods (e.g. R-DANN Purushotham et al. (2017), VRADA Purushotham et al. (2017), CoDATS Wilson et al. (2020)) neglect the conditional distribution discrepancy between two domains, leading to misclassification of the target domain. Therefore, to learn domain-invariant representations by capturing the temporal dependencies and to reduce the conditional distribution discrepancy between two domains, a novel Attentive Recurrent Adversarial Domain Adaptation with Top-k time series pseudo-labeling method called ARADA-TK is proposed in this paper. In the experiments, our proposed method was compared with the state-of-the-art UDA methods (R-DANN, VRADA and CoDATS). Experimental results on four benchmark datasets revealed that ARADA-TK achieves superior classification accuracy when it is compared to the competing methods.
Keywords: Adversarial training; Attentive; Domain adaptation; Pseudo-labeling; Time series classification

Behavioural and endocrine responses to non-interactive live and video conspecifics in males of the Siamese fighting fish - Alex, Deepa; Cardoso, Sara D; Ramos, Andreia; Gonçalves, David (Current Zoology, 2022)
The physiological mechanisms underlying variation in aggression in fish remain poorly understood. One possibly confounding variable is the lack of standardization in the type of stimuli used to elicit aggression. The presentation of controlled stimuli in videos, a.k.a. video playback, can provide better control of the fight components. However, this technique has produced conflicting results in animal behaviour studies and needs to be carefully validated. For this, a similar response to the video and an equivalent live stimulus needs to be demonstrated. Further, different physiological responses may be triggered by live and video stimuli and it is important to demonstrate that video images elicit appropriate physiological reactions. Here, the behavioural and endocrine response of male Siamese fighting fish Betta splendens to a matched for size conspecific fighting behind a one-way mirror, presented live or through video playback, was compared. The video playback and live stimulus elicited a strong and similar aggressive response by the focal fish, with a fight structure that started with stereotypical threat displays and progressed to overt attacks. Post-fight plasma levels of the androgen 11-ketotestosterone were elevated as compared to controls, regardless of the type of stimuli. Cortisol also increased in response to the video images, as previously described for live fights in this species. These results show that the interactive component of a fight, and its resolution, are not needed to trigger an endocrine response to aggression in this species. The study also demonstrates for the first time in a fish a robust endocrine response to video stimuli and supports the use of this technique for researching aggressive behaviour in B. splendens.

Hydrothermal remobilization of subseafloor sulfide mineralization along mid-ocean ridges contributes to the global oceanic zinc isotopic mass balance - Liao, Shili; Tao, Chunhui; Wen, Hanjie; Yang, Weifang; Liu, Jia; Jamieson, John W.; Dias, Ágata Alveirinho; Zhu, Chuanwei; Liang, Jin; Li, Wei; Ding, Teng; Li, Xiaohu; et al. (Geochimica et Cosmochimica Acta, 2022)
Hydrothermal activity on mid-ocean ridges is an important mechanism for the delivery of Zn from the mantle to the surface environment. Zinc isotopic fractionation during hydrothermal activity is mainly controlled by the precipitation of Zn-bearing sulfide minerals, in which isotopically light Zn is preferentially retained in solid phases rather than in solution during mineral precipitation. Thus, seafloor hydrothermal activity is expected to supply isotopically heavy Zn to the ocean. Here, we studied sulfide-rich samples from the Duanqiao-1 hydrothermal field, located on the Southwest Indian Ridge. We report that, at the hand-specimen scale, late-stage conduit sulfide material has lower δ66Zn values (−0.05 ± 0.15 ‰; n = 19) than early-stage material (+0.13 ± 0.15 ‰; n = 10). These lower values correlate with enrichments in Pb, As, Cd, and Ag, and elevated δ34S values. We attribute the low δ66Zn values to the remobilization of earlier sub-seafloor Zn-rich mineralization. Based on endmember mass balance calculations, and an assumption of a fractionation factor (αZnS-Sol.) of about 0.9997 between sphalerite and its parent solution, the remobilized Zn was found consist of about 1/3 to 2/3 of the total Zn in the fluid that formed the conduit samples. Our study suggests that late-stage subsurface hydrothermal remobilization may release isotopically-light Zn to the ocean, and that this process may be common along mid-ocean ridges, thus increasing the size of the previously identified isotopically light Zn sink in the ocean.
Keywords: Hydrothermal activity; Mid ocean ridge; Subsurface remobilization; Zinc isotopic mass balance

Examining the impact of behavioral factors on the intention of adopting E-government services: An empirical study on the hard-to-reach groups in Macao SAR, China - Iong, Kit Yeng; Phillips, Jenny O. L. (Technology in Society, 2022)
In government studies, electronic government has become a hot topic in recent decades. Many scholars believe that soon, the government might not be able to operate smoothly without the help of ICTs as the Internet has been overwhelming people's daily lives already. In analyzing people's behavioral factors towards adopting e-government services, most studies targeted the adult population, while those in the hard-to-reach groups are minimal. This study was designed especially to understand the behavioral factors of the younger generation aged between 18 and 24 and the senior citizens above 60 on their adoption of e-government services in Macao SAR. Sixteen in-depth interviews were conducted based on the semi-structured interview questions developed from the prior literature on the Theory of Planned Behavior and e-government studies. Six significant findings are yielded, which could serve as an important reference for policymakers designing e-government policy and promoting its implementation strategy. These behavioral factors also contribute empirical data to support the theoretical framework of TPB in the context of Macao SAR e-government services.
Keywords: Electronic government; Hard-to-reach groups; In-depth interviews; The theory of planned behavior

A contribution to Paulo Freire’s theory and practice: The ‘Cultural Extension Service/University of Recife’ (1962–64) - Gerhardt, Heinz Peter (Educational Philosophy and Theory, 2022)
This contribution to the special issue is an historical account of Paulo Freire’s pedagogical and administrative praxis before his forced exile in 1964. It relies on interviews collected during a field trip in 1976, a conversation with Paulo Freire in Geneva one year later and on the secondary literature up to date. Being the head of the first Extension Service of a major Brazilian university in the early 1960s gave Freire and his collaborators the space and time to experiment with the today world famous literacy method bearing his name. The concept of ‘Field of Cultural Production’ (Bourdieu) is used to elucidate better Freire and his team’s avant-gardist production within the spaces opened up by Brazil’s popular movements in the early sixties. The contribution shows how the ‘Paulo Freire System’ developed in the praxis of a cultural movement and received its academic consecration in an incremental and eclectic style.
Keywords: Bourdieu; Brazil; Paulo Freire; University of Recife; extension service; literacy

Emotional Intelligence, Work Satisfaction, and Affective Commitment: An Occupational Health Study of Social Workers - Kuok, A. C. H. (Journal of Work and Organizational Psychology, 2022)
Social workers’ work engagement and burnout were tested in relation to (a) personal variable, i.e., emotional intelligence; (b) organizational variables, i.e., work satisfaction and affective commitment. Regressions revealed emotional intelligence - controlling self – negatively predicted depersonalization and reduced personal accomplishment and positively predicted three facets of work engagement. Emotional intelligence - understanding others – was a negative predictor of reduced personal accomplishment. In addition, work satisfaction negatively predicted three components of burnout and positively predicted emotional work engagement. Affective commitment was a positive predictor of three facets of work engagement and negatively predicted reduced personal accomplishment. Implications for management are discussed.

Sudden cardiac death multiparametric classification system for Chagas heart disease's patients based on clinical data and 24-hours ECG monitoring - Cavalcante, Carlos H. L.; Primo, Pedro E. O.; Sales, Carlos A. F.; Caldas, Weslley L.; Silva, João H. M.; Souza, Amauri H.; Marinho, Emmanuel S.; Pedrosa, Roberto C.; Marques, João A. L.; Santos, Hélcio S.; Madeiro, João P. V.; Cavalcante, Carlos H. L.; et al. (Mathematical Biosciences and Engineering, 2023)
About 6.5 million people are infected with Chagas disease (CD) globally, and WHO estimates that $ > million people worldwide suffer from ChHD. Sudden cardiac death (SCD) represents one of the leading causes of death worldwide and affects approximately 65% of ChHD patients at a rate of 24 per 1000 patient-years, much greater than the SCD rate in the general population. Its occurrence in the specific context of ChHD needs to be better exploited. This paper provides the first evidence supporting the use of machine learning (ML) methods within non-invasive tests: patients' clinical data and cardiac restitution metrics (CRM) features extracted from ECG-Holter recordings as an adjunct in the SCD risk assessment in ChHD. The feature selection (FS) flows evaluated 5 different groups of attributes formed from patients' clinical and physiological data to identify relevant attributes among 57 features reported by 315 patients at HUCFF-UFRJ. The FS flow with FS techniques (variance, ANOVA, and recursive feature elimination) and Naive Bayes (NB) model achieved the best classification performance with 90.63% recall (sensitivity) and 80.55% AUC. The initial feature set is reduced to a subset of 13 features (4 Classification; 1 Treatment; 1 CRM; and 7 Heart Tests). The proposed method represents an intelligent diagnostic support system that predicts the high risk of SCD in ChHD patients and highlights the clinical and CRM data that most strongly impact the final outcome.

Actio Ecclesiae: The Participation of the Lay Christian Faithful in the Liturgy of the Hours (c. 1174 Sec. 2) - Law, Cyril Jerome (The Jurist: Studies in Church Law and Ministry, 2023)

LSDA-APF: A Local Obstacle Avoidance Algorithm for Unmanned Surface Vehicles Based on 5G Communication Environment - Li, Xiaoli; Jiao, Tongtong; Ma, Jinfeng; Duan, Dongxing; Liang, Shengbin (Computer Modeling in Engineering & Sciences, 2023)
In view of the complex marine environment of navigation, especially in the case of multiple static and dynamic obstacles, the traditional obstacle avoidance algorithms applied to unmanned surface vehicles (USV) are prone to fall into the trap of local optimization. Therefore, this paper proposes an improved artificial potential field (APF) algorithm, which uses 5G communication technology to communicate between the USV and the control center. The algorithm introduces the USV discrimination mechanism to avoid the USV falling into local optimization when the USV encounter different obstacles in different scenarios. Considering the various scenarios between the USV and other dynamic obstacles such as vessels in the process of performing tasks, the algorithm introduces the concept of dynamic artificial potential field. For the multiple obstacles encountered in the process of USV sailing, based on the International Regulations for Preventing Collisions at Sea (COLREGS), the USV determines whether the next step will fall into local optimization through the discrimination mechanism. The local potential field of the USV will dynamically adjust, and the reverse virtual gravitational potential field will be added to prevent it from falling into the local optimization and avoid collisions. The objective function and cost function are designed at the same time, so that the USV can smoothly switch between the global path and the local obstacle avoidance. The simulation results show that the improved APF algorithm proposed in this paper can successfully avoid various obstacles in the complex marine environment, and take navigation time and economic cost into account.

Foreword - Ma, J.; Du, W.; Lu, W. (Studies in Computational Intelligence, 2023)

Editorial Preface - Marcos, Aderito; Caires, Carlos; Estadieu, Gerald; Mendes, Daniel; Rodrigues, Nuno (International Journal of Creative Interfaces and Computer Graphics, 2023)

An Evangelical Adrift: The Making of John Henry Newman's Theology by Geertjan Zuijdwegt (review) - Morgan, Stephen (Antiphon: A Journal for Liturgical Renewal, 2023)

Pope John Paul II, ‘Memory and Identity: conversations at the dawn of a millennium’ - Morgan, Stephen (Memory and Identity: the proceedings of the 28th ASEACCU Annual Conference, 2023)

The Roman Mass: From Early Christian Origins to Tridentine Reform by Uwe Michael Lang - Morgan, Stephen (Antiphon: A Journal for Liturgical Renewal, 2023)

Exploratory Analysis of Project Management Adoption and Maturity Level of IT Companies–A Comparison between Macao and Hengqin - Wong, Ka Seng; Lobo Marques, João Alexandre (Journal of Advanced Management Science, 2023)

A review on multimodal machine learning in medical diagnostics - Yan, Keyue; Li, Tengyue; Marques, João Alexandre Lobo; Gao, Juntao; Fong, Simon James; Yan, Keyue; Li, Tengyue; Marques, João Alexandre Lobo; Gao, Juntao; Fong, Simon James (Mathematical Biosciences and Engineering, 2023)
Nowadays, the increasing number of medical diagnostic data and clinical data provide more complementary references for doctors to make diagnosis to patients. For example, with medical data, such as electrocardiography (ECG), machine learning algorithms can be used to identify and diagnose heart disease to reduce the workload of doctors. However, ECG data is always exposed to various kinds of noise and interference in reality, and medical diagnostics only based on one-dimensional ECG data is not trustable enough. By extracting new features from other types of medical data, we can implement enhanced recognition methods, called multimodal learning. Multimodal learning helps models to process data from a range of different sources, eliminate the requirement for training each single learning modality, and improve the robustness of models with the diversity of data. Growing number of articles in recent years have been devoted to investigating how to extract data from different sources and build accurate multimodal machine learning models, or deep learning models for medical diagnostics. This paper reviews and summarizes several recent papers that dealing with multimodal machine learning in disease detection, and identify topics for future research.

Occurrence and precipitation mechanism of silver in pyrite from chimney fragments in the Edmond hydrothermal field, Central Indian Ridge - Zhang, Huichao; Chen, Kean; Tao, Chunhui; Alveirinho Dias, Ágata; Liang, Jin; Yang, Weifang; Liao, Shili; An, Fang; Yin, Bohao; Sun, Chuanqiang (Ore Geology Reviews, 2023)

Application of ANN, XGBoost, and Other ML Methods to Forecast Air Quality in Macau - Lei, Thomas M. T.; Ng, Stanley C. W.; Siu, Shirley W. I. (Sustainability, 2023)
Air pollution in Macau has become a serious problem following the Pearl River Delta’s (PRD) rapid industrialization that began in the 1990s. With this in mind, Macau needs an air quality forecast system that accurately predicts pollutant concentration during the occurrence of pollution episodes to warn the public ahead of time. Five different state-of-the-art machine learning (ML) algorithms were applied to create predictive models to forecast PM2.5, PM10, and CO concentrations for the next 24 and 48 h, which included artificial neural networks (ANN), random forest (RF), extreme gradient boosting (XGBoost), support vector machine (SVM), and multiple linear regression (MLR), to determine the best ML algorithms for the respective pollutants and time scale. The diurnal measurements of air quality data in Macau from 2016 to 2021 were obtained for this work. The 2020 and 2021 datasets were used for model testing, while the four-year data before 2020 and 2021 were used to build and train the ML models. Results show that the ANN, RF, XGBoost, SVM, and MLR models were able to provide good performance in building up a 24-h forecast with a higher coefficient of determination (R2) and lower root mean square error (RMSE), mean absolute error (MAE), and biases (BIAS). Meanwhile, all the ML models in the 48-h forecasting performance were satisfactory enough to be accepted as a two-day continuous forecast even if the R2 value was lower than the 24-h forecast. The 48-h forecasting model could be further improved by proper feature selection based on the 24-h dataset, using the Shapley Additive Explanations (SHAP) value test and the adjusted R2 value of the 48-h forecasting model. In conclusion, the above five ML algorithms were able to successfully forecast the 24 and 48 h of pollutant concentration in Macau, with the RF and SVM models performing the best in the prediction of PM2.5 and PM10, and CO in both 24 and 48-h forecasts.
Keywords: Macau; air pollution; air quality; air quality forecast; machine learning

Serpentinization and its implications for ultramafic-hosted sulfide mineralization: A case study at the Tianzuo hydrothermal field, 63.5°E, Southwest Indian Ridge - Ding, Teng; Dias, Ágata Alveirinho; Wang, Jia; Tan, Tingting; Liang, Jin; Wu, Bin; Tao, Chunhui (Marine Geology, 2023)
Reaction of ultramafic rocks with seawater and subsequent serpentinization has been considered one of the most important factors controlling the formation of ultramafic-hosted seafloor massive sulfide (UM-SMS) deposits. However, the mineralization processes responsible for these deposits remain poorly understood, in particular because they are less abundant as compared with their basaltic counterparts. In this work, serpentinites with different alteration grades collected at the Tianzuo hydrothermal field (THF), Southwest Indian Ridge, were studied. Mineralogical and chemical analyses were performed in the secondary opaque minerals resulting from serpentinization to understand the role of this process during the formation of UM-SMS deposits. Our results show that these opaque minerals mainly consist of magnetite, hematite, pentlandite, and minor pyrite, suggestive of high but varying oxygen and sulfur fugacities. The hematite is characterized by an enrichment in Mg, Si, Ni, and Co as compared with magnetite. Pentlandite associated with hematite has elevated and consistent Ni contents as compared with that associated with magnetite. These results indicate that breakdown and decomposition of primary silicate and sulfide minerals during serpentinization has controlled the sources of ore-forming materials. Concentrations of Te are variable and show a positive correlation with Ni in pentlandite associated with magnetite or hematite, suggesting that gabbroic intrusions provided additional material to the hydrothermal system. Oxidation and sulfidation conditions are ideal for the formation of trisulfur ion S3− in THF, which can significantly improve the capability of hydrothermal fluids for leaching ore-forming metals from the wall rocks, promoting the formation of THF. In addition of reduced systems, hydrothermal fluids with high oxygen and sulfur fugacities triggered by extensive seawater infiltration can most likely also develop in ultramafic-hosted systems. These results suggest that the areas with well-developed fractures are promising candidates for further exploration of UM-SMS deposits along mid-oceanic ridges.
Keywords: Opaque minerals; Oxidation and sulfidation; Sulfide mineralization; Tianzuo hydrothermal field; Ultramafic rocks

The transformation of government employees’ behavioural intention towards the adoption of E-government services: An empirical study - Iong, Kit Yeng; Phillips, Jenny O. L. (Social Sciences & Humanities Open, 2023)
Electronic government is increasingly dominant in the study of public administration. In analysing people's behavioural factors towards the adoption of e-services, most previous studies targeted the adult population, while those on government employees are minimal. Government employees have an essential function in the process of government operation; they can be regarded as the principal medium of communication between the service provider (government) and the end-users (citizens). This study was designed to understand the government employees' behavioural factors on their intentions towards adopting e-government services. A set of semi-structured interview questions was developed based on the prior literature on the Theory of Planned Behaviour (TPB) and e-government studies. Ten in-depth interviews were conducted in Macao SAR (Special Administrative Region). In addition to analysing the three primary constructs of TPB, the factor of Trust and some enablers and hindrances were identified. Significant findings were yielded while investigating how the government employees perceived the e-services and how they regarded the general public's perception of this issue. This contextualisation would help policymakers look at this issue from different perspectives and design feasible interventions according to group alignment strategies.
Keywords: Electronic government; Government employees; In-depth interviews; The Theory of Planned Behaviour

How Immigrant Parents and Local Parents Were Involved in Children's Education in Macau - Ng, Shun W.; Cheong, Ka W. (International Journal of Educational Reform, 2023)
The objective of this case study is to analyze how two groups of parents, a group who have newly arrived in Macau from Mainland China and the other who have resided in Macau for more than three decades, interact with the class teachers at the levels of ?two-way communication,? ?supervision of children at home,? and ?participating in decision making? in a secondary school. The findings will redound to the benefits of school leaders, teachers, and indirectly the parents in a sense that looking closely at the ethnic and cultural differences between parents can promote effective cooperation between parents and teachers.

Coral empire: underwater oceans, colonial tropics, visual modernity: by Ann Elias Durham: Duke University Press, 2019, 296 pages ISBN: 9781478003182 (hbk) 99.95 USD, 9781478003823 (pbk) 26.95 USD, 9781478004462 (ebook) 26.95 USD - Zuev, Dennis (Visual Studies, 2023)

Examination of sex-related differences in intestinal and gonadal lipid metabolism in the sea cucumber Apostichopus japonicus - Zhang, Shuangyan; Ru, Xiaoshang; Zhang, Libin; Gonçalves, David; Yang, Hongsheng (Aquaculture, 2023)
Reproduction of the sea cucumber Apostichopus japonicus is critical for aquaculture production. Gonadal development is the basis of reproduction, and lipids, which are among the main nutrients required for gonadal development, directly affect reproduction. We investigated whether gonadal and intestinal lipid metabolism differed between male and female A. japonicus. Transcriptome analysis of the intestines of sexually mature male and female wild-caught individuals revealed differences in gene expression, with 27 and 39 genes being up-regulated in females and males, respectively. In particular, the expression of the fatty acid synthase gene was higher in males than in females. Metabolome analysis of the gonads identified 141 metabolites that were up-regulated and 175 metabolites that were down-regulated in the testes compared with the ovaries in the positive/negative mode of an LC-MS/MS analysis. A variety of polyunsaturated fatty acids were found at higher concentrations in the testes than in the ovaries. 16 s rDNA sequencing analysis showed that the composition and structure of the intestinal microbiota were similar between males and females. These results suggest that sex differences in intestinal metabolism of A. japonicus are not due to differences in the microbiota, and we speculate that gonadal metabolism may be related to intestinal morphology. This information might be useful in improving the reproductive efficiency of sea cucumbers in captivity.
Keywords: Gonads; Intestines; Lipid metabolism; Sea cucumber; Sex differences

COVID-19 Detection by Means of ECG, Voice, and X-ray Computerized Systems: A Review - Ribeiro, Pedro; Marques, João Alexandre Lobo; Rodrigues, Pedro Miguel (Bioengineering, 2023)
Since the beginning of 2020, Coronavirus Disease 19 (COVID-19) has attracted the attention of the World Health Organization (WHO). This paper looks into the infection mechanism, patient symptoms, and laboratory diagnosis, followed by an extensive assessment of different technologies and computerized models (based on Electrocardiographic signals (ECG), Voice, and X-ray techniques) proposed as a diagnostic tool for the accurate detection of COVID-19. The found papers showed high accuracy rate results, ranging between 85.70% and 100%, and F1-Scores from 89.52% to 100%. With this state-of-the-art, we concluded that the models proposed for the detection of COVID-19 already have significant results, but the area still has room for improvement, given the vast symptomatology and the better comprehension of individuals’ evolution of the disease.
Keywords: COVID-19; artificial intelligence; computerized diagnostic systems; image processing; signal processing

Effects of a High-Fat Diet on Intestinal and Gonadal Metabolism in Female and Male Sea Cucumber Apostichopus japonicus - Zhang, Shuangyan; Ru, Xiaoshang; Zhang, Libin; Gonçalves, David; Yang, Hongsheng; Xu, Jialei (Biology, 2023)
Parental nutrient reserves are directly related to reproductive performance in sea cucumbers. This study focused on the lipid requirements of male and female sea cucumbers Apostichopus japonicus during the reproductive stage and analyzed their physiological responses to a high-fat diet (HFD). The intestinal lipid metabolites and microbiome profile changed significantly in animals fed with the HFD, as given by an upregulation of metabolites related to lipid metabolism and an increase in the predominance of Proteobacteria in the microbiome, respectively. The metabolic responses of male and female sea cucumbers to the HFD differed, which in turn could have triggered sex-related differences in the intestinal microbiome. These results suggest that the lipid content in diets can be differentially adjusted for male and female sea cucumbers to improve nutrition and promote reproduction. This data contributes to a better understanding of the reproductive biology and sex differences of sea cucumbers.
Keywords: high-fat diet; intestinal microbes; physiological metabolic responses; sea cucumber; sex differences

An Exploratory Study of Macao's Role as an Arbitration Seat and Venue for Sino-Luso Commercial Disputes - Si, Leung Cheok; Diakite, Ansoumane Douty (Revista Opinião Jurídica (Fortaleza), 2023)
Objective: Over the past decade, arbitration has grown in popularity as a method of resolving commercial disputes worldwide. However, this practice is relatively new in Macao SAR. Recently, official plans were announced to make Macao as a seat of arbitration for commercial disputes between China and Portuguese-speaking countries (Hereinafter PSCs). This article is dedicated to explores the possibility of Macao undertaking and implementing such a role. Accordingly, this article addresses the following issues: What are the strengths and weaknesses of Macao as a seat and eventually as venue for hosting international commercial arbitration between Chinese and PSCs entrepreneurs?Methodology: A mixed-method approach of legal doctrinal and empirical research was used in this article. We first included a thorough study of the concept of arbitration followed by analysis of various legal journals and legislations, including Macao, China, and PSCs’ arbitration laws. An empirical research was then used to collect data by surveying and interviewing with both lawyers and arbitration practitioners from Macao, China and PSCs.Results: This article argues that the strength of Macao resides in the similarities between its legal system and that of the China and PSCs and the languages advantage (Chinese and Portuguese both official languages). In spite of this, arbitration is still relatively underutilized in the region, and there is a limited number of arbitrators and legal professionals with bilingual proficiency.Contributions: This article contributes to the identification of the opportunities and challenges that Macao faces in its potential future development as a seat/venue of arbitration between China and the PSCs.
Keywords: China; Macao; arbitraje internacional comercial; international commercial arbitration; participante y anfitrión de arbitraje; países de habla portuguesa; portuguese-speaking countries; seat and venue of arbitration

AN ANALYSIS OF CRITICAL MANAGERIAL CHALLENGES IN MACAU - Lampo, Alessandro (Revista Gestão em Análise, 2023)
Macau has long been considered to be an example of remarkable economic growth. With the opening of the gaming sector in 2002, the casino and hospitality sector flourished, creating employment opportunities but also imposing several challenges on managers. Since Macau endeavors to be positioned as the center for international business with Portuguese-speaking countries and a platform for trading with China’s Greater Bay Area (GBA), it becomes essential for international enterprises to understand the local dynamics. In light of the limited research available, this study aims to identify management challenges from the perspectives of senior executives in different industries based in Macau. Our findings point out that managers must contend with several issues, such as the lack of a skilled local talent pool, high turnover rates, employees' work attitudes, and a tightly controlled immigration policy. It is also imperative for international managers to nurture relationships and pay attention to the local culture. Our results suggest that Macau has to develop a highly skilled local workforce to attract international companies, while local organizations also have to create an attractive working environment to compete in the marketplace.
Keywords: Macau; casinos; greater bay area; management; managerial challenges

EFFECTIVENESS ANALYSIS OF WATERFALL AND AGILE PROJECT MANAGEMENT METHODOLOGIES – A CASE STUDY FROM MACAU'S CONSTRUCTION INDUSTRY - Marques, Joao Alexandre Lobo; Morais, João José Bragança dos Reis; Alves, José; Gonçalves, Marcus (Revista Gestão em Análise, 2023)
The adoption of project management techniques is a crucial decision for corporate governance in construction companies since the management of areas such as risk, cost, and communications is essential for the success or failure of an endeavor. Nevertheless, different frameworks based on traditional or agile methodologies are available with several approaches, which may create several ways to manage projects. The primary purpose of this work is to investigate the adequate project management methodology for the construction industry from a general perspective and consider a case study from Macau. The methodology considered semi-structured interviews and a survey comparing international and local project managers from the construction industry. The interviews indicate that most construction project managers still follow empirical methods with no specific methodology but consider the adoption of traditional waterfall approaches. In contrast, according to the survey, most project managers and construction managers agree that the project's efficacy needs to increase, namely in planning, waste minimization, communication increase, and focus on the Client's feedback. In addition, there seems to be a clear indication that agile methodology could be implemented in several types of projects, including hospitality development projects. A hybrid development approach based on the Waterfall and Agile methodologies as a tool for the project management area may provide a more suitable methodology for project managers to follow.
Keywords: PMBOK; agile; construction industry; project management methodologies

Monitoring PM2.5 at a Large Shopping Mall: A Case Study in Macao - Lei, Thomas M. T.; Chan, Yan W. I.; Mohd Nadzir, Mohd Shahrul (Processes, 2023)
Employees work long hours in an environment where the ambient air quality is poor, directly affecting their work efficiency. The concentration of particulate matters (PM) produced by the interior renovation of shopping malls has not received particular attention in Macao. Therefore, this study will investigate the indoor air quality (IAQ), in particular of PM2.5, in large-scale shopping mall renovation projects. This study collected on-site PM data with low-cost portable monitoring equipment placed temporarily at specific locations to examine whether the current control measures are appropriate and propose some improvements. Prior to this study, there were no measures being implemented, and on-site monitoring to assess the levels of PM2.5 concentrations was non-existent. The results show the highest level of PM2.5 recorded in this study was 559.00 μg/m3. Moreover, this study may provide a reference for decision-makers, management, construction teams, design consultant teams, and renovation teams of large-scale projects. In addition, the monitoring of IAQ can ensure a comfortable environment for employees and customers. This study concluded that the levels of PM2.5 concentration have no correlation with the number of on-site workers, but rather were largely influenced by the processes being performed on-site.
Keywords: air pollution; construction dust; health exposure; indoor air quality; particulate matter

Quantification of insecticides in commercial seafood sold in East Asian markets: risk assessment for consumers - Ivorra, Lucia; Cardoso, Patricia G.; Chan, Shek Kiu; Cruzeiro, Catarina; Tagulao, Karen (Environmental Science and Pollution Research, 2023)
The extraction of 21 insecticides and 5 metabolites was performed using an optimized and validated QuEChERS protocol that was further used for the quantification (GC–MS/MS) in several seafood matrices (crustaceans, bivalves, and fish-mudskippers). Seven species, acquired from Hong Kong and Macao wet markets (a region so far poorly monitored), were selected based on their commercial importance in the Indo-Pacific region, market abundance, and affordable price. Among them, mussels from Hong Kong, together with mudskippers from Macao, presented the highest insecticide concentrations (median values of 30.33 and 23.90 ng/g WW, respectively). Residual levels of fenobucarb, DDTs, HCHs, and heptachlors were above the established threshold (10 ng/g WW) for human consumption according to the European and Chinese legislations: for example, in fish-mudskippers, DDTs, fenobucarb, and heptachlors (5-, 20- and tenfold, respectively), and in bivalves, HCHs (fourfold) had higher levels than the threshold. Risk assessment revealed potential human health effects (e.g., neurotoxicity), especially through fish and bivalve consumption (non-carcinogenic risk; ΣHQLT > 1), and a potential concern of lifetime cancer risk development through the consumption of fish, bivalves, and crustaceans collected from these markets (carcinogenic risk; ΣTCR > 10–4). Since these results indicate polluted regions, where the seafood is collected/produced, a strict monitoring framework should be implemented in those areas to improve food quality and safety of seafood products.
Keywords: Bivalves; Crustaceans; Health risk assessment; Mudskippers; Organochlorine pesticides

Macau 2.0: New Gaming Law and its Implications for Casino Market - Ho, Hong-Wai; Phillips, Jenny (Gaming Law Review, 2023)
This article discusses the new gaming law in Macau with emphasis on the critical aspects concerning the gaming operators, concession regime, and other regulatory obligations.1 Thanks to the gaming liberalization commenced in 2001,2 Macau has experienced tremendous economic growth. The past two decades have seen the rapid development of large-scale integrated resorts, and Macau now ranks among the world's major gaming jurisdictions.3 Policy and regulatory challenges have also emerged along with the growth of the junket-driven VIP business in casinos.4 With the recent amendment of Law No. 16/2001 and the subsequent enactment of Law No. 16/2022, Macau has strengthened the legal underpinnings of its system of gaming regulation to oversee various groups involved in casinos and their industry practices. The present study is among the first to review the scope and impact of the revised gaming law, and associated managerial and operational implications for Macau casinos. Topics covered include policy directions, concession requirements, industry participants, gaming taxes, and fair business practices. This study could provide insights into the “Macau 2.0” project and how casinos are to be operated and managed over the next decade. This article could also provide practical guidance for policy makers charged with formulating gaming policy and regulation in other jurisdictions.
Keywords: Macao; concession; economic diversification; gaming regulation; junket; operation

A model of integrating convolution and BiGRU dual-channel mechanism for Chinese medical text classifications - Li, Xiaoli; Zhang, Yuying; Jin, Jiangyong; Sun, Fuqi; Li, Na; Liang, Shengbin (PLOS ONE, 2023)
Recently, a lot of Chinese patients consult treatment plans through social networking platforms, but the Chinese medical text contains rich information, including a large number of medical nomenclatures and symptom descriptions. How to build an intelligence model to automatically classify the text information consulted by patients and recommend the correct department for patients is very important. In order to address the problem of insufficient feature extraction from Chinese medical text and low accuracy, this paper proposes a dual channel Chinese medical text classification model. The model extracts feature of Chinese medical text at different granularity, comprehensively and accurately obtains effective feature information, and finally recommends departments for patients according to text classification. One channel of the model focuses on medical nomenclatures, symptoms and other words related to hospital departments, gives different weights, calculates corresponding feature vectors with convolution kernels of different sizes, and then obtains local text representation. The other channel uses the BiGRU network and attention mechanism to obtain text representation, highlighting the important information of the whole sentence, that is, global text representation. Finally, the model uses full connection layer to combine the representation vectors of the two channels, and uses Softmax classifier for classification. The experimental results show that the accuracy, recall and F1-score of the model are improved by 10.65%, 8.94% and 11.62% respectively compared with the baseline models in average, which proves that our model has better performance and robustness.
Keywords: Convolution; Deep learning; Machine learning; Memory recall; Neural networks; Recurrent neural networks; Semantics; Syntax

An Improved Dual-Channel Deep Q-Network Model for Tourism Recommendation - Liang, Shengbin; Jin, Jiangyong; Ren, Jia; Du, Wencai; Qu, Shenming (Big Data, 2023)
Keywords: context-aware; deep reinforcement learning; dual-channel; tourism recommendation

A reserva territorial dos aborígenes potiguaras do Brasil: um locus simbólico - Simões, José Manuel (Revista Internacional em Língua Portuguesa, 2023)
The various volumes coordinated by Pierre Nora to pursue a history of the places of memory in France have become a multidisciplinary theoretical reference for those who, like us, seek to reconstruct the memories with which the land of the Potiguara aborigines of Brazil is organized today. In the introduction to the voluminous work that he directed for eight years, Nora explained his epistemic understanding of the notion of “places of memory”, stressing that a “lieu de mémoire” is any significant entity that, material or immaterial in nature, through a human will or the wear and tear of time, has become a symbolic element of a community's memorial heritage. The French historian also added that, since memory is the fundamental structure of this generally lengthy process, it was convenient to understand it as a phenomenon of emotions and magic that only accommodates the facts that feed it. Strictly speaking, memory is always vague, and reminiscent, stirring both general impressions and fine symbolic details. Furthermore, memory is always vulnerable to transference, repressed and imagined memories, censorship, and all kinds of projections. (Nora, 1984). In this article, we try to understand that the places of memory are also almost always what comes to us, stays, and selects the past. The reserve where they live appears as a symbolic locus to which the Potiguara aborigines cling with all their strength to preserve what remains of their past.
Keywords: aborígenes Potiguara; censuras; locus simbólico; lugares de memória; preservar o passado; reconstrução das memórias

Relationship between Student Teachers' Beliefs and Practices on Early Chinese Literacy Instruction - Sun, Chunrong; Ho, Ka Lee Carrie (Universal Journal of Educational Research, 2023)
This study explores the relationship between student teachers' beliefs and practices in early Chinese literacy instruction. Semi-structured interviews, classroom observation, and document analysis were conducted with six student teachers during their teaching practices. Findings indicated that the student teachers believed explicitly teaching literacy skills and imperceptible acquisition of literacy abilities through communication and meaning-making processes are essential in Chinese early literacy learning. However, they mainly taught Chinese literacy skills in their practices, which means the student teachers still needed to practice what they preached fully. The study suggests that possible reasons for the discrepancies include 'direct teaching' and 'rote learning' might be much easier for student teachers to design and conduct a lesson. Student teachers have limited abilities and experiences in conducting an ideal lesson, and the kindergarten curriculum and onsite supervisors highly influenced their teaching practices. The findings from this study suggested that more operational activities (such as designing lesson plans and conducting micro-teaching) should be used during pre-service training. Furthermore, the communication of educational beliefs between the university supervisor and the onsite supervisor should be strengthened.

China’s Aid policy approach to Poverty Alleviation in the recipient country: A Case study of the Republic of Guinea - Diakite, Ansoumane Douty (Journal of Social Studies (JSS), 2023)
This paper examines the extent to which China’s aid policies integrate poverty alleviation as a goal of their aid in general, particularly in Guinea. More specifically, the paper analyzed how aid donors focus on poverty alleviation and which policies and mechanisms are in place to address poverty in the countries receiving aid. Regarding the methodology, the author collected data from secondary sources, including government declarations of donors, policy documents at both the donor and recipient levels, as well as from scholarly publications. The following findings resulted from study:  China’s aid policies have progressively incorporated poverty alleviationobjectives and identified sectors for intervention against poverty. However, the limitations of China approach to poverty is that China adopts a top-down approach to poverty reduction and lacks of an impact evaluation mechanism based on poverty alleviation.
Keywords: Aid policy; China; Guinea; Poverty alleviation; Strategy

Neuromarketing and Global Branding Reaction Analysis Based on Real-Time Monitoring of Multiple Consumer's Biosignals and Emotions - Goncalves, Marcus; Lobo Marques, Joao Alexandre; Silva, Bruno Riccelli Santos; Luther, Valorie; Hayes, Sydney (Journal of International Business and Management, 2023)
Consumers' selections and decision-making processes are some of the most exciting and challenging topics in neuromarketing, sales, and branding. From a global perspective, multicultural influences and societal conditions are crucial to consider. Neuroscience applications in international marketing and consumer behavior is an emergent and multidisciplinary field aiming to understand consumers' thoughts, reactions, and selection processes in branding and sales. This study focuses on real-time monitoring of different physiological signals using eye-tracking, facial expressions recognition, and Galvanic Skin Response (GSR) acquisition methods to analyze consumers' responses, detect emotional arousal, measure attention or relaxation levels, analyze perception, consciousness, memory, learning, motivation, preference, and decision-making. This research aimed to monitor human subjects' reactions to these signals during an experiment designed in three phases consisting of different branding advertisements. The nonadvertisement exposition was also monitored while gathering survey responses at the end of each phase. A feature extraction module with a data analytics module was implemented to calculate statistical metrics and decision-making supporting tools based on Principal Component Analysis (PCA) and Feature Importance (FI) determination based on the Random Forest technique. The results indicate that when compared to image ads, video ads are more effective in attracting consumers' attention and creating more emotional arousal.

The Hawking Radiation in Massive Gravity: Path Integral and the Bogoliubov Method - Arraut, Ivan; Segovia, Carlos; Rosado, Wilson (Universe, 2023)
We prove the consistency of the different approaches for deriving the black hole radiation for the spherically symmetric case inside the theory of Massive Gravity. By comparing the results obtained by using the Bogoliubov transformations with those obtained by using the Path Integral formulation, we find that in both cases, the presence of the extra-degrees of freedom creates the effect of extra-particles creation due to the distortions on the definitions of time defined by the different observers at large scales. This, however, does not mean extra-particle creation at the horizon level. Instead, the apparent additional particles perceived at large scales emerge from how distant observers define their time coordinate, which is distorted due to the existence of extra-degrees of freedom.
Keywords: Bogoliubov transformation method; Hawking radiation; Massive Gravity; Path Integral method; extra-degrees of freedom

Diagnóstico à literacia da informação de estudantes de ensino superior: um estudo de caso em Macau - Chan, Emily; Sanches, Tatiana (Actas do Congresso Nacional de Bibliotecários, Arquivistas e Documentalistas, 2023)
O presente estudo faz parte de uma investigação mais alargada que pretende i) estudar, numa população estudantil de ensino superior, as suas necessidades e comportamento perante a informação e ii) desenvolver um programa de formação em literacia da informação, integrando este conhecimento e os contributos dos diversos intervenientes (estudantes, docentes, bibliotecários). Sabemos hoje que a integração da literacia da informação nas aprendizagens melhora o desempenho dos estudantes e que, por esse motivo, os bibliotecários académicos podem desempenhar um papel importante ao colaborarem no desenho e formação de programas nestas áreas. Esta comunicação apresenta a primeira fase deste estudo. Trata-se da aplicação de um inquérito por questionário a uma população de estudantes de graduação, no ensino superior, em Macau. Os resultados demonstram as perceções dos estudantes relativamente às suas necessidades de informação, bem como o uso dos recursos informativos preferidos na prossecução dos seus estudos. A formação destes estudantes na pesquisa, recuperação, análise e uso da informação parece ser essencial. A construção de programas de formação em literacia da informação deve ser concebida à medida, recorrendo-se a um diagnóstico próximo e efetivo. A par, é importante continuar a desenvolver ambientes físicos e virtuais que disponibilizem informação credível e que deem resposta às necessidades informacionais dos que os utilizam, apoiando a aprendizagem.
Keywords: Estudantes

The role of environmental concern and technology show-off on electric vehicles adoption: the case of Macau - Lampo, Alessandro; Silva, Susana C.; Duarte, Paulo (International Journal of Emerging Markets, 2023)
Purpose Research on battery electric vehicles (BEVs) has typically considered environmental concern a key determinant of behavioral intention that leads individuals to prefer electric vehicles. This paper challenges this assumption and argues that technology frameworks may require new variables to capture consumers' preferences. A UTAUT2-based study has been developed to assess the role of environmental concern in the BEVs context and put forward the technology show-off (TS) concept to explain the technology's acceptance. Design/methodology/approach A quantitative and cross-sectional look at behavioral intention is adopted. The study uses structural equation modeling to analyze a sample of 236 Macau residents to determine the relevance of the factors behind the choice to adopt BEVs. Findings The findings indicate that environmental concern and price may be relevant to explain behavioral intention to adopt the BEVs technology. Furthermore, the UTAUT2 framework seems to benefit from adding new variables, with TS playing a pertinent role in explaining technology acceptance. Social implications The findings show that environmental concern fails to build an argument for the shift to full electric mobility and promote the desired behavioral change toward adopting BEVs. Herein lies the necessity to consider new variables that can better describe the characteristics of modern society. Originality/value This paper proposes the TS construct, combining visibility and trialability as significant determinants of behavioral intention to use technology. The study also stresses the need to reconsider the role of environmental concerns' impact on consumer decision-making.

China’s Approach to Sustainable Development in Free Trade Agreements - Wei, Dan; Rafael, Ângelo Patrício (Law and Development Review, 2023)
The question of how to adequately integrate environment and labor provisions in free trade agreements is still a difficult one for both States and academicians. This article explores China’s approach to environment and labor issues in free trade agreements. For reference and comparison, it relies on the European Union’s and the United States’ approaches in their respective FTAs. The article identifies China’s preference for a case-by-case approach to the inclusion of environmental chapters in its FTAs. Additionally, in most FTAs it avoids to include provisions on labor standards. These two preferences represent major divergences from the European Union’s and the United States’ approaches, characterized by inclusion of chapters on environment and labor in all their modern FTAs. The article also finds that China’s FTAs rely solely on consultations and cooperation for the implementation of environmental and labor provisions, within the framework of Joint Committees and avoid the inclusion of civil society mechanisms. Moreover, resolution of disputes relies exclusively on consultations, in a diverse procedure than the one applicable to trade disputes. Despite alignment with the European Union model, this is another major point of divergence with the United States’ model, which applies the same enforcement mechanism for both environment and labor issues and trade issues and includes the possibility of applying sanctions. Finally, the article concludes that China’s options with regards to the treatment of environment and labor concerns in its free trade agreements aligns with both its domestic governance approach and its approach to international cooperation.
Keywords: China; environment and trade; free trade agreements; labor and trade; sustainable development

Enhancing Health and Public Health through Machine Learning: Decision Support for Smarter Choices - Rodrigues, Pedro Miguel; Madeiro, João Paulo; Marques, João Alexandre Lobo (Bioengineering, 2023)
In recent years, the integration of Machine Learning (ML) techniques in the field of healthcare and public health has emerged as a powerful tool for improving decision-making processes [...]
Keywords: n/a

A Multi-Channel Text Sentiment Analysis Model Integrating Pre-training Mechanism - Liang, Shengbin; Jin, Jiangyong; Du, Wencai; Qu, Shenming (Information Technology and Control, 2023)
The number of tourist attractions reviews, travel notes and other texts has grown exponentially in the Internet age. Effectively mining users’ potential opinions and emotions on tourist attractions, and helping to provide users with better recommendation services, which is of great practical significance. This paper proposes a multi-channel neural network model called Pre-BiLSTM combined with a pre-training mechanism. The model uses a combination of coarse and fine- granularity strategies to extract the features of text information such as reviews and travel notes to improve the performance of text sentiment analysis. First, we construct three channels and use the improved BERT and skip-gram methods with negative sampling to vectorize the word-level and vocabulary-level text, respectively, so as to obtain more abundant textual information. Second, we use the pre-training mechanism of BERT to generate deep bidirectional language representation relationships. Third, the vectors of the three channels are input into the BiLSTM network in parallel to extract global and local features. Finally, the model fuses the text features of the three channels and classifies them using SoftMax classifier. Furthermore, numerical experiments are conducted to demonstrate that Pre-BiLSTM outperforms the baselines by 6.27%, 12.83% and 18.12% in average in terms of accuracy, precision and F1-score.
Keywords: Pre-training mechanism

LatinX in AI research - Banda, Juan M.; Ruiz-Garcia, Ariel; Montoya, Laura N.; Arraut, Ivan (Neural Computing and Applications, 2023)
We are delighted to present this special issue editorial for Neural Computing and Applications special issue on LatinX in AI research. This special issue brings together a collection of articles that explore machine learning and artificial intelligence research from various perspectives, aiming to provide a comprehensive and in-depth understanding of what LatinX researchers are working on in the field. In this editorial, we will introduce the overarching theme of the special issue, highlight the significance of the selected papers, and offer insights into the contributions made by the authors. The LatinX in AI organization was launched in 2018, with leaders from organizations in Artificial Intelligence, Education, Research, Engineering, and Social Impact with a purpose to together create a group that would be focused on “Creating Opportunity for LatinX in AI.” The main goal is to increase the representation of LatinX professionals in the AI industry. LatinX in AI Org and programs are volunteer-run and fiscally sponsored by the Accel AI Institute, 501(c)3 Non-Profit.

Gauge symmetries and the Higgs mechanism in Quantum Finance - Arraut, Ivan (Europhysics Letters, 2023)
By using the Hamiltonian formulation, we demonstrate that the Merton-Garman equation emerges naturally from the Black-Scholes equation after imposing invariance (symmetry) under local (gauge) transformations over changes in the stock price. This is the case because imposing gauge symmetry implies the appearance of an additional field, which corresponds to the stochastic volatility. The gauge symmetry then imposes some constraints over the free parameters of the Merton-Garman Hamiltonian. Finally, we analyze how the stochastic volatility gets massive dynamically via Higgs mechanism.

Influencing Companies’ Green Governance Through the System of Legal Liability for Environmental Infractions in China and Brazil: Lighting the Way Toward BRICS Cooperation - Wei, D.; Rafael, Ângelo Patrício (BRICS Law Journal, 2023)
Peer-rewieved journal

Acceptance of Insects as Food: An Exploratory Study of Young Consumers in Macau - Lampo, Alessandro; Sun, Hou Tong (Indian Journal of Entomology, 2023)
Substitute foods are increasingly popular to reduce our environmental footprint and promote food security. As the world population is expected to grow and food resources become scarce, insects as food have recently gained attention as a viable alternative. In the present study, a model grounded on the Theory of Planned Behavior (TPB) is proposed and analyzed through structural equation modeling software (SmartPLS) to assess consumers intentions toward insects as food. Except for subjective norm, both attitude and perceived behavioral control were key determinants of intention and, in turn, of actual use behaviour. Despite insects being consumed in nearly 1/4 of the sample (for instance in Chinese medicine), the study found that respondents were on average relatively unwilling to use them as a dietary habit. Also, it appeared that men were more likely to consume insects as food than women. The insights of our study have important implications for practitioners and policymakers seeking to promote sustainable nutritional practices among consumers. This study is particularly relevant for Macau, as the city positions itself as a "UNESCO Creative City of Gastronomy" with the aim to develop internationally a unique and sustainable food image.

A medical text classification approach with ZEN and capsule network - Liang, Shengbin; Sun, Fuqi; Sun, Haoran; Chen, Tingting; Du, Wencai (The Journal of Supercomputing, 2023)
Text classification is an important topic in natural language processing, with the development of social network, many question-and-answer pairs regarding health-care and medicine flood social platforms. It is of great social value to mine and classify medical text and provide targeted medical services for patients. The existing algorithms of text classification can deal with simple semantic text, especially in the field of Chinese medical text, the text structure is complex and includes a large number of medical nomenclature and professional terms, which are difficult for patients to understand. We propose a Chinese medical text classification model using a BERT-based Chinese text encoder by N-gram representations (ZEN) and capsule network, which represent feature uses the ZEN model and extract the features by capsule network, we also design a N-gram medical dictionary to enhance medical text representation and feature extraction. The experimental results show that the precision, recall and F1-score of our model are improved by 10.25%, 11.13% and 12.29%, respectively, compared with the baseline models in average, which proves that our model has better performance.
Keywords: Capsule network; Medical text classification; Text mining; ZEN model

Death of a salesman? the new junket regulation and practice in macau - Ho, Hong-Wai; Phillips, Jenny (Gaming Law Review, 2023)
This review article is among the first to examine the new junket regulations in the Macau gaming industry. Particular emphasis is on the legal and regulatory framework governing the junket activity of gaming promoters and their associates. The recent changes to Macau gaming laws have resulted in stronger licensing requirements for local junket participants and precipitated the collapse of the VIP room system in casinos. Furthermore, this article highlights the policy and managerial implications of the current junket environment for the gaming industry in Macau and possibly other regional gaming jurisdictions. The effects of the new legal environment for Macau junkets could also provide insights into the implementation of similar legislation in other jurisdictions.
Keywords: Macao; VIP room; gambling; gaming regulation; international gaming; junket operation

The Tully-Fisher law and dark matter effects derived via modified symmetries - Arraut, Ivan (Europhysics Letters, 2023)
In any physical system, when we move from short to large scales, new spacetime symmetries emerge which help us to simplify the dynamics of the system. In this letter we demonstrate that certain variations on the symmetries of general relativity at large scales generate the effects equivalent to dark matter ones. In particular, we reproduce the Tully-Fisher law, consistent with the predictions proposed by MOND. Additionally, we demonstrate that the dark matter effects derived in this way are consistent with the predictions suggested by MOND, without modifying gravity.

Neurofinance: Exploratory Analysis Stock Trader's Decision-Making Process by Real-Time Monitoring of Emotional Reactions - Hsu, Hsin-Tzu; Marques, João Alexandre Lobo (European Conference on Management Leadership and Governance, 2023)
Human emotions can be associated with decision-making, and emotions can generate behaviors. Due to the fact that it could be biased and exhaustively complex to examine how human beings make choices, it is necessary to consider relevant groups of study, such as stock traders and non-traders in finance. This work aims to analyze the connection between emotions and the decision-making process of investors and non-investors submitted to the same set of stimuli to understand how emotional arousal might dictate the decision process. Neuroscience monitoring tools such as Real-Time Facial Expression Analysis (AFFDEX), Eye-Tracking, and Galvanic Skin Response (GSR) were adopted to monitor the related experiments of this paper and its accompanying analysis process. Thirty-seven participants attended the study, 24 were classified as stock traders, and 13 were non-traders; the mean age for the groups was 35 and 25, respectively. The designed experiment initially disclosed a thought-provoking result between the two groups under the certainty and risk-seeking prospect theory; there were more risk-takers among non-investors at 75%, while investors were inclined toward certainty at 79.17%. The implication could be that the non-investing individuals were less complex in thought and therefore pursued higher returns besides a high probability of losing the game. In addition, the automatic emotion classification system indicates that when non-investors confronted a stock trending chart beyond their acquaintance or knowledge, they were psychologically exposed to fear, anger, sadness, and surprise. On the contrary, investors were detected with disgust, joy, contempt, engagement, sadness, and surprise, where sadness and surprise overlapped in both parties. Under time pressure conditions, 54.05% of investors or non-investors tend to make decisions after the peak(s) of emotional arousal. Variations were found in the deciding points of the slopes: 2.70% were decided right after the peak(s), 37.84% waited until the emotions turned stable, and 13.51% were determined as the emotional indicators started to slide downwards. Several combinations of emotional responses were associated with decisions. For example, negative emotions could induce passive decision-making, in this case, to sell the stock; nevertheless, it was also examined that as the slope slipped downwards to a particular horizontal point, the individuals became more optimistic and selected the "BUY" option. Future works may consider expanding the study to larger sample size, different demographic groups, and other biometrics for further analysis and conclusions.

Leadership and Neurosciences - The analysis of emotional arousal during decision-making processes with decision-makers exposed to acute stress - Marques, Joao Alexandre Lobo (European Conference on Management Leadership and Governance, 2023)
Corporate leaders are constantly dealing with stress in parallel with continuous decision-making processes. The impact of acute stress on decision-making activities is a relevant area of study to evaluate the impact of the decisions made, and create tools and mechanisms to cope with the inevitable exposure to stress and better manage its impact. The intersection of leadership and neurosciences techniques is called Neuroleadership. In this work, an experiment is proposed to detect and measure the emotional arousal of two groups of business professionals, divided into two groups. The first one is the intervention/stress group, n=30, exposed to stressful conditions, and the control group, n=14, not exposed to stress. The participants are submitted to a sequence of computerized stimuli, such as watching videos, answering survey questions, and making decisions in a realistic office environment. The Galvanic Skin Response (GSR) biosensor monitors emotional arousal in real-time. The experiment design implemented stressors such as visual effects, defacement, unfairness, and time-constraint for the intervention group, followed by decision-making tasks. The results indicate that emotional arousal was statistically significantly higher for the intervention/stress group, considering Shapiro and Mann-Whitney tests. The work indicates that GSR is a reliable stress detector and may be useful to predict negative impacts on executive professionals during decision-making activities.

Neuromarketing: Evaluating Consumer Emotions and Preferences to Improve Business Marketing Management - Zeng, Ian Mei; Marques, João Alexandre Lobo (European Conference on Management Leadership and Governance, 2023)
The invention of neuroscience has benefited medical practitioners and businesses in improving their management and leadership. Neuromarketing, a field that combines neuroscience and marketing, helps businesses understand consumer behaviour and how they respond to advertising stimuli. This study aims to investigate the consumer purchase intention and preferences to improve the marketing management of the brand, based on neuroscientific tools such as emotional arousal using Galvanic Skin Response (GSR) sensors, eye-tracking, and emotion analysis through facial expressions classification. The stimuli for the experiment are two advertisement videos from the Macau tea brand “Guanding Teahouse” followed by a survey. The experiment was conducted on 40 participants. 76.2% of participants that chose the same product in the first survey responded with the same choice of products in the second survey. The GSR peaks in video ad 1 measured a total of 60. On the other hand, video ad 2 counted a total of 55 GSR peaks. The emotions in ad1 and ad2 have similar responses, with an attention percentage of 76%. The results showed that ad1 has a higher engagement time of 11.1% and ad2 has 9.6%, but only 19 of the respondent’s conducted engagement in video ad1, and 31 showed engagement in video ad2. The results demonstrated that although ad 1 has higher engagement rates, the respondents are more attracted to video ad 2. Therefore, ad2 has better marketing power than ad 1. Overall, this study bridges the gap of no previous research on measuring tea brand advertisements with the neuroscientific method. The results provide valuable insights for marketers to develop better advertisements and marketing campaigns and understand consumer preferences by personalising and targeting advertisements based on consumers' emotional responses and behaviour of consumers' purchase intentions. Future research could explore advertisements targeting different demographics.

Perspectives of Local Communities on the Impact of Chinese Aid: A Case Study of China's Aid Projects in the Education Sector in Guinea - Diakite, Ansoumane Douty (Journal of Globalization Studies, 2023)
China's re-emergence as an aid donor has attracted the attention and criticism from Western donors, academia, and the media. In contrast to traditional donors, China's aid has been portrayed as anti-poverty aid, mainly due to its combination with other instruments, such as investment, and the absence of any political or economic conditions. This paper examines the impact of Chinese aid projects in Guinea's education sector from the perspective of the beneficiaries. The author collected data from both primary (interviews) and secondary (document analysis) sources. The present study concludes that China's aid projects in the education sector have received both positive and negative feedback, mainly because the recipients' needs have not been appropriately targeted. This study contributes to the literature on China's role in Africa. More specifically, it discusses the conditions for aid effectiveness in the field of education. Moreover, in the context of the globalization of aid practices, the study proposes best practices for China to adopt in order to improve the practices of its aid delivery. The novelty of this study lies in the methodology (qualitative method) used to understand China's aid from the perspective of the beneficiaries of its aid.

Static recording apparatus for soundscape analysis in Macau - Estadieu, Gerald; Cheung, Yin Yan; Pestana, Pedro Duarte; Barbosa, Alvaro (INTER-NOISE and NOISE-CON Congress and Conference Proceedings, 2023)
The concept of Soundscape was initially proposed to study the relationship between humans and their sonic environment. It has gathered momentum from academia to environmentalists and policymakers throughout the years. The study and characterisation of Soundscapes can be complex as it tries to take a holistic and qualitative approach rather than simply quantifying sound pressure levels. This paper introduces a comprehensive Soundscape study process in an ongoing research project in Macao (China), a small territory (32.9 km2) and one of the most densely populated areas in the world. The paper seeks to show a first version of a technical solution to systematically capture the local soundscape, analyse it, classify it, and ultimately deliver a dataset library and the intangible qualities of the environmental sound. This implementation, including technical documentation, code, and sound library with strong labelling, is presented under an open-source license to encourage future collaborative research. Finally, the paper offers suggestions on further developing the apparatus to reach a systematic and near real-time soundscape analysis with the development of a machine learning system.

Higher Education students' perceptions towards Information Literacy: a study in Macau - Sanches, Tatiana; Chan, Emily (Ibersid: revista de sistemas de información y documentación, 2023)
Integrating information literacy into learning improves student performance and, for that reason, academic librarians can play a significant role by collaborating in the design and training programs in these areas. In Macao, there is no known study on the information literacy performance of higher education students, so we seek to diagnose this area. For that purpose, a survey was applied to higher education students to assess students' perception of information literacy and their self-characterization regarding the use of resources and the type of skills needed for academic work. A semi-structured interview was also carried out with teachers about the same reality. Students perceive themselves to have a low level of confidence in the performance of their academic tasks, which affects their fulfilment. Faculty are aligned with this diagnosis, revealing the students’ weaknesses in the information search and presentation. Overall, information needs are evident among students as also is the use of preferred information resources in pursuit of their studies. The training aimed at students in search, retrieval, analysis, and use of information seems to be essential, which is why the construction of a tailormade training program in Information Literacy is anticipated.
Keywords: Macao

The Role of the Volatility in the Option Market - Arraut, Ivan; Lei, Ka-I. (AppliedMath, 2023)
We review some general aspects about the Black–Scholes equation, which is used for predicting the fair price of an option inside the stock market. Our analysis includes the symmetry properties of the equation and its solutions. We use the Hamiltonian formulation for this purpose. Taking into account that the volatility inside the Black–Scholes equation is a parameter, we then introduce the Merton–Garman equation, where the volatility is stochastic, and then it can be perceived as a field. We then show how the Black–Scholes equation and the Merton–Garman one are locally equivalent by imposing a gauge symmetry under changes in the prices over the Black–Scholes equation. This demonstrates that the stochastic volatility emerges naturally from symmetry arguments. Finally, we analyze the role of the volatility on the decisions taken by the holders of the options when they use the solution of the Black–Scholes equation as a tool for making investment decisions.
Keywords: Black–Scholes equation; Merton–Garman equation; decision theory; option price; stock market; volatility

Unsettling Exiles: Chinese Migrants in Hong Kong and the Southern Periphery During the Cold War Angelina Y. Chin. New York: Columbia University Press, 2023. 320 pp., $35.00; £30.00, ISBN 9780231209991. - Roberts, Priscilla (The China Quarterly, 2023)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0305741023001406/resource/name/firstPage-S0305741023001406a.jpg

Comment on ''Generalized James' effective Hamiltonian method'' - Rosado, W.; Arraut, Ivan (Physical Review A, 2023)
In the paper carried out by Wenjun et al. [Phys. Rev. A 95, 032124 (2017)], a generalization of the James effective dynamics theory based on a first version of the James method was presented. However, we contend that this is not a very rigorous way of deriving the effective third-order expansion for an interaction Hamiltonian with harmonic time-dependence. In fact, here we show that the third-order Hamiltonian obtained by Wenjun et al. is not Hermitian for general situations when we consider time dependence. Its non-Hermitian nature arises from the foundation of the theory itself. In this comment paper, the most general expression of the effective Hamiltonian expanded up to third order is obtained. Our derived effective Hamiltonian is Hermitian even in situations where we have time dependence.

Categorization of Foreign Aid Donors: A Critical Review of the Criteria in Light of China's Reemergence as a Donor - Diakite, Ansoumane Douty; Marques, João Alexandre Lobo (Journal of Global South Studies, 2023)
Over the past several decades, the dichotomy between traditional and emerging donors has been based upon the notion that emerging donors (such as China) support authoritarian regimes and use foreign aid to pursue their economic interests at the expense of the poor in the recipient countries. Accordingly, Western donors, media, and scholars portray Chinese aid as non-poverty-focused. This study aims to review and analyze whether the dichotomy between traditional and emerging donors is still relevant in the current aid system and to propose a new and rigorous criterion for recategorizing donors. In terms of methodology, this study relies on secondary data, including scholarly works on traditional and emerging donors and foreign aid policy documents. Conclusions based on the research indicate that the divide between traditional donors and (re)emerging donors is becoming more ambiguous. The literature review indicates that the two donors’ aids had a mixed impact and that their approaches were similar. This paper highlights the importance of developing different recategorization criteria depending on the impact of aid.
Keywords: China and development assistance committee donors; aid policies; categorization of donors; sustainable development goal; traditional and emerging donors

A Pilot Study for Measuring Complex Problem-Solving in Jordan: Feasibility, Construct Validity, and Behavior Pattern Analyses - Alrababah, Saleh Ahmad; Wu, Hao; Molnár, Gyöngyvér (Sage Open, 2024)
In the 21st century, complex problem-solving (CPS) serves as a key indicator of educational achievement. However, the elements of successful CPS have not yet been fully explored. This study investigates the role of strategic exploration and different problem-solving and test-taking behaviors in CPS success, using logfile data to visualize and quantify students’ problemsolving behavior on 10 CPS problems with different characteristics and levels of difficulty. Additionally, in the present study, we go beyond the limits of most studies that focus on students’ problem-solving behavior pattern analyses in European cultures and education systems to examine Arabic students’ CPS behavior. The results show that computer-based assessments of CPS are feasible and valid in Jordanian higher education. The findings also confirm the structural validity of CPS, indicating that the processes of knowledge acquisition (KAC) and knowledge application (KAP) can be distinguished and separated in the problem-solving process. Large differences were identified in students’ test-taking behavior in terms of the efficacy of their exploration strategy. We identified four latent classes based on the students’ exploration strategy behavior. The study thus leads to a better understanding of how students solve problems and behave during the problem-solving process in uncertain situations.

Reply to the "Comment on The Tully-Fisher law and dark matter effects derived via modified symmetries" by I. Arraut. - Arraut Guerrero, Ivan (Europhysics Letters, 2024)
It has been claimed in \cite1, that the idea proposed in \cite2 has certain mistakes based on arguments of energy conditions and others. Additionally, some of the key arguments of the paper are criticized. Here we demonstrate that the results obtained in \cite2 are correct and that there is no violation of any energy condition. The statements claimed in \cite1 are based on three things: 1). Misinterpretation of the metric solution. 2). Language issues related to the physical quantities obtained in \cite1, where the authors make wrong interpretations about certain results over the geometry proposed in \cite2. 3). Non-rigorous evaluations of the vacuum condition defined via the result over the Ricci tensor R_μν=0.

Matteo Ricci's teaching on the goodness of human nature: its Thomistic and neo‐Confucian sources - Cai, Yilun (The Heythrop Journal, 2024)
Abstract The Jesuit missionary Matteo Ricci's teaching on the goodness of human nature in The True Meaning of the Lord of Heaven represents the fruit of the first encounter between Catholicism and Confucianism. This article will consider the Thomistic and neo‐Confucian sources in Ricci's enunciation of the Catholic doctrine on the goodness of human nature in this Chinese catechism. It will illustrate that Ricci developed his teaching, which is fundamentally Thomistic, with the help of terminology borrowed from the Chinese philosophical tradition. His distinction between the good of nature and the good of virtue leads to prioritising the cultivation of human nature. Ricci's teaching reflects the early modern Jesuits’ appreciation of human freedom. It also displays a Catholic reaction to the sixteenth‐century neo‐Confucian intellectual trend that ignored the importance of moral cultivation.

Career trajectory and cross-system mobility: Career planning of doctoral students in Macao - Ge, Yun (Higher Education Quarterly, 2024)
This study investigates career trajectory and work locations of doctoral students trained in Macao and analyses how their career paths are shaped by perceived macro-level factors. Respondents from four applied disciplinary areas were selected for semi-structured in-depth interviews. Research results show that doctoral students who graduated from Macao higher education institutions enjoy good career prospects in Mainland China. Their competitiveness in the research-related job market benefits from having a multi-level support system and a training mode that promotes government–university–industry collaboration. Policies and demand from industrial sectors are involved in students' learning experience through channels such as financial support, project collaboration and networks. Doctoral students in Macao are strategic planners and actors in leveraging their human capital. As Macao becomes an emerging destination for cultivating high-level research labour, findings from this study capture a model of human capital formation in China's cross-system context.
Keywords: career trajectory; cross-system mobility; doctoral education; employability; human capital formation

Aspects that constitute citizens’ trust in e-government - A review and framework development - Lai, Chimeng; Marques, Alexandre Joao Lobo (Multidisciplinary Reviews, 2024)
The extent of citizens' trust in government determines the success or failure of e-government initiatives. Nevertheless, the idiosyncrasies of the concept and the broad spectrum of its approach still present relevant challenges. This work presents a systematic literature review on e-government trust while elaborating and summarizing a conceptual analysis of trust, introducing evaluation methods for government trust, and compiling relevant research on e-government trust and intentional behavior. A total of 26 key factors that constitute trust have been identified and classified into six categories: Government trust, Trust in Internet and technology (TiIT), Trust in e-government (TiEG), Personal Beliefs, Trustworthiness, and Trust of intermediary (ToI). The value added of this work consists of developing a conceptual framework of TiEG to provide a significant reference for future in-depth studies and research on e-government trust.
Keywords: Systematic Literature Review (SLR); framework; trust; trust in e-government

Impacts of Central Bank Digital Currency on Regional Economic Integration: Evidence from the Greater Bay Area of China - Lei, Weng Chi; Wang, Xinru (The Chinese Economy, 2024)
An increasing number of countries have launched their central bank digital currencies (CBDC) in recent years, but the economic impacts of CBDC adoption are underexplored. To empirically assess how CBDC adoption influences regional economic integration, this paper investigates the Greater Bay Area, where China carried out one of its first digital renminbi pilot programs. The Greater Bay Area provides a good example because the growing acceptance of digital renminbi in the area can potentially mitigate transaction costs and risks due to the exchange rate volatility of the Chinese renminbi, Hong Kong dollar, and Macao pataca. CBDC adoption can lead to greater real and financial integrations by facilitating cross-border trade in goods and services. This paper evaluates deviations from uncovered interest rate parity, purchasing power parity, and real interest rate parity across Guangdong, Hong Kong, and Macao based on monthly interest rate and price data from January 2016 to December 2022. The time series have mean values near zero, which validate the parity conditions and indicate high degrees of financial, real, and economic integrations. The Markov regime-switching regression model identifies three regimes: (1) pre-Covid, (2) post-Covid, and (3) post-CBDC. The Covid-19 outbreak brought lower integration and stability, but the launch of the CBDC restored some of the pre-Covid integration and stability. Regimes 1 and 2 are persistent, and transitions from Regime 3 back to Regime 1 are probable. Hence, this study finds evidence that CBDC adoption improves regional economic integration in the short and long run.
Keywords: Central bank digital currency; Greater Bay Area; digital renminbi; economic integration; financial integration

Revenue Management in Airlines and External Factors Affecting Decisions: The Harmonic Oscillator Model - Arraut, Ivan; Rosado, Wilson; Leong, Victor (Mathematics, 2024)
The Revenue Management (RM) problem in airlines for a fixed capacity, single resource and two classes has been solved before by using a standard formalism. In this paper we propose a model for RM by using the semi-classical approach of the Quantum Harmonic Oscillator. We then extend the model to include external factors affecting the people’s decisions, particularly those where collective decisions emerge.
Keywords: collective decisions; harmonic oscillator; revenue management; spontaneous symmetry breaking

Machine learning-based cardiac activity non-linear analysis for discriminating COVID-19 patients with different degrees of severity - Ribeiro, Pedro; Marques, João Alexandre Lobo; Pordeus, Daniel; Zacarias, Laíla; Leite, Camila Ferreira; Sobreira-Neto, Manoel Alves; Peixoto, Arnaldo Aires; de Oliveira, Adriel; Madeiro, João Paulo do Vale; Rodrigues, Pedro Miguel (Biomedical Signal Processing and Control, 2024)
Objective: This study highlights the potential of an Electrocardiogram (ECG) as a powerful tool for early diagnosis of COVID-19 in critically ill patients with limited access to CT–Scan rooms. Methods: In this investigation, 3 categories of patient status were considered: Low, Moderate, and Severe. For each patient, 2 different body positions have been used to collect 2 ECG signals. Then, from each collected signal, 10 non-linear features (Energy, Approximate Entropy, Logarithmic Entropy, Shannon Entropy, Hurst Exponent, Lyapunov Exponent, Higuchi Fractal Dimension, Katz Fractal Dimension, Correlation Dimension and Detrended Fluctuation Analysis) were extracted every 1s ECG time-series length to serve as entries for 19 Machine learning classifiers within a leave-one-out cross-validation procedure. Four different classification scenarios were tested: Low vs. Moderate, Low vs. Severe, Moderate vs. Severe and one Multi-class comparison (All vs. All). Results: The classification report results were: (1) Low vs. Moderate - 100% of Accuracy and 100% of F1–Score; (2) Low vs. Severe - Accuracy of 91.67% and an F1–Score of 94.92%; (3) Moderate vs. Severe - Accuracy of 94.12% and an F1–Score of 96.43%; and (4) All vs All - 78.57% of Accuracy and 84.75% of F1–Score. Conclusion: The results indicate that the applied methodology could be considered a good tool for distinguishing COVID-19’s different severity stages using ECG signals. Significance: The findings highlight the potential of ECG as a fast and effective tool for COVID-19 examination. In comparison to previous studies using the same database, this study shows a 7.57% improvement in diagnostic accuracy for the All vs All comparison.
Keywords: Accuracy; COVID-19; ECG signals; Machine learning classifiers; Non-linear analysis; –

Relationships among critical thinking disposition components of Chinese undergraduates: A moderated mediating effect analysis - Zhao, Yangyintao; Liu, Yong; Wu, Hao (International Journal of Educational Research, 2024)
Critical thinking (CT), as a form of higher-order thinking, is intended to help individuals form reasonable reflection and judgment to deal with increasingly severe employment situations. As the primary workforce in the labor market, undergraduates must possess a strong critical thinking disposition (CTD) to make better use of CT. Despite extensive research on components of CTD from the perspective of educational practices, there is limited emphasis on investigating the components and their relationships of CTD in the labor market and the impact of gender differences. Therefore, this study presented an analysis of 1535 Chinese undergraduates (Mage = 20.89; SD = 1.43) using the Employer-Employee-Supported Critical Thinking Disposition Inventory (2ES-CTDI), aiming to explore the CTD that undergraduates should possess before entering the labor market. The relationships among the components were examined using SmartPLS4.0 in conjunction with Partial Least Squares Structural Equation Modeling (PLS-SEM). Additionally, a multigroup analysis (PLS-MGA) with a measurement invariance (MI) test was conducted to validate the moderating effects of gender. The findings indicate that (a) self-efficacy has a significant negative effect on habitual truth-digging, and boys are more affected than girls, instant judgment plays a competitive partial mediating role in this relationship; (b) self-efficacy has a significant positive effect on instant judgment, and boys are more likely to make instant judgments than girls; (c) instant judgment significantly positively affects habitual truth-digging. These findings highlight the dynamic equilibrium among the internal components of CTD in the labor market and call for increased attention from educators to the importance of gender differences in the cultivation process.
Keywords: Critical thinking disposition; Labor Market; Moderated mediation; Undergraduates

Fintech Adoption: A Study of Users in the Guangdong-Macao In-Depth Cooperation Zone in Hengqin (China) - Weng, Chi Lei; Lampo, Alessandro (INTI JOURNAL, 2024)
Intended as an economic and development hub, the Hengqin Cooperation Zone aims to foster collaboration and integration between mainland China, Hong Kong, and Macao, serving as a platform for economic development and innovation among the three regions. The zone's development has increased demand for financial services, often offered through fintech. There is, however, a lack of interoperability between the fintech services currently used in Macao and Hengqin. This may hinder Macao users' adoption of the technology. Thus, our research objective is to identify the factors determining Macao residents' adoption of fintech services in the area and provide insights for service providers, developers, and policymakers. A framework based on the Technology Acceptance Model (TAM) and Theory of Planned Behavior (TPB) was used for this purpose. The responses of 103 Macao residents provided evidence that ease of use significantly and positively impacts the usefulness of the technology. This in turn influences attitudes towards fintech usage. Subjective norms and perceived behavioral control positively impact fintech adoption intentions. The fintech industry and the governments of Macao and Hengqin can work on improving technology's ease of use and usefulness. They can also promote them to Macao users, and provide the resources required for better access to fintech in the zone

Hawking Radiation as a Manifestation of Spontaneous Symmetry Breaking - Arraut, Ivan (Symmetry, 2024)
We demonstrate that black hole evaporation can be modeled as a process where one symmetry of the system is spontaneously broken continuously. We then identify three free parameters of the system. The sign of one of the free parameters governs whether the particles emitted by the black hole are fermions or bosons. The present model explains why the black hole evaporation process is so universal. Interestingly, this universality emerges naturally inside certain modifications of gravity.
Keywords: Hawking radiation; black holes; spontaneous symmetry breaking

Digital and Sustainable Trade Facilitation in Western Balkans Countries - Toshevska-Trpchevska, Katerina; Lei, Weng Chi (Florence); Stojkoski, Viktor (European Scientific Journal, ESJ, 2024)
After the Covid-19 Pandemic crisis in international economic relations it became evident that climate-smart aspects should be considered when re-establishing a new international trade order. International organizations have proclaimed that this momentum should be used to include climate-smart trade and investment provisions to enable sustainable development. It has been acknowledged that trade has an important role to play in the global response to climate change, providing economies with tools to draw on in their efforts to mitigate climate change and to adapt to its consequences. In this paper we focus the analysis on investigating the digital and sustainable component of trade facilitation measures applied in Western Balkans countries. To evaluate the importance of trade facilitation measures and their digital and sustainable components we apply standard gravity model with the data from UN Global Survey on digital and sustainable trade facilitation. The results show that trade facilitation measures are important for improving and increasing trade among the Western Balkans countries. Especially, measures connected to improving transparency procedures in trade and measures for alleviating trade formalities are most significant for increasing bilateral trade among Western Balkans countries. With a lower level of importance are the measures for improving cross-border paperless trade between these countries.
Keywords: Digital and sustainable trade facilitation; UN Global Survey on Digital and Sustainable Trade Facilitation; Western Balkans countries; gravity model

Teaching and learning with older adults: Research ethics, risk analysis, and covert research - Ní Bhroin, Áine; Morrison, Keith (Educational Gerontology, 2024)
This article reports a case study of older adults learning English in China. It indicates how, founded on consequentialist ethics, risk analysis, and safeguarding, it was decided to use covert research, drawing on the confluence of risk analysis, risk evaluation, risk management, safeguarding, research ethics, and important contextual and cultural features. Ethical principles of nonmaleficence, beneficence, safeguarding, and protection were addressed, and account was taken of the strength, likelihood, and consequences of risks, safeguards, and benefits, informed by Chinese cultural contexts, values, behaviors, and features of teaching and learning based on andragogy and geragogy. Implications are drawn for teaching and learning with older adults, advocating significant account to be taken of contextual factors.

Order parameter conditions from mutual information and symmetry conditions - Arraut, Ivan; Yu, Wing Chi (International Journal of Modern Physics B, 2024)
The mutual information method has demonstrated to be very useful for deriving the potential order parameter of a system. Although the method suggests some constraints which help to define this quantity, there is still some freedom in the definition. The method then results inefficient for cases where we have order parameters with a large number of constants in the expansion, which happens when we have many degenerate vacuums. Here, we introduce some additional constraints based on the existence of broken symmetries, which help us to reduce the arbitrariness in the definitions of the order parameter in the proposed mutual information method.
Keywords: Mutual information; order parameter; quantum phase transitions; spontaneous symmetry breaking

The cosmological constant emerging from a symmetry invariant - Arraut, Ivan (Modern Physics Letters A, 2024)
The cosmological constant is normally introduced as an additional term entering the Einstein–Hilbert (EH) action. In this letter, we demonstrate that, instead, it appears naturally from the standard EH action as an invariant term emerging from spacetime symmetries. We then demonstrate that the same constraint emerging from this invariant suppresses the short wavelength modes and it favors the long wavelength ones. In this way, inside the proposed formulation, the observed value for the vacuum energy density is obtained naturally from the zero-point quantum fluctuations.
Keywords: Dark energy; cosmological constant; zero point quantum fluctuations